Phthalates in sediments and aquatic biota across 30 rivers in Taiwan−long-term background monitoring of the environmental distribution of chemical substances trends, congener shifts, and ecological risks - Wei-Hsiang Chang; Quang-Oai Lu; Guang-Wen Lien; Hsiu-Ling Chen; Ching-Chang Lee (Water Research, 2026)

Integrated transcriptomic and proteomic analysis reveals isolation and culture associated molecular changes in neonatal porcine pancreatic cell clusters - Chang-Yi Chen; Chen-Ling Chen; Chen-Wei Kao; Chen-Yi Chen; Wan-Wen Hung; Ching-Wen Chang; Jyuhn-Huarng Juang; Wan-Chun Li (Molecular Biology Reports, 2026)
Background While porcine Neonatal Pancreatic Cell Clusters (NPCCs) were potential alternative source of islets, their immaturity and heterogeneity make them inefficiently ameliorate hyperglycemia in rodents. Our previous work showed that NPCCs regress to a transitional-like state immediately after isolation and undergo dynamic transcriptional changes during short-term in vitro culture. The present study aimed to further delineate the molecular cues underlying these changes during porcine pancreatic tissue isolation and cultivation. Method Transcriptomic and proteomic analysis were performed to compare Neonatal Porcine Pancreata (NPP), freshly isolated NPCCs (NPCCs-0D) and 3-day in vitro cultured NPCCs (NPCCs-3D). Using an in-house analysis pipeline, molecular differences between groups were identified. Results NPCCs‑0D showed lower molecular abundance compared with NPP and NPCCs‑3D groups under the tested conditions. Gene Sets Enrichment Analysis (GSEA) revealed that pathways related to receptor signaling and cell–microenvironment interactions were enriched in NPP and NPCCs‑3D, highlighting the importance of external regulation in maintaining pancreatic tissue architecture. In contrast. organelle- and catalysis-associated gene sets were enriched in NPCCs‑0D, suggesting a transcriptionally active and adaptive state. Conclusion Collectively, these findings indicate that molecular differences among NPP, NPCCs-0D, and NPCCs-3D reflect changes in tissue organization, cellular composition, and adaptation to isolation and culture conditions, rather than a linear differentiation process.

TGF-β-induced autophagy in pulmonary artery endothelial cells associated with chronic thromboembolic pulmonary hypertension - Ying-Ju Lai; Yen-Lin Huang; Ching-Yen Tsai; Po-Ru Chen; Chi-Jen Chang; Yung-Hsin Yeh; Celina De Almeida; Hsao-Hsun Hsu (Journal of Molecular Medicine, 2026)

Electrochemically synthesized potassium ferrate for diclofenac degradation: Performance, kinetics, and mechanistic insights - Chia-Hung Chen; Ching-Lung Chen; Hsin-Yu Chiang; Wu-Xing Chen; Amila Kasun Abeysinghe; Fang-Yu Liang; Chih-Chi Yang; Yen-Ping Peng (Journal of Water Process Engineering, 2026)

Geosynthetic-reinforced soil check dam: Case study and numerical analyses - Hsin-Ming Wu; Kuo-Hsin Yang; Chen-Cheng Kao; Chaicharn Thongthanawat; Suched Likitlersuang; Jyun-Yen Wang; Feng-Chi Huang; Wei-Lung Huang; Ching-Shui Kuo (Geotextiles and Geomembranes, 2026)

Flood-driven nutrient influx and phytoplankton succession in the subtropical waters of the Matsu Archipelago, Taiwan - Supriyadi; Yun-Chi Lin; Wan-Lin Chen; Kuo-Shu Chen; Gwo-Ching Gong; Sheng-Fang Tsai (Continental Shelf Research, 2026)

Upcycling of waste polycarbonate into polyallyls for degradable high-performance BMI/polyallyl-based thermosets/CFRPs - Che-Wei Lin; Lu-Ling Chen; Dula Daksa Ejeta; Ching-Hsuan Lin (Chemical Engineering Journal, 2026)

Interface-decoupled oxygen reduction via atomic Pt–Pd–Co clusters and vacancy-mediated kinetic buffering in a hierarchical carbon-supported multimetallic oxide platform - Yang-Yang Hsu; Ching-Hua Fan; Yu-Lin LEE; Sheng Dai; Kuan-Wen Wang; Nozomu Hiraoka; Hirofumi Ishii; Ting-Shan Chan; Chia-Shing Wu; Guo-Wei Lee; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Regulating cation disorder to stabilize oxygen redox in Li-rich DRX cathodes via Fe substitution - Chia-Ching Lin; Péter Udvarhelyi; Hao-Hsiang Chang; Tsung-Yi Chen; Zhenfei Cai; Yu Zhao; Han-Yi Chen; Denis Y.W. Yu (Chemical Engineering Journal, 2026)

Altered dynamic functional connectivity of the language network associated with electronegative L5 in patients with mild cognitive impairment - Ping-Song Chou; Sharon Chia-Ju Chen; Mei-Chuan Chou; Chung-Yao Hsu; Meng-Ni Wu; Ching-Kuan Liu; Chiou-Lian Lai (GeroScience, 2026)

Chlorpyrifos exposure induces inflammatory and immune dysregulation: An integrative in silico and in vitro analysis - Chen-Yu Chiang; Shih-Pin Chen; Ci-Wen Luo; Chun-Hung Su; Shiuan-Shinn Lee; Wen-Ying Chen; Chun-Jung Chen; Ching-Chi Tseng; Pin-Tzu Chen; Yin-Che Lu; Yu-Hsiang Kuan (Pesticide Biochemistry and Physiology, 2026)

Waste mop cloth recycling enables rapid, high-throughput removal of viscous winter oil spills - Min Zhang; Ching-Wen Lou; Kaifang Xie; Hengshu Zhou; Jia-Horng Lin; Guangting Han; Que Chen; Ting Dong (Journal of Hazardous Materials, 2026)

High-throughput toxicological profiling and ToxPi-based prioritization of chemical migrants from recycled paper used in food contact materials - Pei-Shan Chih; Pei-Chun Hsu; Rachelle D. Arcega; Wei-Hsiang Chang; Pei-Chu Tai; Ching-Chang Lee; Trias Mahmudiono; Wan-Ru Wang; Rong-Jane Chen; Hsiu-Ling Chen (Journal of Hazardous Materials, 2026)

L-theanine combined with epigallocatechin gallate to ameliorate alcoholic liver disease in mice by regulating the intestinal flora and activating the PPARα/FABP1/GPX4 pathway to inhibit ferroptosis - Jiayin Fu; Fei Yan; Dong Qu; Longhua Wang; Xiaohua Chen; Guotao Pu; Wei Yin; Ching Yuan Hu (Food Bioscience, 2026)

Real-world emission factors and inhalation health risks of PM-bound metals from workboats using ultra-low sulfur marine fuel - Po-Yen Chien; Chia-Hsiang Lai; Chia C. Wang; Dhruv Vishal Patel; Ajay Pillarisetti; Wu-Xing Chen; Chia-Hung Chen; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Dong-Ni Wu; I-Hsuan Wu; et al. (Environmental Pollution, 2026)

Probabilistic seismic hazard assessment for Taiwan: Updates and improvements in TEM PSHA2025 - Jia-Cian Gao; Jo-Chen Kao; Chung-Han Chan; Ray Y. Chuang; Cheng-Hung Chen; J. Bruce H. Shyu; Kuo-En Ching; Yu Wang; Kuo-Fong Ma (Engineering Geology, 2026)

Piezo-coupled triboelectric self-powered tactile sensor based on a self-healable polymer for object recognition - Manikandan Venkatesan; Wei-Wen Chen; Yu-Chen Wang; Yung-Chi Hsu; Jayashree Chandrasekar; Hao-Yuan Chen; Shih-Yu Lin; Chia-Jung Cho; Shang-Jui Huang; Ming-An Chung; Wen-Ya Lee; Yu Wen; et al. (Chemical Engineering Journal, 2026)

ENSO-modulated upstream rainout and convection predominantly control precipitation oxygen isotopes recorded in tree rings from Taiwan’s cloud forests - Nguyen-Xuan Hau; Masaki Sano; Takeshi Nakatsuka; Kevin J. Anchukaitis; Thanh Ngo-Duc; Ying-Shuo Chang; Zhen Li; Le-Thi Thuong; I.-Ching Chen (Climate Dynamics, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Phylogeny and taxonomic revisions of Piper (Piperaceae) in Taiwan - Po-Hao Chen; Chia-Hao Chang; Kuan-Ning Kung; Hung‑Chih Lin; An-Ching Chung; Chia-Ying Ou; Shih-Hui Liu (Journal of Plant Research, 2026)
Taiwan, located at the northernmost extent of Huxley’s Line, marks the furthest point along this biogeographic boundary where exchanges of flora and fauna occur. The genus Piper , a globally distributed and taxonomically complex group of both economic and evolutionary importance, has a convoluted taxonomic history in this transitional zone that requires comprehensive study. Here, we integrate morphological, molecular, and distributional data to revise the taxonomy of Taiwanese Piper , resolve their evolutionary relationships, and infer their biogeographic history. Our revision recognizes 11 species in Taiwan, including seven native taxa, of which three are endemic. The present analysis establishes the first comprehensive phylogenetic framework for Taiwanese Piper and reveals that native species arose from lineages on both sides of Wallace’s Line. Collectively, these findings provide the first evidence of bidirectional expansion within a genus in Taiwan and position Piper as an exemplary system for examining phylogeographic dynamics in transitional biogeographic zones.

Corrigendum to “L-theanine combined with epigallocatechin gallate to ameliorate alcoholic liver disease in mice by regulating the intestinal flora and activating the PPAR/FABP1/GPX4 pathway to inhibit ferroptosis” [Food Bioscience 83 (September 2026) 109552] - Jiayin Fu; Fei Yan; Dong Qu; Longhua Wang; Xiaohua Chen; Guotao Pu; Wei Yin; Ching Yuan Hu (Food Bioscience, 2026)

Consumer exposure risk to uropathogenic Escherichia coli from commonly consumed juice retailed in Taiwan: A quantitative microbial exposure assessment focused on sugarcane juice - Liu-Yean Goh; Ching-Wen Chang; L.-W. Antony Chen; Kuan-Hung Lu (Food Control, 2026)

Chlorpyrifos exposure induced cytotoxic death in pancreatic islet β-cells via the functional co-activation of JNK and AMPKα signaling downstream-mediated mitochondria-dependent apoptosis pathway - Ching-Yao Yang; Kuan-I Lee; Ya-Wen Chen; Shing-Hwa Liu; Kai-Min Fang; Chun-Ying Kuo; Wei-Cheng Lia; Kai-Chih Chang; Jun-An Ke; Cheng-Tien Wu; Chun-Fa Huang; Chin-Chuan Su (Food and Chemical Toxicology, 2026)

Activity of microbial dark carbon fixation along the gradient of hydrothermal plume inflow by subtropical shallow-water vents - Pei-Chi Ho; Hsiao-Chun Tseng; Wen-Chen Chou; Gwo-Ching Gong (Estuarine, Coastal and Shelf Science, 2026)

Biomass-inherent nitrogen doping in utilized chopsticks carbon for alkaline electrolysis - PratimaDevi Sivasubramanian; Yen-Ping Peng; Po-Hsun Lin; Subramanian Sakthinathan; Te-Wei Chiu; Ching-Lung Chen (Biomass and Bioenergy, 2026)

AlgaePath 2.0: An updated database for revealing algal coding and non-coding gene interactions in metabolic pathways - Kuan-Chieh Tseng; Wen-Lin Wang; Yen-Lin Shen; Hung-Teng Wang; Ching-Ya Yuan; Chien-Wen Yang; Ching-Nen Nathan Chen; Wen-Chi Chang (Algal Research, 2026)

Aurone analog LYK01 exerts oxidative stress-dependent antiproliferation, G2/M arrest, apoptosis, and DNA damage of oral cancer cells involving MAPK modulation - Yan-Ning Chen; Chia-Hung Yen; Ching-Yu Yen; Ammad Ahmad Farooqi; Meng-Yang Chang; Tsu-Ming Chien; Jen-Yang Tang; Hsueh-Wei Chang (Molecular and Cellular Biochemistry, 2026)

Longitudinal association between dietary quality trajectories and cognitive frailty in older adults: a 12-year study of the TIGER cohort - Ting-I. Lee; Bo-Yu Hsiao; Te-Hsuan Huang; Ling-Wei Chen; Yi-Chun Chou; Meei-Shyuan Lee; Jeng-Min Chiou; Yen-Ching Chen; Jen-Hau Chen (GeroScience, 2026)

Design of strontium ferrite nanoparticles anchored on MCM-41 modified glassy carbon electrode combined with computational studies for the electrochemical sensing of the anti-inflammatory drug mesalazine - Kiruthika Mariappan; Saravana Pandi Sivaji; Shen Ming Chen; Subramanian Sakthinathan; Ching-Lung Chen; Te-Wei Chiu; Prabakaran Muthusamy (Journal of Water Process Engineering, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

Uncovering hidden β-adrenergic agonist exposure from meat consumption through nationally representative human biomonitoring in Taiwan - Ho-Tang Liao; Tzu-Hsuan Peng; Chien-Jen Wang; Jing-Fang Hsu; Ching-Chun Lin; Wen-Harn Pan; Shu-Lih Chia; Pau-Chung Chen (International Journal of Hygiene and Environmental Health, 2026)

Circular bioprocessing of bovine blood for peptide-based antimicrobial and antibiofilm agents - Gan Huey; Asif Ali Bhat; Bao-Hong Lee; Ming‐Kuei Shih; Li-Jung Yin; You-Lin Tain; Yu-Wei Chen; Yeu-Ching Shi; Chih-Yao Hou (Bioresource Technology, 2026)

Unraveling rainfall-induced accelerated slope deformation through the integration of GNSS, seismic, and hydrologic data in Lantai, Taiwan - Yan-Hong Chen; Ya-Ju Hsu; Hsin-Hua Huang; Kuo-Lung Wang; Rou-Fei Chen; Horng-Yue Chen; Jyr-Ching Hu; Chuen-Fa Ni; Kuo-Jen Chang; Chih-Yu Kuo (Landslides, 2026)
Studying deep-seated catastrophic landslides is challenging due to their complex geological conditions, slow and imperceptible movements, limited real-time monitoring, and difficulties in accurately assessing sliding behavior. We examine slope instability in a deep-seated landslide-prone area located in Lantai, Taiwan, by analyzing the temporal evolutions of slope movement and rainfall. Using a non-invasive automatic monitoring system that integrates the Global Navigation Satellite System, seismic velocity changes derived from ambient noise interferometry, as well as rainfall and groundwater-level records, we investigate rainfall-induced accelerated slope deformation in 2015–2024. Our findings show that acceleration events are triggered when rainfall lasts over 30 h and cumulative rainfall exceeds 200 mm at the study site. Multiple sliding events show a consistent temporal sequence, in which rainfall triggers an immediate dv/v decrease of 2–4%, followed by GNSS horizontal displacement typically in the range of ~10–30 mm within 1–2 days, and a delayed groundwater-level rise of about ~3 m occurring 4–5 days after peak GNSS displacement rate. This time lag suggests the initial slope acceleration is associated with pore-pressure increases within the landslide mass. The one-dimensional hydrological model successfully simulates rainfall infiltration into the groundwater system, enabling prediction of delayed groundwater responses. This integrated monitoring-modeling framework improves hazard assessment and early warning for rainfall-induced deep-seated landslides and is broadly applicable worldwide.

Efficacy of NEPA for prevention of chemotherapy induced nausea and vomiting in head and neck cancer patients receiving cisplatin-based chemotherapy - Tzer-Zen Hwang; Chih-Chun Wang; Chuan-Chien Yang; Ching-Feng Lien; Chien-Chung Wang; Yu-Chen Shih; Shyh-An Yeh; Tai-Heng Yeh; Meng-Che Hsieh (European Journal of Clinical Pharmacology, 2026)

Two simplified analytical models considering skin effect on heat transfer in aquifer thermal energy storage systems - Chen Wang; Ching-Sheng Huang (Advances in Water Resources, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

First complete coding sequence of ovine herpesvirus 2 from a malignant catarrhal fever case of Formosan sambar deer in Taiwan: Genomic characterization and molecular epidemiology - Ruei-Sheng Tsai; Shih-Te Chuang; Hau-You Tzeng; Fong-Yuan Lin; Ching-Yu Tseng; Yi-Chen Chen; Wei-Li Hsu (The Veterinary Journal, 2026)

Use of AI-mediated image analysis to investigate the influence of environmental factors and recreational scuba diving on fish activity patterns in a marine protected area - Ching-Han Chang; Dong-Lin Li; Li-Shu Chen; Yi-Ta Shao (Regional Studies in Marine Science, 2026)

G2I-En predictions of indoor PM1, PM2.5, and PM10 exposure in child-specific microenvironments: Bridging the gap between low-cost sensors and mechanistic understanding in highly-polluted regions - Quang-Oai Lu; Wei-Hsiang Chang; Hsiu Ling Chen; Ching-Chang Lee (Journal of Cleaner Production, 2026)

Enabling fast Li+ transport and cycling stability in solid-state lithium metal batteries via fluorinated layered double hydroxide electrolyte fillers - John Peter Isaqu; Karuppiah Pandi; Yi-Shiuan Wu; Chun-Chen Yang; Ching-Yuan Su (Chemical Engineering Journal, 2026)

Direct Versus Indirect Bypass in Early-Stage Moyamoya (Suzuki I-III): A Propensity Score-Weighted Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Victor Gabriel El-Hajj; Michael Rizzuto; Matthews Lan; Pious Patel; Michael Baldassari; Arbaz Momin; Yazan Shamli Oghli; Marissa Tucci; Joseph Schaefer; et al. (Translational Stroke Research, 2026)

ICE1 plays a vital role in the development of pollen grains through regulating tapetum degradation and nutrient mobilization in Arabidopsis thaliana - Fa-Li Chang; Jer-Lun Kuo; Meng-Ting Wu; Ching-Hsing Liang; Shiang-Jiuun Chen; Chien-Chih Yang (Plant Molecular Biology, 2026)

Mechanisms of Coral Bleaching and Biomarkers for Early Detection - Michelle Glory G Jonik; Mahadi Mohammad; Sazlina Salleh; Ching-Nen Nathan Chen; Nur Ain Amani Abdul Mubin; Nur Hidayah Abdullah (Ocean Science Journal, 2026)

Application of a novel complex surfactant to enhance the bioremediation of weathered-diesel oil contaminated soils: mechanism and mesocosm-scale study - Wei-Ting Chen; Jiun-Hau Ou; Wei-Zhe Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Soils and Sediments, 2026)

Combined Associations of Lead and Arsenic Species with Liver Dysfunction and Hepatic Fibrosis Among Young Adults in Taiwan - Kai-Wei Liao; Chih-Wen Wang; Wei-Lun Hung; Ya-Ling Chen; Yee-How Say; Yang-Ching Chen; Wei-Shan Chin (Exposure and Health, 2026)

Canada's Forests Are Shifting From a Recovery‐Driven Carbon Sink to a Disturbance‐Driven Carbon Source - Salvatore R. Curasi; Joe R. Melton; Elyn R. Humphreys; Vivek K. Arora; Jason Beaver; Alex J. Cannon; Jing M. Chen; Txomin Hermosilla; Sung‐Ching Lee; Michael A. Wulder (Global Change Biology, 2026)
Canada's terrestrial ecosystems are critical to the global carbon cycle and are responding to unprecedented climate change and wildfire disturbance. However, our understanding of Canada's historical (~1920—present) carbon cycle is incomplete. There are also no published physically coherent (i.e., those that respect conservation laws) wall‐to‐wall estimates of all major carbon pools and fluxes for Canada. Existing assessments vary in spatial scale and methodology, yielding notable differences in the magnitude of Canada's land carbon sink. Moreover, inversions and data‐driven estimates do not disentangle the relative influence of disturbance, CO 2 fertilization, or climate change on Canada's carbon cycle. Here, we synthesize information from the site to Canada‐wide scale with a land surface model and the most comprehensive wildfire and wood harvest estimates available to provide the first physically coherent wall‐to‐wall estimates of all major carbon pools and fluxes for Canada. Using factorial model runs, we show that Canada's terrestrial ecosystems have been a carbon sink since the mid‐20th‐century, due to wildfire and timber harvest before 1940. Since the early 2000s, wildfire disturbance has been driving Canadian forests towards becoming a carbon source. Continued increases in wildfire activity will further weaken, and may ultimately reverse, Canada's role as a carbon sink.

Caffeic acid restores neurogenesis and synaptic integrity under glucolipotoxic stress by suppressing inflammation and pyroptosis - I-Ning Tsai; Xiang-Ning Xie; Ping-En Ko; Yung-Che Tsai; Ching-Chun Chen; Li-Sung Hsu; Chau-Jong Wang (Metabolic Brain Disease, 2026)

Immunogenicity Assessment for siRNA Therapeutics: A Risk-Based Proposal for Event-Driven Testing - An Zhao; Sarah Bond; Valerie Clausen; Mu Chen; Ching-Ha Lai; Joshua Zylstra; Christine Grimaldi; Michael A. Partridge (The AAPS Journal, 2026)

Novel DUAL Z-SCHEME Bi2MoO6/SO3H@g-C3N4/ZnS photocatalyst enhanced by persulfate activation for rapid ofloxacin degradation: Integrated experimental and DFT studies - Imran Nasir Appau Zahir Hussain; Sanjay Ballur Prasanna; Po-Chun Chen; Yu-Chien Lin; Ching-Wei Tung; Ren-Jei Chung (Journal of Water Process Engineering, 2026)

Coupling fine-scale molecular approaches with hydrodynamic modeling to inform conservation management of the endangered and endemic fiddler crab Xeruca formosensis - Kun-Ching Hung; Hui-Chen Lin (Journal of Environmental Management, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Improvement of flotation-sieving method for extracting soil microplastics and delineating measurable particle-size fractions - Yi-Jie Liao; Zi-Yi Chen; Bo-Ching Chen; Kai-Wei Juang (Environmental Geochemistry and Health, 2026)

New features of Peristediidae fishes in the South China Sea - Han Tian; Hsuan‐Ching Ho; Pan Liu; Mingting Li; Wei Xie; Yane Jiang; Xingle Guo; Jiajie Chen; Junpeng Yang; Kedong Yin (Journal of Fish Biology, 2026)
Deep‐diving surveys enable observations of new features of behavioural and functional dimensions of the fish that are typically missing from specimen‐based taxonomy. This study documents three rare armoured searobins (Peristediidae: Scalicus engyceros , Paraheminodus murrayi , Peristedion liorhynchus ) in Xianbei Seamount, Zhongsha Islands and Shenhu Canyon in the South China Sea. Not seen in the dead specimen, the fish in life exhibits bizarre shrimp‐like (in common sense) morphology: the lip barbels formed a laterally rake‐like structure, and the pectoral fins functioned as legs that literally ‘walked’ on the sediment. The fish S. engyceros showed both sideways and backward walking. The paired pectoral fins extrude outwards laterally like flat plates, supporting body balance during walking and swimming. When disturbed, individuals escaped rapidly using both pectoral appendages and tail fins, combining shrimp‐like jerky movements with typical fish swimming. The same species have been reported to occur in both the North and South Pacific oceans, suggesting that their oceanic distribution is by larval dispersal via oceanic currents such as equatorial and Indonesian throughflow currents. The co‐occurrence of three congeners in the same sea may hint local geographic speciation at work after settlement in a seamount habitat.

Development of a high-sensitivity dopamine sensor using copper tungstate nanoparticle-decorated carbon nanofibers on a glassy carbon electrode for analysis in various biological samples - Kiruthika Mariappan; Jing-Han Teng; Fu-Yi Chang; Shen Ming Chen; Jenn Fang Su; Ching-Lung Chen (Journal of Environmental Chemical Engineering, 2026)

Comparative study of promising CaAl-LDH and conventional immobilizing agents in mitigating ecological and health risks associated with soil Pb contamination - Jianying Yu; Nan Wei; Haochen Fang; Yining Chen; Tengfei Guo; Qijia Zhang; Yangyang Chen; Jiahong Yu; Jianyu Zhang; Zeliang Han; Kaiqin Xu; Ching Yuan; et al. (Journal of Environmental Management, 2026)

A proof-of-concept study on green mining of seawater calcium via biochar interfaces for fluoride removal and carbon dioxide capture - TsingHai Wang; Zi-Ying Lu; Yun-Chen Sung; Chia-An Tsao; Jenn-Fang Su; Ching-Lung Chen; Chung-Yu Guan (Journal of Environmental Chemical Engineering, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Methotrexate-loaded FeAuGd nanoparticles for synergistic magnetic-hyperthermia and chemotherapy - Kayalvizhi Samuvel Muthiah; Lenin Subramanian; Yen-Lin Chen; Udesh Dhawan; Yu-Chien Lin; Ching-Li Tseng; Ren-Jei Chung (Chemical Engineering Journal, 2026)

Cold Atmospheric Plasma as a Non-Thermal and Biocompatible Disinfection Strategy for Ultrasound Transducers - Ching-Yuan Lin; Kuan-Yi Lee; Dong-Jin Li; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2026)

Are There Increased Observations of Equatorial TC Genesis in the Satellite Era? Part I: Typhoon Vamei (2001) - Chih-Pei Chang; Ching-Hwang Liu; Yun-Lan Chen (Journal of Meteorological Research, 2026)

Interactive effects of retinal biomarkers and sleep on cognition: longitudinal evidence from community-dwelling older adults - Ting-Wen Chu; Yi-Ting Hsieh; Jeng-Min Chiou; Yao-Lin Liu; Yen-Ching Chen; Jen-Hau Chen (GeroScience, 2026)

Sensorimotor postural training induces multi-level cortical network reorganization in older adults enhancing efficiency and resilience - Yi-Ching Chen; Gwo-Ching Chang; Yi-Ying Tsai; Chen-Guang Zhao; Ing-Shiou Hwang (GeroScience, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Blockchain technology for risk management in food supply chain: A systematic literature review on emerging themes and sustainability implications - Shang-Ching Kuei; Mu-Chen Chen (Food Control, 2026)

Early-childhood exposure to per- and polyfluoroalkyl substances (PFAS) and neurobehavioral development in children - Chia-Jung Tung; Jia-Hwa Yang; Ching-Chun Lin; Chia-Yang Chen; Wu-Shiun Hsieh; Mei-Huei Chen; Pau-Chung Chen (Environmental Research, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Enhancing River Health through an Integrated ISC Assessment Methodology Enhancing river health through ISC assessments: a holistic method - Ching-Feng Chen; Chia-Ming Fan (Stochastic Environmental Research and Risk Assessment, 2026)

Isolation, characterization and antioxidant and cytotoxic activities of constituents from the orchid Oncidium spp. - Wen-Xuan Pan; Ya-Ching Chang; Shu-Feng Hsieh; Chun-Hong Chen; Kuan-Hua Chen; Po-Jen Chen; Sio-Hong Lam (Natural Product Research, 2026)

Functional analysis of wssv025 gene in the pathogenicity of white spot syndrome virus in Penaeus monodon - Shanel G. Manito; Cong-Yan Chen; Brandon Rafael de Jesús Castillo-Corea; Mary Nia M. Santos; Casiano H. Choresca; Fiona L. Pedroso; Christopher Marlowe Caipang; Han-Ching Wang; Fernand F. Fagutao (Fish & Shellfish Immunology, 2026)

Aldehyde dehydrogenase 2 mitigates acrolein-driven ferroptosis to preserve kidney function - Yu-Ming Kuo; Shiu-Dong Chung; Jui-Ting Chang; Hui-Min Yang; Chieh-Chen Lee; Chih-Ching Lin; Hsiang-Tsui Wang (Environmental Pollution, 2026)

A study on fast recognition of multi-class bridge damage based on improved Siamese ResNet50 with limited samples - Liujie Chen; Haodong Yao; Ke Gan; Yingzhuo Ye; Ching-Tai Ng; Jiyang Fu (Engineering Structures, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Atomic-scale CuOx–Fe3O4₋x/TiO2 heterostructures with defect synergy for highly selective and efficient reverse water–gas shift reaction - Po-Wen Cheng; Fa-Chih Pai; Chien-Yi Liu; Chih-Wei Hu; Ching-Yi Chou; Guo-Wei Lee; Chia-Shing Wu; Chun-Hong Kuo; Kuang-Kuo Wang; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Injectable near-infrared–responsive silk fibroin nanocomposite hydrogel enabling spatiotemporally controlled photothermal chemotherapy - Ling-Chu Yang; Ching-Wen Hwang; Shao-Hsuan Tsao; Hsin-Yao Lin; Yunching Chen; Dehui Wan (Chemical Engineering Journal, 2026)

Geochemical signatures of mud and core gases from the Milun Fault Scientific Drilling (MiDAS), Taiwan: Implications for fluid pathways and crustal degassing - Ching-Chou Fu; Kuo-Hang Chen; Kuo-Wei Wu; Pei-Ling Wang; Ai-Ti Chen; Vivek Walia; Kuo-Fong Ma (Chemical Geology, 2026)

Outcomes of Bypass Surgery in Patients with Moyamoya Syndrome Secondary To Sickle Cell Disease: a Multicenter Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Celine Yacoub; Nimer Adeeb; Antony A. Fuleihan; Sravanthi Koduri; Michael Baldassari; Matthews Lan; Pious Patel; Arbaz A. Momin; Elias Atallah; et al. (Translational Stroke Research, 2026)

Blood flow restriction modulates common drive to motor units and force precision: implications for neuromuscular coordination - Chia-Chan Wu; Yen-Ting Lin; Yueh Chen; Yi-Ching Chen; Ing-Shiou Hwang (European Journal of Applied Physiology, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Environmental DNA metabarcoding enriches the conventional survey of a high diverse fish community in the Dongsha atoll - You-Chen Liu; Yi-Ching Yang; Kang-Ning Shen; Chun-Huo Chiu; Te-Yu Liao (Frontiers in Marine Science, 2026)
To effectively conserve coral reef ecosystems, it is essential to monitor changes in fish fauna using minimally invasive methods. In this study, we conducted a fish survey in the Dongsha Atoll using eDNA metabarcoding. Analyzing 37 sequencing units from 26 water samples collected across 12 sites from May 2017 to September 2018, we identified 421 species from 79 families. Among these, 192 species had not been recorded in previous conventional surveys. Some of these newly recorded species are fast-swimmers, while others may be larvae or eggs, which are challenging to observe visually. However, 68% of species documented in previous records were not detected in our study. This limitation is likely due to insufficient samplings, primer specificity, fish characteristics, and rapid DNA degradation in the dynamic physical and chemical conditions (e.g., temperature, pH) of the coastal environment. Despite that eDNA metabarcoding cannot capture the full range of species within the atoll, it effectively complements visual census surveys by enriching our understanding of the diverse fish community in marine habitats.

Reef fish assemblages show limited response to giant clam density and restocking - Nathan W. Price; Yan-Zhen Meng; Wen-Yuan Zhang; Jinn-Shing Weng; Ching-Min Yang; Kao-Sung Chen; Joseph Heard; Wei-Chen Tung; Yu-De Pei; Colin Kuo-Chang Wen (Regional Studies in Marine Science, 2026)

Investigating the impact of numerical uncertainties in CFD-generated training data on neural network models for wind-turbine wake predictions - Maokun Ye; Yao Zhong; Hamn-Ching Chen; Decheng Wan (Ocean Engineering, 2026)

Formononetin protects against oxaliplatin-induced peripheral neurotoxicity via Nrf2/HO-1 antioxidant pathway without impairing anticancer efficacy - Yang-Chen Chang; Wan-Hsuan Lin; Horng-Huey Ko; Yi-Ching Lo; Hsun-Shuo Chang; Hui-Ching Lin; Yih-Fung Chen (NeuroToxicology, 2026)

Ferrous-driven microbial synergy enhances reductive dechlorination under sulfide stress - Che-Wei Lu; Po-Sheng Kuo; Ku-Fan Chen; Chih-Ching Chien; Chih-Ming Kao; Ssu-Ching Chen (Journal of Hazardous Materials, 2026)

Biochar-assisted detoxification of groundwater trichloroethene: Mitigating vinyl chloride accumulation and environmental risks via Dehalococcoides mccartyi-containing consortium - Che-Wei Lu; Ku-Fan Chen; Ching-Wen Tsai; Chao-Ling Yao; Ssu-Ching Chen (Journal of Environmental Management, 2026)

Advancing agrochemical surveillance: High-entropy MgFeCoNiZn layered double hydroxide for fenuron detection in soil and water - Chandini Ragumoorthy; Santhiyagu Sahayaraj Rex Shanlee; Shen-Ming Chen; Pichai Christina Ruby Stella; So-Qian Ching (Chemical Engineering Journal, 2026)

Revealing the operando ORR mechanism of single-atom catalysts anchored in nanobowl structures for advanced hydroxide exchange membrane fuel cells - Sun-Tang Chang; Hui-Xin Liu; Yi-Ching Chu; Ying-Rui Lu; Chen-Hao Wang (Chemical Engineering Journal, 2026)

A pH/glucose dual-responsive Janus dressing with optimized gradient modulus/tissue adhesion promotes diabetic wound healing by dynamic drug-payload release - Huabiao Ye; Ting Dong; Ruoxuan Li; Lihua Fang; Kaifang Xie; Guangting Han; Que Chen; Shan Chi; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2026)

Photothermal-pancaking synergy in interfacial absorption enables rapid purification of viscous oil-in-water emulsions - Ruoxuan Li; Chaofan Zhu; Ching-Wen Lou; Kaifang Xie; Jia-Horng Lin; Guangting Han; Que Chen; Ting Dong (Chemical Engineering Journal, 2026)

Closed-loop recovery of nickel sulfate hexahydrate from spent lithium-ion batteries for fabrication high-performances Ni-rich LiNi0.8Co0.1Mn0.1O2 cathode materials - Yola Bertilsya Hendri; Ching-Hsiang Hsu; Jia-Hao Hu; Yi-Shiuan Wu; Amun Amri; Chun-Chen Yang (Chemical Engineering Journal, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Emerging trends and clinical challenges in AI-enhanced emotion diagnosis using physiological data - Ying-Ying Tsai; Guan-Lin Wu; Yu-Jie Chen; Yen-Feng Lin; Ju-Yu Wu; Ching-Han Hsu; Lun-De Liao (Medical & Biological Engineering & Computing, 2026)

Interdecadal Decreases in Tropical Cyclone Activity Over the South China Sea During Fall and the Associated Interdecadal Index - Jien‐Yi Tu; Jau‐Ming Chen; Mei‐Yun Tsai; Ching‐Huang Chen (International Journal of Climatology, 2026)
For the period 1979–2023, tropical cyclone (TC) activity in the South China Sea (SCS) during fall (September–November) exhibited an interdecadal decrease around 2000. The decrease occurred in the observed number of total TCs, migratory TCs moving from the western North Pacific (WNP) into the SCS, and local TCs forming within the SCS. Interdecadal decreases in TC activity from 1979–1999 to 2001–2023 are affected by interdecadal components of lower‐level anticyclonic anomalies extending from the Bay of Bengal across the SCS into the tropical WNP. These components effectively hinder TC genesis and subsequent passage frequency over the SCS and the tropical WNP, resulting in interdecadal decreases in TC activity over the SCS. These anomalous anticyclones owe their existence to significant interdecadal variations in sea surface temperatures (SSTs) over the southeastern Indian Ocean (74°–92° E, 16° S‐EQ; zone A), mid‐latitude North Pacific (170° E–160° W, 26°–40° N; zone B), and off‐equatorial eastern North Pacific (150°–126° W, 6°–24° N; zone C). Given these modulating processes, an interdecadal index based on areal‐mean values of interdecadal SST components over the above three zones is computed as C−(A + B)/2. This interdecadal index exhibits a relatively coherent phase with interdecadal variability in total TCs over the SCS. For these two variables, their interdecadal time series have a significant correlation coefficient of 0.89. Interdecadal SST variations over the above three zones reflect salient variability features of the Pacific Decadal Oscillation (PDO). On the other hand, the linear trend feature in the global warming time series is obviously different from the interdecadal oscillation feature in the total TC time series over the SCS. The PDO plays a more important role than global warming in modulating interdecadal variability of TC activity over the SCS during fall.

Post‐Drought Vegetation Shifts Lead to Divergent Carbon, Water and Energy Responses in a Savanna Ecosystem of Southwest China - Palingamoorthy Gnanamoorthy; Junbin Zhao; Yajun Chen; Linjie Jiao; Boonsiri Sawasdchai; Zhang Jing; Abhishek Chakraborty; Pramit Kumar Deb Burman; Sung‐Ching Lee; Thomas A. M. Pugh; Yiping Zhang; Qinghai Song (Ecology Letters, 2026)
Increasing drought frequency and intensity affect biophysical functions of natural ecosystems. In tropical semi‐arid savannas, while immediate drought effects are well‐studied, the drought legacy effects on vegetation composition and associated ecosystem functions remain unclear. We used data of vegetation composition, net ecosystem CO 2 exchange, surface albedo and evapotranspiration (ET) in 2017–2022 from a savanna ecosystem, Southwest China, to investigate the legacy effect of an extreme drought event that occurred in 2019. Vegetation declined continuously for 3 post‐drought years. While tree numbers declined by 12%, shrub numbers dropped by 50% compared with pre‐drought levels, shifting vegetation dominance toward trees. This structural change caused sustained reductions in albedo and ET, which remained below pre‐drought levels, despite gross primary production recovering in the years immediately post‐drought. Vegetation shifts disproportionately impact ecosystem functions, with energy and water fluxes exhibiting greater vulnerability and potentially enhancing regional warming as droughts increase in Asian savannas.

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Determination of dissolved inorganic carbon export and the controlling factors in small mountainous Rivers, Taiwan - Man-Ching Choi; Pei-Hao Chen; Chi-Wang Tsui; Jr-Chuan Huang; Jun-Yi Lee; Li-Chin Lee (Journal of Hydrology, 2025)

Design of a novel copper tin oxide anchored with phosphorus-doped multiwalled carbon nanotubes on a glassy carbon electrode for highly selective monitoring of mercury ions - Selva priya Selvam; Kiruthika Mariappan; Shen Ming Chen; Ching-Lung Chen (Journal of Environmental Chemical Engineering, 2025)

Quantitative microbial exposure assessment of uropathogenic Escherichia coli in ready-to-eat chicken: Consumer risk and mitigation strategies in Taiwan - Liu-Yean Goh; Ching-Wen Chang; L.-W. Antony Chen; Kuan-Hung Lu (Food Research International, 2025)

White spot syndrome virus facilitates and relies on shrimp de novo nucleotide synthesis to support viral pathogenesis - Cong-Yan Chen; Der-Yen Lee; Shih-Shun Lin; Chun-Hung Liu; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Uncovering AphBvp-mediated regulation of PirAvp/PirBvp toxins and biofilm formation in AHPND causing Vibrio parahaemolyticus - Michael Eniola Ayenero; Ramya Kumar; Han-Ching Wang; Phuoc Thien Le; Yu-Hsuan Chen; Chu Fang Lo; Shin-Jen Lin; Hao-Ching Wang (Fish & Shellfish Immunology, 2025)

WSSV regulates malate-aspartate shuttle during infection - Yen Siong Ng; Fang-Jyun Guo; Kuan-Lun Huang; Cong-Yan Chen; Shu-Wen Cheng; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Light-activated dialdehyde cellulose nanocrystals (DACNC)-erythrosine generates ROS for Vibrio inactivation in whiteleg shrimp - Dewi Nur’aeni Setyowati; Shao-Chen Lu; Yong-Ching Heng; Jia-Wei Zhou; Yi-Min Chen; Shih-Chen Shi; Fu-I Lu (Fish & Shellfish Immunology, 2025)

Deciphering the mechanism behind shrimp body color regulation - Yun Chen; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Mitochondrial pyruvate carrier proteins mediate host-pathogen interactions during WSSV infection in shrimp - Yu-Chen Lin; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Unleashing instant on-site naked-eye detection by a portable NIR-SPR platform with organic upconversion - Li-Chen Su; Xin-Hui Wang; Chun-Jen Shih; Zhi-Hao Huang; Ying-Feng Chang; Chen-Kai Chang; Chi-Yun Wang; Yu-Ching Huang; Shun-Wei Liu (Chemical Engineering Journal, 2025)

Reconciling volume- and mass-based hygroscopicity parameters: Insights from coupled H-TDMA–APM measurements - Ta-Chih Hsiao; Ke-Ching Chen; Jun-Fa Ye; Si-Chee Tsay; Neng-Huei Lin (Atmospheric Environment, 2025)

Antioral cancer effects of ginger derivative 3-HDM exert oxidative stress-associated apoptosis and DNA damage - Kuan-Liang Chen; Hsin-I Lu; Ching-Yu Yen; Chung-Yi Chen; Tsu-Ming Chien; Jiiang-Huei Jeng; Bing-Hung Chen; Hsueh-Wei Chang (Molecular Biology Reports, 2025)

Associations between parental shift work exposure and pregnancy outcomes: role of father’s shift work status - Chih-Fu Wei; Mei-Huei Chen; Ching-Chun Lin; Yueliang Leon Guo; Shio-Jean Lin; Ya-Wen Chen; Wu-Shiun Hsieh; Pau-Chung Chen (International Archives of Occupational and Environmental Health, 2025)

Development and validation of a five-channel multiplex LC−ESI−MS/MS method for the quantification of carboxylic acids in urine - Wan-Hui Lu; Ju-Yu Chen; Te-I Weng; Ching-Hua Kuo; Guan-Yuan Chen (Analytica Chimica Acta, 2025)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Interspecific Competition Reduces Energy Expenditure by Decreasing Intragroup Conflict in a Social Burying Beetle - Bo‐Fei Chen; Yi‐Ching Li; Dustin R. Rubenstein; Angèle Rolland; Syuan‐Jyun Sun; Mark Liu; De‐Pei Chen; Sheng‐Feng Shen (Ecology Letters, 2025)
Assessing the physiological costs of sociality remains challenging due to complex interactions between environmental and social factors. To overcome this challenge, we integrated game theory with empirical research to examine how interspecific competition affects energy expenditure in the cooperatively breeding Asian burying beetle Nicrophorus nepalensis . Our nested tug‐of‐war model made two predictions: beetles facing interspecific competition would experience (1) lower physiological costs due to reduced investment in intragroup conflict, despite increased cooperative effort; and (2) decreasing physiological cost differences between dominance ranks. Using thermal imaging, we analysed body temperature as a proximal indicator of thermogenic effort during carcass work. Results supported our model's two key predictions: beetles competing with blowflies exhibited lower body temperatures, with less pronounced temperature differences between social ranks. Thus, reduced social conflict outweighs the energetic costs of increased cooperation in the face of external threats, providing insights into how environmental conditions shape energy allocation in social species.

Cover Image, Volume 28, Issue 12 - Bo‐Fei Chen; Yi‐Ching Li; Dustin R. Rubenstein; Angèle Rolland; Syuan‐Jyun Sun; Mark Liu; De‐Pei Chen; Sheng‐Feng Shen (Ecology Letters, 2025)

Fluoride removal from groundwater via powder-nano MgO adsorption: novel adsorbents development and mechanisms studies novel adsorbents development and mechanisms studies - Jiun-Hau Ou; Ssu-Ching Chen; Wei-Zhe Lin; Francis Verpoort; Rao Y. Surampalli; Chih-Ming Kao (Environmental Science and Pollution Research, 2025)

Social-ecological memories as references for biodiversity restoration and conservation action in coastal community - Chia-Hsuan Hsu; Yu-Wen Wu; Jiefeng Kang; Hung-Kai Chiu; Mei-Ching Li; Wei-Ting Chen (Marine Pollution Bulletin, 2025)

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

Per- and polyfluoroalkyl substances (PFAS) in resource recovery: Transforming challenges into opportunities for sustainable nutrients and biosolids management - Ahmed I. Yunus; Thomas Igou; Srinivas Jalla; Elliot Reid; Abigail Cohen; George Yuzhu Fu; Ching-Hua Huang; Athena Verghis; Yongsheng Chen; Joe F. Bozeman (Process Safety and Environmental Protection, 2025)

Gastrointestinal stability and DPP-IV inhibitory activity of tilapia (Oreochromis niloticus) viscera hydrolysate-derived novel peptides LPCL and TPFLPDE, with LPCL-modulated GLP-1 and PepT1 expression in STC-1 cells - Rhessa Grace Guanga Ortizo; Ching-Shu Lai; Choirul Anwar; Vishal Sharma; Pei-Pei Sun; Chiu-Wen Chen; Cheng-Di Dong; Mei-Ling Tsai (Food Research International, 2025)

Epigenetic transgenerational effects of prenatal exposure to 2,2′,4,4′-tetrabromodiphenyl ether on sperm function and DNA methylation in rat offspring - Ching-Shu Lai; Wei-Cheng Hsu; Jenq-Renn Chen; Bing-Mu Hsu; Kuo-Hsin Lee; Ping-Hsun Wu; Ping-Chi Hsu (Food and Chemical Toxicology, 2025)

Anaerobic Fe(II) bio-oxidation by Cyanidiophyceae to enhance As(III) removal: A novel and efficient biological material toward resilient remediation - Nhu Anh Thi Than; Liang Ching Hsu; Yu-Hsien Chen; Kamonchanok Huangmee; Chun-Chieh Wang; Heng Yi Teah; Yu-Min Tzou; Yen-Lin Cho; Yu-Ting Liu (Chemical Engineering Journal, 2025)

Natural lignan justicidin A-induced mitophagy as a targetable niche in bladder cancer - Kai-Hsun Chang; Hsin-Chih Chen; Ching-Ying Chen; Shu-Ping Tsai; Man-Yuan Hsu; Pao-Yuan Wang; Shan-Ying Wu; Chun-Li Su (Chemico-Biological Interactions, 2025)

Immune signaling and drought tolerance mediated by NDR1-AHA5 regulation of H⁺–ATPase, guard cells, and homeostasis - Yi-Ju Lu; Huan Chen; Alex Corrion; Pai Li; Saroopa Samaradivakara; Ching Man Wai; Hikaru Sakamoto; Patrícia Santos; Robert VanBuren; Yongsig Kim; Brad Day; Ilker Buyuk (Plant Cell Reports, 2025)

Interactions between turnover rate and bioactivity of atractylenolide III in Atractylodes macrocephala rhizome in the theory of crude drugs’ pairs and prescriptions in traditional Chinese and Japanese Kampo medicine - Pei-Ying Chou; Yung-Jia Chiu; Che-Chun Lin; Lih-Geeng Chen; Shih-Yi Hsiung; Toshiaki Makino; Ching-Chiung Wang (Journal of Natural Medicines, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Changes in Prooxidant and Antioxidant-Related Trace Element Levels During Helicobacter pylori Eradication Therapy - Ching-Chiang Lin; Ming-Kun Ku; Hsueh-Chiao Liu; Hui-Wen Chou; Po-Chih Chen; Deng-Chyang Wu; Yeou-Lih Huang (Biological Trace Element Research, 2025)

Vertical distribution of picoplankton across a cold eddy in the West Pacific Ocean - Patrichka Wei Yi Chen; Madeline Olivia; Chia Mei Chang; Gwo Ching Gong; Chung-Chi Chen; Sen Jan; Clara Natalie Annabel; An Yi Tsai (Frontiers in Marine Science, 2025)
Mesoscale eddies are recognized as an important driver of environmental and microbial dynamics in the Pacific Ocean. However, their specific impact on microbial community vertical distribution remains underexplored. In contrast with the surrounding waters, a cyclonic cold eddy can provide nutrients to the photic zone, increasing primary production and altering microbial communities. A field investigation was conducted in the West Pacific Ocean during cyclonic cold eddy propagation to determine the impact of cold eddies on bacteria and picophytoplankton. Within the cold eddy region, dissolved inorganic nitrate concentrations were higher than those in adjacent water at 100-m depth. Flow cytometric analyses were used to estimate the abundances of picoplankton populations (heterotrophic bacteria and picophytoplankton) in seawater samples collected from the surface to 1,000 m. In this study, Prochlorococcus was the dominant component of abundance at depths above 100 m (62% to 95%). Interestingly, when compared to outside of eddy stations, cyclonic eddy-affected regions had the lowest maximum value of Synechococcus and Prochlorococcus . In contrast to Synechococcus and Prochlorococcus , the distribution pattern of picoeukaryotes abundance showed maxima values (>0.4 × 10 3 cells mL −1 ) at 100–200-m depth within cyclonic eddy-affected regions. Overall, the abundance of bacteria was approximately 2 × 10 5 cells mL −1 at the surface and increased to >4 × 10 5 cells mL −1 at 200-m depth at stations outside the eddy. However, peaks in bacterial abundance were observed at 50-m depth, and abundance decreased with increasing depth in the cyclonic eddy-affected regions. In the oligotrophic open ocean, our findings contribute to a better understanding of the biological response of mesoscale eddies.

Nutrient supply, prey body size and biomass determine the trophic structures in marine plankton food webs - Pei-Chi Ho; Chia-Ting Chen; Noboru Okuda; Pei-Ling Wang; Gwo-Ching Gong; Chih-hao Hsieh (Progress in Oceanography, 2025)

Exploring Chemical Composition and α-Glucosidase Inhibitory of Nelumbo nucifera Seedpods - Pai-Hsin Chen; Ching-Kuo Lee (Phytochemistry Letters, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Enhanced electrochemical nitrate reduction: Geometrically tailored Pd/Cu electrodes for superior nitrogen selectivity - Thi Nhat-Tuyen Nguyen; Kiruthika Mariappan; Muhammad Sheraz Ahmad; Feng-Ze Tian; Ching-Wei Tung; Jenn Fang Su; Chao-Lin Liu; Ching-Lung Chen (Journal of Environmental Chemical Engineering, 2025)

Segmentation of the Manila subduction zone and slab tearing beneath the Philippine mobile belt - Shu-Kun Hsu; Wen-Nan Wu; Lien-Kai Lin; Shiou-Ya Wang; Yi-Ching Yeh; Leo T. Armada; Carla B. Dimalanta; Kuan-Ting Chen; Yun-Jie Tsai; Ching-Hui Tsai (Journal of Asian Earth Sciences, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

Gallium maltolate and cisplatin co-treatment effectively targets triple-negative breast cancer in spheroid and mouse models - Ya-Wen Yang; Yu-Chen Hsieh; Ching-Yu Liu; Chun-Kai Pan; Zi-Yu Pan; Kai-Yin Lo (Toxicology and Applied Pharmacology, 2025)

Antimony induces mitochondria-dependent and ER stress-triggered apoptosis via the oxidative stress-activated JNK signaling pathway in pancreatic islet β-cells - Ken-An Lin; Chin-Chuan Su; Shing-Hwa Liu; Kuan-I. Lee; Kai-Min Fang; Chih-Hsin Tang; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology, 2025)

Sol-gel assisted synthesis of rare earth (4f)‐transition metal (3d) binary metal oxide: Application to electrocatalytic oxidation of carbamate insecticide - Yamunadevi Kandeepan; Tse-Wei Chen; Sivaprakash Sengodan; Shen-Ming Chen; Wei-Ching Cheng (Process Safety and Environmental Protection, 2025)

A hybrid diagnostic system for corrosion mechanism identification in petrochemical equipment: Integrating Bayesian probabilities and association rule - Yen-Ju Lu; Ching-Wen Wang; Chen-Hua Wang (Process Safety and Environmental Protection, 2025)

Heterostructure La0.5Sr0.5Fe0.4Mn0.6O3/TiC/porous graphene oxide for efficient trace-level detection of methiocarb pesticide in environmental samples - Francis Packiaraj Don Disouza; Shen-Ming Chen; Michael Ruby Raj; So-Qian Ching; Matar Alsalwi; Prabhakarn Arunachalam; Chelladurai Karuppiah (Process Safety and Environmental Protection, 2025)

Precision-engineered Si@NiCo2O4 surfaces via tailored amine functionalization for trace-level detection of bendiocarb in ecological and edible samples - Pandiyan Parkavi; Santhiyagu Sahayaraj Rex Shanlee; Shen-Ming Chen; Mariya Antony John Felix; So-Qian Ching (Journal of Water Process Engineering, 2025)

Effect-based high-throughput screening of environmental water samples: Focus on liver toxicity pathways and endocrine disruption - Olivia Lautan; Ssu-Ning Chen; Chin-Ching Lu; Yi-Hsuan Huang; Hsiu-Ling Chen; Pei-Shan Chih; Rong-Jane Chen (Journal of Hazardous Materials, 2025)

Community shift of aquatic insects following waste-water treatment implementation at Dongda Creek, Taichung City, Taiwan - Lilibeth A. Bucol; Ching-Chen Lee; Lan-Wai Yeh; Li-Wei Wu; Jyh-Min Chiang (Journal of Asia-Pacific Entomology, 2025)

Hyperbaric oxygen therapy attenuates carbon monoxide-induced lung injury by restoring mitochondrial dynamics and suppressing Pink1/Parkin-mediated mitophagy - Tzu-Hao Chen; Chien-Chin Hsu; Ching-Ping Chang; Chien-Cheng Huang; Ying-Jan Wang (Environmental Pollution, 2025)

Causes, emission characteristics, and health risks of persistent free radicals and reactive oxygen species in PM2.5 produced by smoldering incense - Yu-Chieh Wang; Bo-Yu Chen; Yen-Hsien Li; Tzu-Hsien Tseng; Chon-Lin Lee; Wei-Min Ching (Atmospheric Pollution Research, 2025)

Effects of fertilizers on arsenic accumulation in ratoon rice: implications for human health risks - Kai-Wei Juang; Han-Ting Hsu; Wan-Ting Chiao; Chien-Hui Syu; Bo-Ching Chen (Environmental Geochemistry and Health, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Prenatal exposure to air pollution and pediatric acute leukemia: A nationwide study - Hsin-Chien Yen; I-Chieh Chen; Wei-Szu Lin; Kuan-Chia Lin; Meng-Che Wu; Ching-Heng Lin (Science of The Total Environment, 2025)

Robustness of gametogenesis in the scleractinian coral, Tubastraea aurea, in the shallow-water hydrothermal vent field off Kueishan Island, northeastern Taiwan - Emily Corrigan; Chieh-Jhen Chen; Bo-Song Wang; Sylvie Dufour; Ching-Fong Chang (Science of The Total Environment, 2025)

Utilizing natural compounds as ligands to disrupt the binding of SARS-CoV-2 receptor-binding domain to angiotensin-converting enzyme 2, impeding viral infection - Jingyi Wu; Ting-Hsu Chen; Zi-han Shen; May-Jywan Tsai; Max K. Leong; Yan-qiang Huang; Ching-Feng Weng (Phytochemistry Letters, 2025)

Adaptive fluoride removal across concentration scales: Potential roles of microbial and acicular gypsum interactions in nitrogen and phosphate cycling - Ying-Liang Yu; Wei-Han Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Hazardous Materials, 2025)

Enhanced removal of antimony, arsenic and cadmium by bone char in co-contaminated aqueous systems: A lattice level mechanistic understanding - Prakash C. Loni; Biqing Liang; Ching-Yu Chiang; Yao-Chang Lee; Jagat Rathod; Ci-Hong Ciou; Pei-Hua Wu; Wei-Hsin Chen (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunology, 142: 109,134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Vacuum-assisted carbon molecular sieve membrane reactor for non-oxidative ethane dehydrogenation - Antara Bhowmick; H. Hasan Koybasi; Ching-En Ku; Genwei Chen; Sooyeon Hwang; Chen Zhang; Dionisios G. Vlachos; Dongxia Liu (Chemical Engineering Journal, 2025)

Sequential slot-die coating of perovskite solar cell modules under ambient conditions with precise phase-transition control - Chia-Feng Li; Shih-Han Huang; You-Ren Chen; Hou-Chin Cha; Ssu-Yung Chung; Yu-Hung Hsiao; Feng-Yu Tsai; Yu-Ching Huang (Chemical Engineering Journal, 2025)

Development and Evaluation of a Dual-Mode Cold Atmospheric Plasma System for Stage-Specific Wound Healing Applications - Ching-Yuan Lin; Dong-Jin Li; Yu-Shen Chen; Chia-Wei Hsu; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Development of a colorimetric loop-mediated isothermal amplification (cLAMP) assay for the rapid and visual detection of Aeromonas dhakensis infection in aquaculture - Suat Moi Puah; Wei Ching Khor; Yen Ching Lim; Kyaw Thu Aung; Tien-Tien Vicky Lau; Chen Chen Yong; Po Teen Lim; Chui Pin Leaw; Kek Heng Chua (Aquaculture, 2025)

Reimagining species on the move across space and time - Alexa L. Fredston; Morgan W. Tingley; Montague H.C. Neate-Clegg; Luke J. Evans; Laura H. Antão; Natalie C. Ban; I-Ching Chen; Yi-Wen Chen; Lise Comte; David P. Edwards; Birgitta Evengard; Belen Fadrique; et al. (Trends in Ecology & Evolution, 2025)

Palmitic acid and lipopolysaccharide induce macrophage TNFα secretion, suppressing browning regulators and mitochondrial respiration in adipocytes - Tsui-Chun Tsou; Szu-Ching Yeh; Feng-Yuan Tsai; Pei-Yu Chen (Toxicology and Applied Pharmacology, 2025)

Polycyclic aromatic hydrocarbon-aryl hydrocarbon receptor signaling regulates chronic inflammation in lung-gut axis - Tzu-Yu Cheng; Ching-Shan Luo; Po-Hao Feng; Kuan-Yuan Chen; Chih-Cheng Chang; Nguyen Van Hiep; Yueh-His Chen; Yun-Kai Yeh; Sheng-Ming Wu (Toxicology and Applied Pharmacology, 2025)

High-performance nitrogen selectivity through selective nitrate reduction on nickel-supported copper foam architectures - Thi Nhat-Tuyen Nguyen; Kiruthika Mariappan; Jih-Hsing Chang; TsingHai Wang; Subramanian Sakthinathan; Chao-Lin Liu; Ching-Lung Chen (Process Safety and Environmental Protection, 2025)

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

Response and recovery times of vegetation productivity under drought stress: Dominant factors and relationships - Chengyun Wang; Jie Chen; Sung-Ching Lee; Lihua Xiong; Tianhua Su; Qian Lin; Chong-Yu Xu (Journal of Hydrology, 2025)

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa by product as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunol. (2023) 142 109134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Taiwan population-based epigenetic clocks and their application to long-term air pollution exposure - Ching-chun Huang; Shih-chun Pan; Pau-chung Chen; Yue Leon Guo (Environmental Research, 2025)

Mechanistic insights into chloroethene dechlorination by Dehalococcoides mccartyi strain CWV2: A multi-omics perspective - Chih-Ming Kao; Ku-Fan Chen; Po-Sheng Kuo; Chih-Ching Chien; Che-Wei Lu; Ssu-Ching Chen (Water Research, 2025)

Effects of pterostilbene on inducing apoptosis in normal bladder and bladder cancer cells - Chen-Hsun Ho; Chia-Kwung Fan; Yi-Chen Chu; Shih-Ping Liu; Po-Ching Cheng (Tissue and Cell, 2025)

A potential closed-loop reutilization of iron sludge for wastewater treatment through the solid state reaction with spent coffee grounds - Kun Qin; TsingHai Wang; Wei-Tong Li; Zi-Ying Lu; Cheng-Yu Li; Wei-Fan Kuan; Jenn-Fang Su; Ching-Lung Chen (Process Safety and Environmental Protection, 2025)

Fabrication of sesamin-loaded sodium caseinate nanoparticles: Insight to characterization, in vitro digestion, and molecular docking analysis - Wan-Yi Liu; Tzu-Yu Chen; Yun-Shan Hsieh; Yung-Yi Cheng; Shiou-Ling Li; Li-Ching Chang; Yu-Tse Wu (Food Bioscience, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

Prenatal melatonin reprograms liver injury in male pups caused by maternal exposure to a high-fat diet and microplastics - Yu-Jen Chen; Hong-Ren Yu; Ching-Chou Tsai; Mao-Meng Tiao (Apoptosis, 2025)

Interannual variations in the size structure of swordtip squid Uroteuthis edulis in the southern East China Sea - Tzu-Yun Ching; Chih-Shin Chen (Fisheries Research, 2025)

3D Bismuth oxyhalide flowers intertwined 1D graphitic carbon fibers catalyst: A disposable electrochemical sensor for the detection of carcinogenic 3,3′,5,5′-Tetrabromobisphenol A in water samples - Thangavelu Sakthi Priya; Tse-Wei Chen; Shen-Ming Chen; Wei-Ching Cheng (Process Safety and Environmental Protection, 2025)

Toxicity evaluation and prioritization of recycled plastic food contact materials using in silico tools - Rachelle D. Arcega; Pei-Shan Chih; Pei-Chun Hsu; Wei-Hsiang Chang; Rong-Jane Chen; Trias Mahmudiono; Ching-Chang Lee; Hsiu-Ling Chen (Journal of Hazardous Materials, 2025)

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Rapid evaluation of apigenin bioavailability and hypouricemic bioactivity by targeted metabolomics study in enterohepatic microenvironment mimetic cell culture model - Su-Jung Hsu; Hui-Chen Chung; Chia-Hsuan Chang; Yi-Chi Liao; Ta-Wei Liu; Shu-Mei Lin; Ching-Kuo Lee (Food Research International, 2025)

Deep learning for the detection of good hygienic practices control measures for food handlers - I-Chun Chen; Ching-Ho Chi; Hao-Hsiang Ku (Food Control, 2025)

Tensile behavior of Q890 and Q960 high-strength steel butt joints after corrosion - Man-Tai Chen; Zhichao Gong; Huan Cao; Chen Shen; Fengming Ren; Johnny Ching Ming Ho; Mianheng Lai (Engineering Structures, 2025)

Singular value decomposition of near-field electromagnetic data for compressing and accelerating deep neural networks in the prediction of geometric parameters for through silicon via array - Song-En Chen; Eugene Su; Chih-Chung Wang; Jia-Han Li; Chao-Ching Ho (Computer Physics Communications, 2025)

Chlorpyrifos-oxon results in autophagic flux dysfunction contributing to neuronal apoptosis via a ROS/AMPK/CHOP activation pathway - Jui-Ming Liu; Kuan-I Lee; Chin-Chuan Su; Kai-Min Fang; Shing-Hwa Liu; Shih-Chang Fu; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Ya-Wen Chen; Ching-Yao Yang; Chun-Fa Huang (Chemico-Biological Interactions, 2025)

Correction: Intermittent Hypoxia Activates N-Methyl-D-Aspartate Receptors to Induce Anxiety Behaviors in a Mouse Model of Sleep-Associated Apnea - Yun Fan; Mei-Chuan Chou; Yen-Chin Liu; Ching-Kuan Liu; Chu-Huang Chen; Shiou-Lan Chen (Molecular Neurobiology, 2025)

Preliminary analysis of landslides induced by the 3 April 2024 Mw 7.4 Hualien, Taiwan earthquake - Yi Chen; Chuang Song; Zhenhong Li; Bo Chen; Chen Yu; Jyr-Ching Hu; Xingmin Cai; Shuang Zhu; Qianwen Wang; Yixin Ma; Changjun Gu; Suju Li; et al. (Landslides, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Establishment of a pseudotargeted LC‒MS/MS workflow for analyzing triglycerides in biological samples - Wei-Chieh Wang; Chin-Yi Wang; Ta-Chen Su; Po-Chih Lin; Wen-Chi Chang; Kuei-Pin Chung; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

4-Anilinoquinolinylchalcone derivatives mediate antifibrotic effects through ERK/MRTF—a signaling pathway crosstalk - Padhmavathi Selvam; Chih Hua Tseng; Ching Tung Wang; Yu-Yo Sun; Yeh-Long Chen; Yu-Tse Kao; Hans-Uwe Dahms; Chih Mei Cheng (Environmental Science and Pollution Research, 2025)

Junceellolide Q, a new polyacetoxybriarane from the delicate sea whip octocoral Junceella fragilis - Yih-Gang Goan; Mingzi M. Zhang; Lun Kelvin Tsou; Zhi-Hong Wen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yu-Jen Wu; Jih-Jung Chen; Hai Nhat Do; Pei-Luen Jiang; Ping-Jyun Sung (Phytochemistry Letters, 2025)

An experimental study of the voltammetric quantification of hazardous pollutant nitroaniline using a 3D flower-like manganese ferrate lattice occupied active carbon black - Antony Jasmine Vincent John; Saranvignesh Alagarsamy; Tse-Wei Chen; Shen-Ming Chen; Ching So-Qian; Elayappan Tamilalagan; Wedad A. Al-onazi; M. Ajmal Ali; Mohamed S. Elshikh (Journal of Water Process Engineering, 2025)

Development of a real-time dynamic inundation risk assessment approach on paddy fields during typhoons: Exploration of adaptation strategies and quantification of risks - Bing-Chen Jhong; Feng-Wen Chen; Ching-Pin Tung (Journal of Environmental Management, 2025)

Effects of humidity on photocatalytic oxidation of elemental mercury by rGO-modified CeO2/TiO2: Kinetic analysis and experimental exploration - Ji-Ren Zheng; Chung-Shin Yuan; Ting-Yu Chen; Ching-Ching Hsu; Chung-Hsuang Hung; Huazhen Shen (Journal of Environmental Chemical Engineering, 2025)

Boosting anode interfacial stability in All-Solid-State lithium hybrid batteries with MCMB-Modified stainless steel current collector - Abebe Taye Fenta; Yosef Nikodimos; Semaw Kebede Merso; Ayenew Meniber; Misganaw Adigo Weret; Kassie Nigus Shitaw; Bereket Woldegbreal Taklu; Felika Valencia; Tsung-I Yeh; Chia Lung Hsieh; Chia-Yu Chang; Ya-Jun Liu; et al. (Chemical Engineering Journal, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Kirenol ameliorates endotoxin-induced acute lung injury by inhibiting the ERK and JNK phosphorylation–mediated NFκB pathway in mice - Frank Cheau-Feng Lin; Shih-Pin Chen; Sheng-Chien Lin; Ching-Chi Tseng; Stella Chin-Shaw Tsai; Yu-Hsiang Kuan (Inflammopharmacology, 2025)

Association Between Urinary Paraben Concentrations and Early Renal Impairment in Young Adults in Taiwan - Wei-Shan Chin; Yung-Ning Chuang; Wei-Lun Hung; Yee-How Say; Ling-Chu Chien; Yang-Ching Chen; Ho-Ching Kao; Man-Ping Luo; Chia-Huang Chang; Kai-Wei Liao (Exposure and Health, 2025)

Akkermansia muciniphila: promises and pitfallsfor next-generation beneficial microorganisms - Yantong Liu; Zonglun Li; Sze Ching Lee; Shurui Chen; Feifei Li (Archives of Microbiology, 2025)

Cortical adaptations in regional activity and backbone network following short-term postural training with visual feedback for older adults - Yi-Ching Chen; Yi-Ying Tsai; Wei-Min Huang; Chen-Guang Zhao; Ing-Shiou Hwang (GeroScience, 2025)

The herbicide 2,4-dichlorophenoxyacetic acid induces pancreatic β-cell death via oxidative stress-activated AMPKα signal downstream-regulated apoptotic pathway - Ken-An Lin; Chin-Chuan Su; Kuan-I Lee; Shing-Hwa Liu; Kai-Min Fang; Chih-Hsin Tang; Wei-Cheng Lia; Chun-Ying Kuo; Kai-Chih Chang; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology Letters, 2025)

Spatiotemporal variation in marine plankton communities driven by environmental changes in the East China sea - Chia-Ting Chen; Pei-Chi Ho; Fan-Sian Lin; Esther Wong; Fuh-Kwo Shiah; Gwo-Ching Gong; Chih-hao Hsieh (Progress in Oceanography, 2025)

Artificial digestion represents the worst-case scenario for studying nanoplastic fate in gastrointestinal tract - Giselle Lee; Ya-Jhu Jhang; Yu-Tung Jhang; Yen-Chen Chang; Hui-Wen Chang; Chun-Yu Chuang; Yung-Kun Chuang; Ching-Wei Lin; I-Lun Hsiao (Journal of Hazardous Materials, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Interactions between environmental pollutants and gut microbiota: A review connecting the conventional heavy metals and the emerging microplastics - Xiaochen Chen; Zengdi Zhang; Yushiang Hsueh; Chunpeng Zhang; Jianying Yu; Junyu Zhu; Jia Niu; Naiyi Yin; Jianyu Zhang; Xiaoyu Cui; Xianhua Liu; Kaiqin Xu; et al. (Environmental Research, 2025)

Hijacking the hyaluronan assisted iron endocytosis to promote the ferroptosis in anticancer photodynamic therapy - Hong Deng; Jiayu Chen; Huimin Wang; Runmeng Liu; Yiyi Zhang; Hui Chang; Ching-Hsuan Tung; Weiqi Zhang (Carbohydrate Polymers, 2025)

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

Acute caffeine supplementation offsets the impairment in 10-km running performance following one night of partial sleep deprivation: a randomized controlled crossover trial - Yi-Shan Tsai; Ting-Tzu Chen; Yau-Ching Chan; Chun-Chin Huang; Ting-Fu Lai; Yung Liao; Richard S. Metcalfe; Yung-Chih Chen; Ho-Seng Wang (European Journal of Applied Physiology, 2025)

Challenges and limitations of applying the flux variance similarity (FVS) method to partition evapotranspiration in a montane cloud forest - Ching-Hung Shih; Ray G. Anderson; Todd. H. Skaggs; Jehn-Yih Juang; Yi-Ying Chen; Yi-Shin Jang; Rong-Yu Gu; Cho-Ying Huang; Min-Hui Lo (Agricultural and Forest Meteorology, 2025)

Elucidating the Phase I metabolism of psilocin in vitro - Junqi Chen; Ziteng Wang; Ching Yee Yong; Evelyn Mei Ling Goh; Hooi Yan Moy; Eric Chun Yong Chan (Archives of Toxicology, 2025)

Correction: CCL4 contributes to aging related angiogenic insufficiency through activating oxidative stress and endothelial inflammation - Ting-Ting Chang; Liang-Yu Lin; Ching Chen; Jaw-Wen Chen (Angiogenesis, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Myriscagayanone C, a new compound from the fruit of myristica cagayanensis, inhibits fMLP-induced respiratory bursts by specifically preventing Akt translocation in human neutrophils - Hsiang-Ruei Liao; Chen-Lung Chen; Yu-Yao Kao; Fu-Chao Liu; Ching-Ping Tseng; Jih-Jung Chen (Chemico-Biological Interactions, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The difference in roaming behavior between owned and unowned dogs in a satoyama landscape area - Tsung-Han Kuo; Gau-Ming Chang; Pin-Huan Yu; Wei-Hsuan Chen; Shih-Ching Yen (Applied Animal Behaviour Science, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Characterizing immune responses of grey mullet (Mugil cephalus) to Nocardia seriolae ex vivo and in vivo - Ya-Ting Wang; Chien-Yueh Lee; Ching-Hung Chan; Liang-Chuan Lai; Mong-Hsun Tsai; Eric Y. Chuang; Li-Han Chen (Aquaculture International, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

A deeper look at switching intention to electric moped: Magnitude vs Uncertainty - Timo Eccarius; Ching-Fu Chen (Travel Behaviour and Society, 2025)

Tidal currents and atmospheric inorganic nitrogen contribute to diurnal variation of dissolved nutrients and chlorophyll a concentrations in Mirs Bay, Hong Kong - Ho Wen Lo; Xu Yu; Hanzhe Chen; Wai Ching Chu; Nga Man Chung; Sze Wing Lau; Jinjian Li; Shumin Liang; Kezheng Liao; Henry Charles James Thomas; Ziyan Wang; Zijing Zhang; et al. (Regional Studies in Marine Science, 2025)

Detecting infrastructure hazard potential change by SAR techniques on postseismic surface deformation: A case study of 2016 Meinong earthquake in southwestern Taiwan - Chih-Heng Lu; Ray C. Chuang; Ping-Chen Chiang; Jiun-Yee Yen; Kuo-En Ching; Yue-Gau Chen (Engineering Geology, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Enhancing cisplatin efficacy in hepatocellular carcinoma with selenocystine: The suppression of DNA repair and inhibition of proliferation in hepatoma cells - Pei-Yi Wu; Ulfah Hasanah; Sheng-Hua Yang; Sin-Yi Chen; Yueh-Hsia Luo; Chien-Chin Chen; Ssu-Ching Chen (Chemico-Biological Interactions, 2025)

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

Exploring the seasonal characteristics of the equatorial Atlantic SSTA: insights from an extended recharge-discharge oscillator framework - Zhenyu Cai; Han-Ching Chen; Wenchang Ge; Leishan Jiang (Climate Dynamics, 2025)

Challenging the Standard Immunogenicity Assessment Approach: 1-Tiered ADA Testing Strategy in Clinical Trials - Ching-Ha Lai; Mu Chen; Sasha Fraser; Jessica Wang; Sean McAfee; Emma Speaks; Nicholas Simeone; Jacqueline Rodriguez; Colin Stefan; Lisa DeStefano; Chinnasamy Elango; Matthew D. Andisik; et al. (The AAPS Journal, 2024)

Potato Protein Hydrolysate (PPH902) treatment in adipocytes inhibits lipogenesis by activating AMPK - Yi-Ju Chen; Ching-Fang Chang; Rathinasamy Baskaran; Chih-Hung Liang; Hsin-Ning Kuo; Mosleh Mohammad Abomughaid; Wan-Teng Lin (South African Journal of Botany, 2024)

High-fidelity CFD simulations of two tandemly arrayed wind turbines under various operating conditions - Maokun Ye; Hamn-Ching Chen; Arjen Koop (Ocean Engineering, 2024)

Hepatoprotective effect of MUFA-enriched refined Greenland halibut fin oil to inhibit hepatic fibrosis in carbon tetrachloride-induced mice - Pei-Pei Sun; Yi-Sheng Tseng; Chien-Chia Chen; Ching-Shu Lai; Cheng-Di Dong; Vishal Sharma; Mei-Ling Tsai (Food Bioscience, 2024)

The influence of exposure to inorganic arsenic and other arsenic species on early renal impairment among young adults in Taiwan - Wei-Shan Chin; Wei-Lun Hung; Yee-How Say; Ling-Chu Chien; Yang-Ching Chen; Yun-Peng Lo; Kai-Wei Liao (Environmental Pollution, 2024)

Analyzing Dehalochip: A functional DNA microarray for reductive dichlorination in chloroethene-contaminated sites - Che-Wei Lu; Chih-Ming Kao; Chao-Ling Yao; Ssu-Ching Chen (Environmental Pollution, 2024)

A review of metal nanomaterials-based electrochemical biosensors for environmental wastewater monitoring and their remediation - PratimaDevi Sivasubramanian; Mohanraj Kumar; Ching-Lung Chen; V.S. Kiran-kumar; Melvin S. Samuel; Jih-Hsing Chang (Environmental Nanotechnology, Monitoring & Management, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Sustainable production of graphene using biomass waste as a precursor: Environmental and economic implications - Santhanalakshmi Nagendran; Mohanraj Kumar; Natarajan Prakash; Ching-Lung Chen; Melvin S. Samuel; Ethiraj Selvarajan; Jih-Hsing Chang (Biocatalysis and Agricultural Biotechnology, 2024)

Targeting Fatty Acid Synthase to Halt Tumor Progression and Enhance Radiosensitivity in Breast Cancer Cells - Ching-I Chen; Hui-Wen Chan; Ching-Yi Shen; Hui-Yen Chuang (Journal of Medical and Biological Engineering, 2024)
Purpose Breast cancer, the most prevalent cancer among women, is closely linked to abnormal glucose and lipid metabolism, leading to radioresistance by upregulating survival-signaling pathways. Overexpression of fatty acid synthase (FASN), a key enzyme in lipogenesis, results in excessive lipid synthesis in breast cancer. This study evaluated whether FASN inhibition enhanced the radiosensitivity of breast cancer cells and inhibited their progression, potentially uncovering mechanisms for new therapeutic strategies. Methods MCF-7 breast cancer cells were treated with the FASN inhibitors orlistat and TVB-3166, and cytotoxicity was assessed using the MTT assay. Protein expression changes, migratory ability, and responses to radiotherapy were analyzed by the Western blotting, Transwell, and MTT assays, respectively. To confirm FASN dependence, MCF-7 cells were infected with shFASN lentivirus to verify the specificity of the observed effects to FASN inhibition. Results Both orlistat and TVB-3166 treatments induced significant cell death. Reduced FASN, HKII, pERK, and pAKT expression levels, along with an increased BAX/p-BCL2 ratio, indicate that FASN inhibition disrupted cell proliferation and promoted apoptosis by altering tumor metabolism. Furthermore, decreased MMP9 expression correlated with reduced cell migration after FASN inhibition. Importantly, FASN inhibition significantly and dose-dependently enhanced the radiosensitivity of MCF-7 cells. These findings were validated using shFASN lentivirus, confirming that the observed effects were FASN-dependent. Conclusion FASN inhibition limited survival and migration and enhanced radiosensitivity in MCF-7 cells. These findings indicate the potential efficacy of FASN inhibitors as standalone therapies or as adjuncts to radiotherapy for breast cancer.

The Association Among Urinary Di-(2-ethylhexyl) Phthalate Metabolites, Serum Lipid Profiles, and Serum Apoptotic Microparticles in a Young Taiwanese Population - Chien-Yu Lin; Sandy Huey-Jen Hsu; Ching-Way Chen; Chikang Wang; Fung-Chang Sung; Ta-Chen Su (Exposure and Health, 2024)

Effect of a tropical cyclone on the pelagic ecosystem of a continental shelf - Chung‐Chi Chen; Chih‐hao Hsieh; Yu‐Hsin Cheng; Wei‐Jen Huang; Wen‐Chen Chou; Fuh‐Kwo Shiah; Gwo‐Ching Gong; Tzong‐Yueh Chen (Limnology and Oceanography, 2024)
This study aimed to comprehend the effects of Typhoon Maria on the pelagic ecosystem in the southern East China Sea. Shipboard measurements were conducted at eight sampling stations before (2–4 d) and after (3–6 d) the typhoon, which enabled the evaluation of the potential impacts of the typhoon on this pelagic ecosystem, with particular focus on carbon dynamics. Following the typhoon's passage, there was a slight drop in sea surface temperature. The response of the variables to the typhoon, however, exhibited variations at different sampling stations. For further analysis, t ‐tests compared variables, while type II regression assessed the linear correlation between two variables. Overall, during the post‐typhoon period, concentrations of nitrate, chlorophyll a , primary production, bacterial biomass and production, plankton community respiration, and abundance of large phytoplankton (> 2 μ m) and the relative abundance of picophytoplankton among larger‐sized picoeukaryotes were higher compared to the pre‐typhoon period. The mean value of fugacity of CO 2 was similar to or slightly lower than pre‐typhoon period. Although the typhoon‐induced vigorous primary production might have absorbed a significant amount of CO 2 , the decrease in fugacity of CO 2 could have been offset by the plankton community respiration. The findings suggest that the typhoon enhanced physical disturbance and increased water column mixing, which, in turn, augmented nutrient availability and promoted plankton growth in the shallow water column. Overall, this study sheds light on the complex interactions between typhoons and marine ecosystems and highlights the importance of further investigating these phenomena to better understand their ecological implications.

Comprehensive evaluation of the nephrotoxicity of carbon quantum dots: Effects of the surface charge - Pei-Luen Jiang; Yan-Yu Hong; Lingyan Yang; Han-Jia Lin; Chih-Ching Huang; Yan-Hua Chen; Chia-Hua Lin; Yi-Chun Chen (Chemosphere, 2024)

Evaluating the embryotoxicity of benzophenone-based photoinitiators in stem cells and zebrafish embryos - Chen-Yi Weng; Tzu-Ching Chang; Jun-Yang Liou; Ju-Hsin Hsu; Chia-Chi Ho; Salim Arrokhman; Pinpin Lin (Toxicology, 2024)

Assessing the fate, toxicity, and ecological risk of mixtures of di(2-ethylhexyl)phthalate and di-n-butylphthalate using aquatic and terrestrial microcosms - Ching-Chang Lee; Wei-Ling Chen; Colin S. Chen; Chien-Jung Tien (Science of The Total Environment, 2024)

Numerical simulation of a semi-submersible FOWT platform under calibrated extreme and irregular waves - Haoyuan Gu; Hamn-Ching Chen (Ocean Engineering, 2024)

Development of modified MgO/biochar composite for chemical adsorption enhancement to cleanup fluoride-contaminated groundwater - Ying-Liang Yu; Chiann-Yi Chen; Chathura Dhanasinghe; Francis Verpoort; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Management, 2024)

Self-regenerative Ni/SiO2 for dry reforming of methane (DRM): 1000 h-longevity assessment and operando insights to coke removal under N2 atmosphere - Li-Wei Chen; Kim Hoong Ng; Liang-Ching Hsu (Chemical Engineering Journal, 2024)

Rational design of stable Cu and AuCu nanoparticles for investigations of size-enhanced SERS applications - Kuan-Wen Liu; Pei-Yu Sie; Jing-Yin Huang; Hsi-Ying Chen; Yi-Lun Chen; Yu-Ching Lin; Mei-Yi Liao (Analytica Chimica Acta, 2024)

Application of composite persulfate oxidation to remediate weathered lubricating oil-contaminated soils: Batch and pilot-scale studies - Wei-Ting Chen; Jiun-Hau Ou; Yih-Terng Sheu; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Chemical Engineering, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

High efficiency in blue TADF OLED using favorable horizontal oriented host - Yi-Zhen Li; Hsuan-Chi Liang; Chia-Hsun Chen; Ching-Huang Chiu; Lian-Chun Huang; Yi-Ting Lee; Yi-Chung Dzeng; Chi Chen; Bo-Yen Lin; Jiun-Haw Lee; Tien-Lung Chiu; Man-kit Leung (Chemical Engineering Journal, 2024)

Longitudinal Morphometric Changes in the Corticospinal Tract Shape After Hemorrhagic Stroke - Seth B. Boren; Sean I. Savitz; Nicole Gonzales; Khader Hasan; Andrea Becerril-Gaitan; Vahed Maroufy; Yuan Li; James Grotta; Emily A Steven; Ching-Jen Chen; Clark W. Sitton; Jaroslaw Aronowski; et al. (Translational Stroke Research, 2024)

Development of Quantitative Norms for Normal Lung Uptake Based on Three-Dimensional Gallium-67 Single Photon Emission Computed Tomography/Computed Tomography - Tzyy-Ling Chuang; Wei-Lin Li; Yu-Ching Hs; Jyh-Cheng Chen; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2024)
Purpose Gallium-67 (Ga-67) lung scans assess alveolitis and interstitial lung disease, with Ga-67 accumulation correlating with inflammation intensity as seen in lung biopsy sections. Both semi-quantitative and quantitative methods have been used, with the latter providing an inflammatory activity index linked to lung lavage and histopathological scores. However, differing reference points result in varying outcomes. This study aimed to establish standard Ga-67 index parameters using semi-quantitative analysis and a linear regression model based on planar and SPECT/CT images. Methods Twenty subjects without lung disease received a 5–6 mCi Ga-67 injection via the ankle. Both planar and SPECT/CT images were analyzed, with semi-quantitative values assessed using GraphPad Prism 9.5.1. Results Compared to planar images, SPECT/CT acquisitions for the lung-to-arm uptake ratio proved the most reliable indicator for assessing lung inflammation. Increased lung Ga-67 uptake was defined as greater than 2 standard deviations from the average Ga-67 uptake for healthy subjects. The normal range was 0.065 ± 0.049 for the right side and 0.076 ± 0.070 for the left side. Conclusion Lung-to-arm ratios in SPECT/CT images are more accurate than those in planar images. This method should be adopted as a standard clinical practice, providing more reliable diagnostic information and improving patient management. Future studies should compare patients without lung disease to those with lung disease to determine the diagnostic benefit of these norms.

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Correction: Potential Factors Associated with the Blood Metal Concentrations of Reproductive-Age Women in Taiwan - Tsung-Ho Ying; Chun-Jui Huang; Chia-Jung Hsieh; Pei-Ju Wu; Chang-Ching Yeh; Ping-Kun Hung; Wei-Hsiang Chang; Meng-Hsing Wu; Hsin Hung; Jung-Wei Chang; Chen-Tai Wang; Rachelle D. Arcega; et al. (Exposure and Health, 2024)

Recursive analytical solution for nonequilibrium multispecies transport of decaying contaminant simultaneously coupled in both the dissolved and sorbed phases - Yu-Chieh Ho; Heejun Suk; Ching-Ping Liang; Chen-Wuing Liu; Thu-Uyen Nguyen; Jui-Sheng Chen (Advances in Water Resources, 2024)

Distinct water mass between inside and outside eddy drive changes in prokaryotic growth and mortality in the tropical Pacific Ocean - Patrichka Wei-Yi Chen; Madeline Olivia; Gwo-Ching Gong; Sen Jan; Tung-Yuan Ho; Louis St. Laurent; An-Yi Tsai (Frontiers in Marine Science, 2024)
Throughout the western tropical Pacific Ocean, eddies and currents play an important role in biogeochemical cycling. Many studies have investigated the effects of hydrography on vertical patterns of picophytoplankton and heterotrophic bacterial abundance in mesoscale eddies. There is a lack of field observations to determine what impact dynamic hydrological systems of eddies have on prokaryotic community activity (growth and mortality rates). An objective of this study was to examine how anticyclonic eddies influence picoplankton abundance and activity (growth and mortality rates). To meet this purpose, heterotrophic bacterial and picophytoplankton growth and mortality rates were examined by modified dilution experiments conducted at the surface, deep chlorophyll maximum (DCM), and 200 m depth outside (OE) and inside of warm eddies core (EC) in the west Pacific Ocean. A high heterotrophic bacterial grazing rate was found in the EC region in the present study. Furthermore, the picophytoplankton grazing rate in EC was frequently greater than the grazing rate in OE. Furthermore, the higher grazing rates in the EC region cause a lower proportion of viral lysis to account for heterotrophic bacteria and picophytoplankton mortality. The results of our experiments suggest that downwelling in EC might increase picophytoplankton growth and grazing rates, increasing the carbon sink in the warm eddy and potentially increasing ocean carbon storage.

China's gray zone actions in the East China Sea, Taiwan Strait, and South China Sea: A comparative study and impact on fisheries - Wei-Chung Chen; Ching-Hsiewn Ou; Ming-Hao Yang; Yi-Che Shih (Marine Policy, 2024)

Revisiting the synergistic oxidation of peracetic acid and permanganate(Ⅶ) towards micropollutants: The enhanced electron transfer mechanism of reactive manganese species - Yufei Shi; Shaoze Xiao; Yajie Qian; Ching-Hua Huang; Jiabin Chen; Nan Li; Tongcai Liu; Yalei Zhang; Xuefei Zhou (Water Research, 2024)

Mapping local climate zones and its applications at the global scale: A systematic review of the last decade of progress and trend - Renfeng Wang; Mengmeng Wang; Chao Ren; Guangzhao Chen; Gerald Mills; Jason Ching (Urban Climate, 2024)

Study on the performance of highly doped copper tailings sand for concrete pavements using specific grading techniques - Sung-Ching Chen; Meng-Yao Gao; Wei-Ting Lin; Le-Ping Liu; Kinga Korniejenko (Minerals Engineering, 2024)

Classification of aged batteries based on capacity and/or resistance through machine learning models with aging features as input: A comparative study - Yi-Cheng Wang; Kuo-Ching Chen (Journal of Cleaner Production, 2024)

Modelling the distribution of fish habitat type and habitat diversity in natural rivers - Hsuan-Ju Hung; Wei-Cheng Lo; Ching-Nuo Chen; Chih-Heng Tsai (Journal for Nature Conservation, 2024)

Bioinspired multiscale hierarchical structure enables solar-thermal conversion for low-temperature aqueous electrochromic device - Qi Zhao; Xue Chen; Qiming Zhu; Chin Ho Kirk; Jianguo Sun; Li Wang; Shuai Guo; Swee Ching Tan; Yanfeng Gao; John Wang (Chemical Engineering Journal, 2024)

Cardenolide glycosides sensitize gefitinib-induced apoptosis in non-small cell lung cancer: inhibition of Na+/K+-ATPase serving as a switch-on mechanism - Chi-Min Du; Wohn-Jenn Leu; Yi-Huei Jiang; She-Hung Chan; Ih-Sheng Chen; Hsun-Shuo Chang; Lih-Ching Hsu; Jui-Ling Hsu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Taxonomic notes on Mucuna (Fabaceae: Papilionoideae) of Taiwan - Po-Hao Chen; An-Ching Chung; Chih-Chiang Wang; Sheng-Zehn Yang; Chien-Ti Chao (Kew Bulletin, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Nutrient sources, phytoplankton blooms, and hypoxia along the Chinese coast in the East China Sea: Insight from summer 2014 - Chung-Chi Chen; Wen-Chen Chou; Chin-Chang Hung; Gwo-Ching Gong (Marine Pollution Bulletin, 2024)

Surface engineering of the lightweight aggregates derived from the dredged harbor sediment for green fertilizer utilization - TsingHai Wang; ZiYing Lu; ChiaYu You; Wei-Fan Kuan; Ching-Lung Chen; Yee Cheng Lim; Chiu-Wen Chen; Cheng-Di Dong (Process Safety and Environmental Protection, 2024)

Energy transition: Cap-and-trade and carbon capture and storage for achieving net-zero emissions with sustainable insurance - Shi Chen; Yuqi Li; Jyh-Horng Lin; Ching-Hui Chang (Journal of Environmental Management, 2024)

Ammonia recovery via direct contact membrane distillation: Modeling and performance optimization - Yuan Hu; Ching Yoong Loh; Ming Xie; Gang Chen; Manhong Huang; Jinli Qiao (Journal of Environmental Management, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

Surface ligand engineering of perovskite quantum dots for n-type and stretchable photosynaptic transistor with an ultralow energy consumption - Wei-Cheng Chen; Yan-Cheng Lin; Zih-Syuan Syu; Ya-Shuan Wu; Kai-Wei Lin; Cheng-Liang Liu; Chi-Ching Kuo; Wen-Chang Chen (Chemical Engineering Journal, 2024)

Enhancing dye degradation in darkness: The role of SnO2 nanorod clusters in flexocatalysis - Nai-Jen Chang; Yu-Ching Chen; Sz-Nian Lai; Jyh Ming Wu (Chemical Engineering Journal, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Development of a high-throughput kinase activity platform using nanoLC-MS/MS with DIA approach for studying the anti-cancer mechanism of Taxol in ovarian cancer - Chia-Hsin Lee; Yu-Ching Liu; Chao-Jung Chen (Analytica Chimica Acta, 2024)

CCL4 contributes to aging related angiogenic insufficiency through activating oxidative stress and endothelial inflammation - Ting-Ting Chang; Liang-Yu Lin; Ching Chen; Jaw-Wen Chen (Angiogenesis, 2024)
Aging is a natural process associated with chronic inflammation in the development of vascular dysfunction. We hypothesized that chemokine C-C motif ligands 4 (CCL4) might play a vital role in aging-related vascular dysfunction. Circulating CCL4 was up-regulated in elderly subjects and in aged animals. CCL4 inhibition reduced generation of reactive oxygen species (ROS), attenuated inflammation, and restored cell functions in endothelial progenitor cells from elderly subjects and in aged human aortic endothelial cells. CCL4 promoted cell aging, with impaired cell functioning, by activating ROS production and inflammation. CCL4 knockout mice and therapeutic administration of anti-CCL4 neutralizing antibodies exhibited vascular and dermal anti-aging effects, with improved wound healing, via the down-regulation of inflammatory proteins and the activation of angiogenic proteins. Altogether, our findings suggested that CCL4 may contribute to aging-related vascular dysfunction via activating oxidative stress and endothelial inflammation. CCL4 may be a potential therapeutic target for vascular protections during aging.

Experimental observation of exceptional bound states in a classical circuit network - Deyuan Zou; Tian Chen; Haiyu Meng; Yee Sin Ang; Xiangdong Zhang; Ching Hua Lee (Science Bulletin, 2024)

Upcycling of waste polycarbonate to recyclable Poly(carbonate-imines) with exceptional thermal properties and unprecedented flame retardancy - Yi-Chun Chen; Pin-Qi Mu; Kamani Sudhir K. Reddy; Ru-Jong Jeng; Mahdi M. Abu-Omar; Ching-Hsuan Lin (Chemical Engineering Journal, 2024)

Carbon-in-carbon: Hybrid carbonized nanomaterials with multifunctional activities for the treatment of endophthalmitis - Hong-Jyuan Jian; Yi-Ru Chiou; Anisha Anand; Chien-Fu Chen; David Hui-Kang Ma; Jui-Yang Lai; Chih-Ching Huang; Huan-Tsung Chang (Chemical Engineering Journal, 2024)

Efficiency of PGK1 proteins delivered to the brain via a liposomal system through intranasal route administration for the treatment of spinocerebellar ataxia type 3 - Yu-Shuan Chen; Zhen-Xiang Hong; Yi-Tung Lin; En-CI Tsao; Pei-Yu Chen; Ching-Ann Liu; Horng-Jyh Harn; Tzyy-Wen Chiou; Shinn-Zong Lin (Drug Delivery and Translational Research, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Risk Analysis of Pirate Attacks on Southeast Asian Ships Based on Bayesian Networks - Qiong Chen; Jinsheng Zhang; Jiaqi Gao; Yui-Yip Lau; Jieming Liu; Mark Ching-Pong Poo; Pengfei Zhang (Journal of Marine Science and Engineering, 2024)
As a bridge for international trade, maritime transportation security is crucial to the global economy. Southeast Asian waters have become a high-incidence area of global piracy attacks due to geographic location and complex security situations, posing a great threat to the development of the Maritime Silk Road. In this study, the factors affecting the risk of pirate attacks are analyzed in depth by using the Global Ship Piracy Attacks Report from the IMO Global Integrated Shipping Information System (GISIS) database (i.e., 2013–2022) in conjunction with a Bayesian Network (BN) model, and the Expectation Maximization algorithm is used to train the model parameters. The results show that piracy behaviors and the ship’s risk are the key factors affecting the risk of pirate attacks, and suggestions are made to reduce the risk of pirate attacks. This study develops a theoretical basis for preventing and controlling the risk of pirate attacks on ships, which helps maintain the safety of ship operations.

Cross-frequency modulation of postural fluctuations and scalp EEG in older adults: error amplification feedback for rapid balance adjustments - Yi-Ching Chen; Yi-Ying Tsai; Wei-Min Huang; Chen-Guang Zhao; Ing-Shiou Hwang (GeroScience, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Enhancing methane formation in carbon dioxide hydrogenation on nickel clusters with zirconium additives: Exploring active sites, reaction pathways, and catalytic mechanisms - Ching-Shiun Chen; Tse-Ching Chen; Jia Huang Wu; Hung-Chi Wu; Chia-Min Yang; Tsung-Cheng Yang; Chih-Wen Pao (Chemical Engineering Journal, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Age and dietary restriction modulate mitochondrial quality in quadriceps femoris muscle of male mice - Ting-Rui Zhang; Chun-Hsien Chiang; Tzu-Chieh Hsu; Chih-Yun Wang; Ching-Yi Chen (Biogerontology, 2024)

Multiscale Variability of Autumn Precipitation in Eastern Taiwan Modulated by ENSO, ISO, and TC Activity - Ching-Hsuan Wu; Wei-Ting Chen; Chien-Ming Wu (Asia-Pacific Journal of Atmospheric Sciences, 2024)

The effects of Elgucare in a rat model of intervertebral disc degeneration - Ting-Kuo Chang; Yueh-Ching Liu; Tzu-Yun Chien; Yu-Ting Chen; Ching-Chen Chen (Advances in Traditional Medicine, 2024)
As an avascular tissue, the intervertebral disc (IVD) faces difficulties in obtaining nutrients and is prone to accumulating metabolic waste. The ensuing IVD degeneration (IVDD) causes symptoms such as low back pain. Traditional Chinese medicine has a millennia-long history of treating IVDD, with the advantages of safety and few adverse effects. Based on prior pharmacological research, the Chinese herbal formula Elgucare is abundant in the nutrients required by the IVD and can improve blood circulation, accelerating the removal of metabolic waste from the IVD. This study used a 23 G needle to surgically induce IVDD in a rat model. Thirty rats were randomly assigned to five groups: one that underwent sham surgery (Sham), one with IVDD that was not fed Elgucare (EGC-0), and three with IVDD that were fed Elgucare at different concentrations for six weeks (EGC-L, EGC-M, and EGC-H). Study parameters, including total body weight, plantar sensitivity to pain, gait analysis, IVD thickness, and IVD morphology, were used to assess the effects of Elgucare on IVDs. Our results showed that administering Elgucare to rats effectively reduced plantar tingling and improved swing speed during gait analysis. Elgucare also accelerated increases in IVD thickness and increased the proportion of IVD that returned to normal cellularity. The possible benefits of Elgucare include alleviating pain, improving mobility, and accelerating IVD repair, indicating its potential for use in IVD therapy.

Protective Effects of Roselle Aqueous Extracts against UV-Induced Damage in Zebrafish Fins - I-Ting Lee; Ching-Yuan Huang; Wei-Lin Su; Tran M. Truong; Chi-Chung Wen; Bo-Chang Wang; Yau-Hung Chen (Fishes, 2024)
(1) Background: Roselle (Hibiscus sabdariffa) is a flowering plant reported to have anti-obesity, antioxidant, antibacterial, and anti-inflammatory effects. This study aims to evaluate the UV-absorbing and antioxidant activities of roselle aqueous extracts (RAE) and test the protective effects of RAE against UV radiation in zebrafish embryos. (2) Methods: DPPH assay and UV-spectrum methods were applied to evaluate the antioxidant and UV-absorbing activities, respectively. The protective effects of RAE were evaluated using fin morphology recording, Kaplan–Meier analysis, and Cox proportional hazards regression. Real-time PCR experiments were also applied to detect both the UV- and RAE-induced gene expressions. (3) Results: Our results show that (i) RAE had UV-absorbing abilities and significantly reduced ROS production in vitro; (ii) the mean times of malformed fins in the UV + RAE (36 and 48 ppm) groups were 3.56 and 4.44 days, respectively, and were prolonged compared to those in the UV-only group (3.36 days); (iii) zebrafish in the UV + RAE (36 and 48 ppm) groups were 0.963 and 0.496 (p

Maritime transport resilience: A systematic literature review on the current state of the art, research agenda and future research directions - Yui-yip Lau; Qiong Chen; Mark Ching-Pong Poo; Adolf K.Y. Ng; Chung Chui Ying (Ocean & Coastal Management, 2024)

Green production planning for circular supply chain and resource management: An empirical study for high-tech textile dyeing - Chen-Fu Chien; Ping-Chen Kuo; Pei-Ching Sun; Hsuan-An Kuo (Resources, Conservation and Recycling, 2024)

Comparative study of wave height transformation: Bragg reflection versus wave breaking at submerged rectangular breakwaters - Ching-Piao Tsai; Chun-Han Ko; Han-Chen Shih; Yueh-Heng Chen; Ying-Chi Chen (Ocean Engineering, 2024)

Bioremediation of trichloroethylene-contaminated groundwater using green carbon-releasing substrate with pH control capability - Hsin-Chia Lee; Ssu-Ching Chen; Yih-Terng Sheu; Chao-Ling Yao; Kai-Hung Lo; Chih-Ming Kao (Environmental Pollution, 2024)

Effects of occupational exposure to metal fume PM2.5 on lung function and biomarkers among shipyard workers: a 3-year prospective cohort study - Huan Minh Tran; Ching-Huang Lai; Wei-Liang Chen; Chung Ching Wang; Che-Wei Liang; Chi-Yu Chien; Chih-Hong Pan; Kai-Jen Chuang; Hsiao-Chi Chuang (International Archives of Occupational and Environmental Health, 2024)
Objective This study investigates the associations of α1-antitrypsin, inter-α-trypsin inhibitor heavy chain (ITIH4), and 8-isoprostane with lung function in shipyard workers exposed to occupational metal fume fine particulate matter (PM 2.5 ), which is known to be associated with adverse respiratory outcomes. Methods A 3-year follow-up study was conducted on 180 shipyard workers with 262 measurements. Personal exposure to welding fume PM 2.5 was collected for an 8-h working day. Pre-exposure, post-exposure, and delta (∆) levels of α1-antitrypsin, ITIH4, and 8-isoprostane were determined in urine using enzyme-linked immunosorbent assays. Post-exposure urinary metals were sampled at the beginning of the next working day and analyzed by inductively coupled plasma-mass spectrometry. Lung function measurements were also conducted the next working day for post-exposure. Results An IQR increase in PM 2.5 was associated with decreases of 2.157% in FEV 1 , 2.806% in PEF, 4.328% in FEF 25% , 5.047% in FEF 50% , and 7.205% in FEF 75% . An IQR increase in PM 2.5 led to increases of 42.155 µg/g in ∆α1-antitrypsin and 16.273 µg/g in ∆ITIH4. Notably, IQR increases in various urinary metals were associated with increases in specific biomarkers, such as post-urinary α1-antitrypsin and ITIH4. Moreover, increases in ∆ α1-antitrypsin and ∆ITIH4 were associated with decreases in FEV 1 /FVC by 0.008% and 0.020%, respectively, and an increase in ∆8-isoprostane resulted in a 1.538% decline in FVC. Conclusion Our study suggests that urinary α1-antitrypsin and ITIH4 could indicate early lung function decline in shipyard workers exposed to metal fume PM 2.5 , underscoring the need for better safety and health monitoring to reduce respiratory risks. Graphical abstract

Quantifying payloads of antibody‒drug conjugates using a postcolumn infused-internal standard strategy with LC‒MS - Chih-Ning Cheng; Hsiao-Wei Liao; Ching-Hung Lin; Wen-Chi Chang; I-Chun Chen; Yen-Shen Lu; Ching-Hua Kuo (Analytica Chimica Acta, 2024)

An innovative permeable reactive bio-barrier to remediate trichloroethene-contaminated groundwater: A field study - Che-Wei Lu; Kai-Hung Lo; Sun-Chong Wang; Chih-Ming Kao; Ssu-Ching Chen (Science of The Total Environment, 2024)

Quantification of numerical uncertainties of CFD-predicted wind turbine performance with overset grids - Maokun Ye; Yan Zhao; Hamn-Ching Chen; Decheng Wan (Ocean Engineering, 2024)

The angiogenesis-modulating effects of coumarin-derivatives - Han-Ting Huang; Ching-Yuan Huang; Chih-Jou Lee; Bo-Jie Sun; Zong-Wei Jhang; Chi-Chung Wen; Yun-Hsin Wang; Tao-Sheng Li; Ching-Yuh Chern; Yau-Hung Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Correction: Potential Factors Associated with the Blood Metal Concentrations of Reproductive-Age Women in Taiwan - Tsung-Ho Ying; Chun-Jui Huang; Chia-Jung Hsieh; Pei-Ju Wu; Chang-Ching Yeh; Ping-Kun Hung; Wei-Hsiang Chang; Meng-Hsing Wu; Hsin Hung; Jung-Wei Chang; Chen-Tai Wang; Rachelle D. Arcega; et al. (Exposure and Health, 2024)

The Association of Bisphenol A and Parabens Exposure and Oxidative Stress in Attention-Deficit/Hyperactivity Disorder in Children and Adolescents - Boopathi Subramani; Chia-Huang Chang; Ting-Yu Fang; Ching-Jung Yu; Jung-Chieh Du; Hsien-Chih Chiou; Jia-Woei Hou; Winnie Yang; Hsin-Chang Chen; Ying-Sheue Chen; Betau Hwang; Mei-Lien Chen (Exposure and Health, 2024)

Determination of the Elemental Iodine in Human Breast Milk by Inductively Coupled Plasma mass Spectrometry - Chun-Jui Huang; Jia-Zhen Li; Chii-Min Hwu; Harn-Shen Chen; Chang-Ching Yeh; Fan-Fen Wang; Chen-Chang Yang (Biological Trace Element Research, 2024)

Bringing traits back into the equation: A roadmap to understand species redistribution - Lise Comte; Romain Bertrand; Sarah Diamond; Lesley T. Lancaster; Malin L. Pinsky; Brett R. Scheffers; J. Alex Baecher; R. M. W. J. Bandara; I‐Ching Chen; Jake A. Lawlor; Nikki A. Moore; Brunno F. Oliveira; et al. (Global Change Biology, 2024)
Ecological and evolutionary theories have proposed that species traits should be important in mediating species responses to contemporary climate change; yet, empirical evidence has so far provided mixed evidence for the role of behavioral, life history, or ecological characteristics in facilitating or hindering species range shifts. As such, the utility of trait‐based approaches to predict species redistribution under climate change has been called into question. We develop the perspective, supported by evidence, that trait variation, if used carefully can have high potential utility, but that past analyses have in many cases failed to identify an explanatory value for traits by not fully embracing the complexity of species range shifts. First, we discuss the relevant theory linking species traits to range shift processes at the leading (expansion) and trailing (contraction) edges of species distributions and highlight the need to clarify the mechanistic basis of trait‐based approaches. Second, we provide a brief overview of range shift–trait studies and identify new opportunities for trait integration that consider range‐specific processes and intraspecific variability. Third, we explore the circumstances under which environmental and biotic context dependencies are likely to affect our ability to identify the contribution of species traits to range shift processes. Finally, we propose that revealing the role of traits in shaping species redistribution may likely require accounting for methodological variation arising from the range shift estimation process as well as addressing existing functional, geographical, and phylogenetic biases. We provide a series of considerations for more effectively integrating traits as well as extrinsic and methodological factors into species redistribution research. Together, these analytical approaches promise stronger mechanistic and predictive understanding that can help society mitigate and adapt to the effects of climate change on biodiversity.

Corrigendum to “Electrochemical nitrate reduction over bimetallic Pd–Sn nanocatalysts with tunable selectivity toward benign nitrogen” [350 (2024) 141182] - Jenn Fang Su; Muhammad Sheraz Ahmad; Wei-Fan Kuan; Ching-Lung Chen; Tahir Rasheed (Chemosphere, 2024)

Vertical variations of bacterial growth, mortality loss to nanoflagellates, and viruses in the subtropical northwestern Pacific Ocean - Feng-Hsun Chang; Gwo-Ching Gong; Chih-hao Hsieh; Patrichka Wei-Yi Chen; Vladimir Mukhanov; An-Yi Tsai (Journal of Marine Systems, 2024)

A practical lateral spreading pressure model for piles in inclined liquefied ground - Jiunn-Shyang Chiou; Ching-Lin Chen; Jing Ling Ng; Yuan-Man Hsu (Engineering Structures, 2024)

Photo-protection and photo-inhibition during light induction in Barbula indica and Conocephalum conicum under different light gradients - Chung-I. Chen; Kuan-Hung Lin; Meng-Yuan Huang; Kuei-Yu Yao; Chau-Ching Huang; Tzu-Chao Lin; En-Liang Chu; Jia-Dong Yang; Ching-Wen Wang (Photosynthesis Research, 2024)

Mapping land-use and land-cover changes through the integration of satellite and airborne remote sensing data - Meng-Hsuan Lin; Ying-Tong Lin; Min-Lin Tsai; Yi-Ying Chen; Yi-Chun Chen; Hsueh-Ching Wang; Chi-Kuei Wang (Environmental Monitoring and Assessment, 2024)

Different microbial communities in paddy soils under organic and nonorganic farming - Jimmy Kuo; Daniel Liu; Wei Hao Wen; Ching Yuan Chiu; Wanyu Chen; Yun Wen Wu; Fang-Ting Lai; Chorng-Horng Lin (Brazilian Journal of Microbiology, 2024)

Probing the hair detectability of prohibited substances in sports: an in vivo-in silico-clinical approach and analytical implications compared with plasma, urine, and faeces - Shao-Hsin Hung; Hung-Lin Kan; Chun-Wei Tung; Yi-Ching Lin; Ting-Ting Chen; Ciao Tian; William Chih-Wei Chang (Archives of Toxicology, 2024)
Hair analysis is a crucial method in forensic toxicology with potential applications in revealing doping histories in sports. Despite its widespread use, knowledge about detectable substances in hair is limited. This study systematically assessed the detectability of prohibited substances in sports using a multifaceted approach. Initially, an animal model received a subset of 17 model drugs to compare dose dependencies and detection windows across different matrices. Subsequently, hair incorporation data from the animal experiment were extrapolated to all substances on the World Anti-Doping Agency’s List through in-silico prediction. The detectability of substances in hair was further validated in a proof-of-concept human study involving the consumption of diuretics and masking agents. Semi-quantitative analysis of substances in specimens was performed using ultra-performance liquid chromatography–tandem mass spectrometry. Results showed plasma had optimal dose dependencies with limited detection windows, while urine, faeces, and hair exhibited a reasonable relationship with the administered dose. Notably, hair displayed the highest detection probability (14 out of 17) for compounds, including anabolic agents, hormones, and diuretics, with beta-2 agonists undetected. Diuretics such as furosemide, canrenone, and hydrochlorothiazide showed the highest hair incorporation. Authentic human hair confirmed diuretic detectability, and their use duration was determined via segmental analysis. Noteworthy is the first-time reporting of canrenone in human hair. Anabolic agents were expected in hair, whereas undetectable compounds, such as peptide hormones and beta-2 agonists, were likely due to large molecular mass or high polarity. This study enhances understanding of hair analysis in doping investigations, providing insights into substance detectability.

Electrochemical nitrate reduction over bimetallic Pd–Sn nanocatalysts with tunable selectivity toward benign nitrogen - Jenn Fang Su; Muhammad Sheraz Ahmad; Wei-Fan Kuan; Ching-Lung Chen; Tahir Rasheed (Chemosphere, 2024)

Fluorinated photoreduced graphene oxide with semi-ionic C–F bonds: An effective carbon based photocatalyst for the removal of volatile organic compounds - Xin Hong Tai; Wei-Song Hung; Thomas Chung Kuang Yang; Chin Wei Lai; Kian Mun Lee; Chia-Yun Chen; Joon Ching Juan (Chemosphere, 2024)

Isolation and characterization of the novel phage BP14 for lysing Vibrio parahaemolyticus and reducing virulence proteins - Te-Ken Hsu; Hui-Yu Shih; Hui-Ju Huang; Jeff Chia-Kai Hsu; Han-Ching Wang; Yi-Yin Chen; Li-Li Chen (Aquaculture, 2024)

Exploring the multifaceted impact of lanthanides on physiological pathways in human breast cancer cells - Yi-Ming Huang; Tsu-Yu Hsu; Ching-Yu Liu; Yu-Chen Hsieh; Kuan-Yun Lai; Ya-Wen Yang; Kai-Yin Lo (Toxicology, 2024)

Separation and enrichment of tricolor phosphors in waste phosphors through liquid–liquid–powder extraction method and its benefit evaluation for recovery - Li Pang Wang; Jun Ming Hou; Yan Jhang Chen; Bu Ching Tseng; Sandhya Babel (Minerals Engineering, 2024)

Exposure estimates of PM2.5 using the land-use regression with machine learning and microenvironmental exposure models for elders: Validation and comparison - Chin-Yu Hsu; Wei-Ting Hsu; Ching-Yi Mou; Pei-Yi Wong; Chih-Da Wu; Yu-Cheng Chen (Atmospheric Environment, 2024)

Potential Factors Associated with the Blood Metal Concentrations of Reproductive-Age Women in Taiwan - Tsung-Ho Ying; Chun-Jui Huang; Chia-Jung Hsieh; Pei-Ju Wu; Chang-Ching Yeh; Ping-Kun Hung; Wei-Hsiang Chang; Meng-Hsing Wu; Hsin Hung; Jung-Wei Chang; Chen-Tai Wang; Rachelle D. Arcega; et al. (Exposure and Health, 2024)
Exposure of reproductive-age women to toxic trace elements warrants attention because of their negative effects. This study aimed to investigate the levels of arsenic (As), cadmium (Cd), mercury (Hg), chromium (Cr), and lead (Pb) in the blood of 837 Taiwanese childbearing-age women and establish the correlation between their dietary pattern and heavy metal concentration. The concentrations of Cd and Pb were significantly higher in nonpregnant women than in pregnant women (Cd: 2.41 µg/L vs. 2.12 µg/L; Pb: 0.83 µg/dL vs. 0.73 µg/dL), whereas the concentration of Cr was significantly lower in nonpregnant women than in pregnant women (Cr: 0.98 µg/L vs. 1.05 µg/L). Otherwise, no significant differences in As (9.02 µg/L vs. 9.51 µg/L) and Hg (3.71 µg/L vs. 3.79 µg/L) were found between the nonpregnant and pregnant women. Overall, the blood metal concentrations of Cd and Hg showed a decreasing trend in the different pregnancy stages. The levels of As and Hg were highly correlated with seafood intake. Finally, lifestyle habits, such as burning incense usage and Chinese herb intake may contribute to metal accumulation in maternal or reproductive-age women. Preventive risk communication and educational strategies should be applied to these subgroups in view of food safety and public health concern. Graphical Abstract

Emergence of OXA-48-producing hypervirulent Klebsiella pneumoniae strains in Taiwan - Yi-Tsung Lin; Chien Chuang; Sheng-Hua Chou; Chih-Han Juan; Tsuey-Ching Yang; Barry N. Kreiswirth; Liang Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Effect of stress on the rehabilitation performance of rats with repetitive mild fluid percussion-induced traumatic brain injuries - Yu-Lin Wang; Chi-Chun Chen; Ching-Ping Chang (Cognitive Neurodynamics, 2024)

Semi-analytical models for two-dimensional multispecies transport of sequentially degradation products influenced by rate-limited sorption subject to arbitrary time-dependent inlet boundary conditions - Thu-Uyen Nguyen; Yu-Chieh Ho; Heejun Suk; Ching-Ping Liang; Zhong-Yi Liao; Jui-Sheng Chen (Advances in Water Resources, 2024)

Green cost performance measure of China’s thermal power industry: evidence from Chinese 30 provinces - Xiang Chen; Jiayu Zhang; Chih-Yu Yang; Ching-Cheng Lu; Jun Wang (Environment, Development and Sustainability, 2024)

Consumption of the nonnutritive sweetener acesulfame potassium increases central precocious puberty risk - Hung-Tsung Wu; Chi-Chen Chiang; Chung-Teng Wang; Yue-Hwa Chen; Shih-Yuan Hsu; Yang-Ching Chen (Journal of Hazardous Materials, 2024)

Structure-specific metabolism of flavonol molecules by Bacillus subtilis var. natto BCRC 80517 - Che-Wei Wang; Hsin-Ya Tsai; Chen Hsu; Ching-Chun Hsieh; I-Shu Wang; Chi-Fon Chang; Nan-Wei Su (Food Chemistry, 2024)

Property rights arrangement and stakeholder networks hindering floating photovoltaics: A case of private open-access ponds in Taiwan - Yi-Chieh Chen; Kenneth Bicol Dy; Ching-Cheng Chang; Shih-Hsun Hsu (Energy Policy, 2024)

A longitudinal study on the change in sleep across three waves of the COVID-19 outbreaks in Hong Kong - Denise Shuk Ting Cheung; Branda Yee-Man Yu; Simon Ching Lam; Doris Yin Ping Leung; Ka-Fai Chung; Fiona Yan-Yee Ho; Shu-Cheng Chen; Wing-Fai Yeung (Sleep and Biological Rhythms, 2024)

Screen for low-arsenic-risk rice varieties based on environment–genotype interactions by using GGE analysis - Kai-Wei Juang; Ting Tsai; Chien-Hui Syu; Bo-Ching Chen (Environmental Geochemistry and Health, 2024)

Deciphering microbial communities and their unique metabolic repertoire across rock-soil–plant continuum in the Dayoukeng fumarolic geothermal field of the Tatun Volcano Group - Jung-Sheng Chen; Bashir Hussain; Hsin-Chi Tsai; Viji Nagarajan; Rajendran Senthil Kumar; I-Ching Lin; Bing-Mu Hsu (Environmental Science and Pollution Research, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Highly efficient Bi2O2CO3 coupled with interlayer expanded MoS2 photocatalyst with oxygen vacancy mediated direct Z-scheme charge transfer for photocatalytic degradation of organic pollutant - Magdeline Tze Leng Lai; Thomas Chung Kuang Yang; Chin Wei Lai; Chia-Yun Chen; Mohd Rafie Johan; Kian Mun Lee; Joon Ching Juan (Journal of Environmental Chemical Engineering, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Membrane distillation of a waste stream from neodymium‑iron‑boron scrap recovery: Performance and scaling mitigation - Yuan Hu; Ludovic F. Dumée; Ming Xie; Ching Yoong Loh; Gang Chen; Manhong Huang; Jinli Qiao (Desalination, 2023)

Effect of sodium promoters on Ni/Al2O3 catalyst for CO2 hydrogenation: The carbon fixation as carbon nanofiber and reverse-water gas reactions - Ching-Shiun Chen; Tse-Ching Chen; Hung-Chi Wu; Jia-Huang Wu; Chih-Wen Pao (Chemical Engineering Journal, 2023)

Machine learning-based monosaccharide profiling for tissue-specific classification of Wolfiporia extensa samples - Shih-Yi Hsiung; Shun-Xin Deng; Jing Li; Sheng-Yao Huang; Chen-Kun Liaw; Su-Yun Huang; Ching-Chiung Wang; Yves S.Y. Hsieh (Carbohydrate Polymers, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Generation of artificial rainfall events for flood risk assessment in Taiwan - Wen-Ko Hsu; Pei-Chiung Huang; Ching-Cheng Chang; Wei-Ling Chiang; Dung-Jiang Chiou; Cheng-Wu Chen (Natural Hazards, 2023)

Interdecadal variability of meridional tropical cyclone genesis over the western North Pacific and associated modulating processes - Jien‐Yi Tu; Jau‐Ming Chen; Pei‐Hua Tan; Mei‐Yuan Tsai; Tzu‐Ling Lai; Ching‐Huang Chen (International Journal of Climatology, 2023)
During the period 1970–2020, evident interdecadal variability of meridional tropical cyclone (TC) genesis occurs in the western North Pacific (WNP) from September through October (SO). From the periods 1970–1996 (IP1) to 1998–2020 (IP2), TC genesis during SO is enhanced (suppressed) in the region north (south) of 20°N. The large‐scale modulating processes feature a general warming of sea surface temperature (SST) over the WNP and systematic northward displacement in atmospheric circulations. The northward‐shifted Pacific subtropical high and monsoon trough result in an anomalous anticyclone across the subtropical region and an anomalous cyclone across the South China Sea and the northern WNP east of Taiwan. This anomalous cyclone facilitates TC genesis to increase in the northern WNP. Meanwhile, the southeastward‐extending monsoon trough retreats northwestward, leading to an anomalous anticyclone over the tropical eastern WNP and a decrease in TC genesis over the southern region. Correlation analyses indicate that the Pacific Decadal Oscillation (PDO) is more effective than global warming in modulating interdecadal increases of TC genesis in the northern region due to inclusions of both trend and oscillation features. Interdecadal decreases of TC genesis in the southern region exhibit a major oscillation feature and are thus mainly affected by interdecadal oscillation components of PDO. More TCs forming in the oceans east of Taiwan are steered by the overlying anomalous cyclone to recurve northward toward oceans to the northeast and north of Taiwan. TC‐induced rainfall over Taiwan thus increases by 25% from IP1 to IP2, which accounts for about 82% of increased total rainfall in Taiwan, showing the notable impact of interdecadal TC genesis on local climate in the WNP.

Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei) - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2023)

Real-time hybrid simulation for seismic control performance evaluation of an active inerter damper system - Pei-Ching Chen; Po-Chang Chen (Engineering Structures, 2023)

Tandem surface engineering of graphene quantum dot-assisted fluorinated NiFe Prussian blue analogue for electrocatalytic oxygen evolution reaction - Angelina Melanita Tarigan; Sofiannisa Aulia; Mia Rinawati; Ling-Yu Chang; Yao-Sheng Cheng; Ching-Cheng Chang; Wei-Hsiang Huang; Jeng-Lung Chen; Heru Setyawan; Min-Hsin Yeh (Chemical Engineering Journal, 2023)

Pinostrobin modulates FOXO3 expression, nuclear localization, and exerts antileukemic effects in AML cells and zebrafish xenografts - Pei-Yi Chen; Ching-Yen Lin; Chia-Ling Wu; Pei Ying Keak; Je-Wen Liou; Wan-Yun Gao; Liang-In Lin; Jui-Hung Yen (Chemico-Biological Interactions, 2023)

Uncovering molecular mechanisms involved in microbial volatile compounds-induced stomatal closure in Arabidopsis thaliana - Tu-Trinh Thi Truong; Chi-Chou Chiu; Jing-Yu Chen; Pei-Yu Su; Tri-Phuong Nguyen; Ngoc-Nam Trinh; Tetsuro Mimura; Ruey-Hua Lee; Ching-Han Chang; Hao-Jen Huang (Plant Molecular Biology, 2023)

Interaction between driftwood deposition patterns and debris flow fan development - Yen-Yu Chiu; Jia-Yen Wu; Hung-En Chen; Ching-Ying Tsou; Su-Chin Chen (Landslides, 2023)

First principal observation documenting the three-dimensional uptake of cadmium and spatial distribution of cadmium hydroxyapatite mineral in bone char - Partha Pratim Biswas; Jagat Rathod; Ching-Yu Chiang; Biqing Liang; Chun-Chieh Wang; Yao-Chang Lee; Yu-Chun Chuang; Prakash C. Loni; Wei-Hsin Chen; Shan-Li Wang (Chemosphere, 2023)

Microplastics in the soil environment: Focusing on the sources, its transformation and change in morphology - Junyu Zhu; Guowen Dong; Fu Feng; Jing Ye; Ching-Hua Liao; Chih-Hung Wu; Sheng-Chung Chen (Science of The Total Environment, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

Hybridize magnesium-iron layered double hydroxide with biopolymers to develop multiple pathways for phosphate sorption and release: A potential slow release phosphorus fertilizer - Wen-Hui Li; Liang-Ching Hsu; Yu-Min Tzou; Yi-Chun Chen; Heng Yi Teah; Yu-Yu Kung; Han-Yu Chen; Yu-Ting Liu (Chemical Engineering Journal, 2023)

Severity of Liver Cirrhosis Evaluated by Digital Subtraction Angiography Using Quantitative Color-Coding Analysis Before Transarterial Embolization - Lung-Hui Giiang; Chang-Hsien Liu; Chih-Yung Yu; Te-Pao Lin; Hsiang-Cheng Chen; Chun-Jung Juan; Yu-Ching Chou (Journal of Medical and Biological Engineering, 2023)

Capture of colloidal fine suspended particle by aquatic vegetation under rainfall - Congrong Yu; Xiuhui Ye; Ying Li; Ching-Sheng Huang; Zhongbo Yu; Gang Chen; Xiaoxiao Hao (Science of The Total Environment, 2023)

Duplicated paralog of sulfide: quinone oxidoreductase contributes to the adaptation to hydrogen sulfide-rich environment in the hydrothermal vent crab, Xenograpsus testudinatus - Chi Chen; Guan-Chung Wu; Yao-Tse Chung; Hau-Wen Li; Pei-Hsuan Chou; Yung-Che Tseng; Chieh-Jhen Chen; Sylvie Dufour; Ching-Fong Chang (Science of The Total Environment, 2023)

Effect of indoor air quality on the association of long-term exposure to low-level air pollutants with cognition in older adults - Yen-Ching Chen; Pei-Iun Hsieh; Jia-Kun Chen; Emily Kuo; Hwa-Lung Yu; Jeng-Min Chiou; Jen-Hau Chen (Environmental Research, 2023)

Parameter correlation study on two new analytical solutions for radially divergent tracer tests in two-zone confined aquifers with vertical dispersion effect - Chen Wang; Ching-Sheng Huang; Chenchen Tong; Cheng-Haw Lee (Advances in Water Resources, 2023)

Exploring electric moped sharing preferences with integrated choice and latent variable approach - Ching-Fu Chen; Chiang Fu; Pei-Ya Siao (Transportation Research Part D: Transport and Environment, 2023)

Cleanup of Cr(VI)-polluted groundwater using immobilized bacterial consortia via bioreduction mechanisms - Wei-Han Lin; Chih-Ching Chien; Jiun-Hau Ou; Ying-Liang Yu; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Management, 2023)

Resilience and probiotic interventions to prevent and recover from shrimp gut dysbiosis - Ramya Kumar; Mei-Ying Huang; Chih-Ling Chen; Han-Ching Wang; Hsiao-Pei Lu (Fish & Shellfish Immunology, 2023)

Regulating energy gap in Ir-based ionic complexes to generate near-infrared emissions: Application in solid-state light-emitting electrochemical cells - Yan-Ding Lin; Pei-Wan Hsiao; Wun-Yu Chen; Sih-Yu Wu; Wei-Min Zhang; Chin-Wei Lu; Hai-Ching Su (Chemical Engineering Journal, 2023)

Application of chitosan with different molecular weights in cartilage tissue engineering - Runjie Zhang; Shwu Jen Chang; Yanzhen Jing; LiYuan Wang; Ching-Jung Chen; Jen-Tsai Liu (Carbohydrate Polymers, 2023)

Rat Hair Metabolomics Analysis Reveals Perturbations of Unsaturated Fatty Acid Biosynthesis, Phenylalanine, and Arachidonic Acid Metabolism Pathways Are Associated with Amyloid-β-Induced Cognitive Deficits - Tian-Hoe Tan; Shih-Wen Li; Chih-Wei Chang; Yuan-Chih Chen; Yu-Hsuan Liu; Jui-Ti Ma; Ching-Ping Chang; Pao-Chi Liao (Molecular Neurobiology, 2023)
Hair is a noninvasive valuable biospecimen for the long-term assessment of endogenous metabolic disturbance. Whether the hair is suitable for identifying biomarkers of the Alzheimer’s disease (AD) process remains unknown. We aim to investigate the metabolism changes in hair after β-amyloid (Aβ 1-42 ) exposure in rats using ultra-high-performance liquid chromatography-high-resolution mass spectrometry–based untargeted and targeted methods. Thirty-five days after Aβ 1-42 induction, rats displayed significant cognitive deficits, and forty metabolites were changed, of which twenty belonged to three perturbed pathways: (1) phenylalanine metabolism and phenylalanine, tyrosine, and tryptophan biosynthesis— l -phenylalanine, phenylpyruvate, ortho-hydroxyphenylacetic acid, and phenyllactic acid are up-regulated; (2) arachidonic acid (ARA) metabolism—leukotriene B4 (LTB4), arachidonyl carnitine, and 5(S)-HPETE are upregulation, but ARA, 14,15-DiHETrE, 5(S)-HETE, and PGB2 are opposite; and (3) unsaturated fatty acid biosynthesis— eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), FA 18:3 + 1O, and FA 18:3 + 2O are downregulated. Linoleic acid metabolism belonging to the biosynthesis of unsaturated fatty acid includes the upregulation of 8-hydroxy-9,10-epoxystearic acid, 13-oxoODE, and FA 18:2 + 4O, and downregulation of 9(S)-HPODE and dihomo-γ-linolenic acid. In addition, cortisone and dehydroepiandrosterone belonging to steroid hormone biosynthesis are upregulated. These three perturbed metabolic pathways also correlate with cognitive impairment after Aβ 1-42 stimulation. Furthermore, ARA, DHA, EPA, l -phenylalanine, and cortisone have been previously implicated in the cerebrospinal fluid of AD patients and show a similar changing trend in Aβ 1-42 rats’ hair. These data suggest hair can be a useful biospecimen that well reflects the expression of non-polar molecules under Aβ 1-42 stimulation, and the five metabolites have the potential to serve as novel AD biomarkers.

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Estimating arsenic biotransfer factors from feed to chicken: a viable approach to animal feed risk assessment - Ching-Chi Hung; Hsin-Tang Lin; Ching-Yi Chen; Kuan-Yi Chen; Tsung-Yu Lee; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Ethanol production using the whole solid-state fermented sugarcane bagasse cultivated by Trichoderma reesei RUT-C30 supplemented with commercial cellulase - Ching An Lin; Cheng Cheng; Li Wei Chen; C. Will Chen; Kow Jen Duan (Biocatalysis and Agricultural Biotechnology, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Inferring faulting model using InSAR deformation differencing vector: application to the 2014 Napa earthquake - Ying-Hui Yang; Hao-Liang Li; Qiang Chen; Jing Chen; Jyr-Ching Hu; Xiao-Yun Li; Qiang Xu (Journal of Geodesy, 2023)

Commentary: Evaluating stock status of 16 commercial fish species in the coastal and offshore waters of Taiwan using the CMSY and BSM methods - Ting-Chun Kuo; Nan-Jay Su; Ching-Chun Cheng; Kwang-Ming Liu; Chih-Shin Chen; Hsueh-Jung Lu; Ming-An Lee (Frontiers in Marine Science, 2023)

Co-incidence of BA.1 and BA.2 at the start of Singapore's Omicron wave revealed by Community and University Campus wastewater surveillance - Feng Jun Desmond Chua; Se Yeon Kim; Eric Hill; Jia Wei Cai; Wei Lin Lee; Xiaoqiong Gu; Siti Aisyah Afri Affandi; Wee Chiew Germaine Kwok; Weijie Ng; Mats Leifels; Federica Armas; Franciscus Chandra; et al. (Science of The Total Environment, 2023)

Effect of polysaccharide derived from dehulled adlay on regulating gut microbiota and inhibiting Clostridioides difficile in an in vitro colonic fermentation model - Bao-Hong Lee; Shih-Ching Huang; Chih-Yao Hou; You-Zuo Chen; Yu-Hsin Chen; Sulfath Hakkim Hazeena; Wei-Hsuan Hsu (Food Chemistry, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Recent development of sustainable self-healable electronic skin applications, a review with insight - Jean-Sébastien Benas; Fang-Cheng Liang; Manikandan Venkatesan; Zhen-Li Yan; Wei-Cheng Chen; Su-Ting Han; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2023)

Predicting survival after radiosurgery in patients with lung cancer brain metastases using deep learning of radiomics and EGFR status - Chien-Yi Liao; Cheng-Chia Lee; Huai-Che Yang; Ching-Jen Chen; Wen-Yuh Chung; Hsiu-Mei Wu; Wan-Yuo Guo; Ren-Shyan Liu; Chia-Feng Lu (Physical and Engineering Sciences in Medicine, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Enhancing the mechanical and hydromechanical behaviors of mudstone soils using sugarcane press mud - Febi Satria Gumanta; Soheil Ghadr; Chieh-Sheng Chen; Chih-Hsuan Liu; Ching Hung; Arya Assadi-Langroudi (Transportation Geotechnics, 2023)

Chemical decontamination of foods using non-thermal plasma-activated water - Samuel Herianto; Rachelle D. Arcega; Chih-Yao Hou; How-Ran Chao; Ching-Chang Lee; Chia-Min Lin; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2023)

An efficient cellular image-based platform for high-content screening of neuroprotective agents against chemotherapy-induced neuropathy - Yang-Chen Chang; Yi-Ching Lo; Hsun-Shuo Chang; Hui-Ching Lin; Chien-Chih Chiu; Yih-Fung Chen (NeuroToxicology, 2023)

Building high-capacity mesoporous adsorbents for fluoride removal through increased surface oxygen anions using organogel-assisted synthesis - Wei-Fan Kuan; Fang-Yu Chang; Jhih-Jing Chang; Hsuan-Chih Kuo; Chia-Hsun Hsieh; Jenn Fang Su; Ching-Lung Chen (Journal of Cleaner Production, 2023)

Improvement of enzymatic cross-linking of ovalbumin and ovotransferrin induced by transglutaminase with heat and reducing agent pretreatment - Chun-Chi Chen; Ming-Ching Kao; Chao-Jung Chen; Cheng-Hsun Jao; Jung-Feng Hsieh (Food Chemistry, 2023)

Deficiency of RAB39B Activates ER Stress-Induced Pro-apoptotic Pathway and Causes Mitochondrial Dysfunction and Oxidative Stress in Dopaminergic Neurons by Impairing Autophagy and Upregulating α-Synuclein - Ching-Chi Chiu; Yi-Hsin Weng; Tu-Hsueh Yeh; Juu-Chin Lu; Wan-Shia Chen; Allen Han-Ren Li; Ying-Ling Chen; Kuo-Chen Wei; Hung-Li Wang (Molecular Neurobiology, 2023)

Transformation of dissolved organic matter during UV/peracetic acid treatment - Penghui Du; Wen Liu; Qiang Zhang; Peng Zhang; Chen He; Quan Shi; Ching-Hua Huang; Junjian Wang (Water Research, 2023)

Enhanced nitrate reduction over functionalized Pd/Cu electrode with tunable conversion to nitrogen and sodium hydroxide recovery - Kuan-Ling Chen; Muhammad Sheraz Ahmad; Ching-Lung Chen (Science of The Total Environment, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

Homogenization of spatially variable hydraulic conductivity in the presence of a geotechnical structure - Jianye Ching; Zhi-Yu Chen; Kok-Kwang Phoon (Computers and Geotechnics, 2023)

Sleep disturbance in adults with untreated primary brain tumors: prevalence and impact on quality of life - Pei-Ching Lin; Pin-Yuan Chen; Kuo-Chen Wei; Jian-her Lin; Mei-Ru Lin; Huan-Chih Wang; Hsiao-Yean Chiu (Sleep and Biological Rhythms, 2023)

United States Federal Emergency Management Agency regional clustering by disaster exposure: a new paradigm for disaster response - Colton Margus; Attila Hertelendy; Yudong Tao; Erik Coltey; Shu-Ching Chen; Steven Luis; Mei-Ling Shyu; Gregory R. Ciottone (Natural Hazards, 2023)

NOx removal and copper recovery from the leaching process for waste printed circuit boards: performance evaluation and potential environmental impact assessment - Tse-Lun Chen; Yen-Syun Chen; Pen-Chi Chiang; Yi-Hung Chen; Ching-Hsiang Hsu (Environmental Science and Pollution Research, 2023)

Juvenile and Trash Fish Excluder Device (JTED) for Taiwanese Bottom Trawl - Chao-Ching Chen; Hsin-Zong Lin; Kuo-Wei Lan (Fishes, 2023)
Juvenile and trash fish excluder devices (JTEDs) are used to mitigate the ecological impact of trawling. Trawling has a large ecological footprint in Taiwan. Thus, this study designed three JTEDs, which differed only in grid interval, for single boat bottom otter trawls that are commonly used in Taiwan. The designed JTEDs were tested in the waters off of Kaohsiung on a Kaohsiung-based bottom trawler, and the results were as follows. (1) At least 300 species were caught, and 189 of these species had little commercial value; their weight accounted for 52.5% of the total catch. (2) The three JTEDs had good exclusion performance. (3) The ratios of the weight of bycatch excluded to the weight of total catch were 7.9%, 29.1%, and 36.2%, for grid intervals of 10, 15, and 20 mm, respectively. (4) JTEDs with grid intervals of 10, 15, and 20 mm were associated with a 0.4%, 11.5%, and 19.0% loss in revenue, respectively. (5) Mature (and thus commercially valuable) Loliginidae tended to be excluded when the grid interval was 20 or (especially) 15 mm. In general, the designed JTEDs should be used at a grid size of 15 mm because this strikes the best balance between profitability and sustainability.

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Benzyl isothiocyanate attenuates activation of the NLRP3 inflammasome in Kupffer cells and improves diet-induced steatohepatitis - Chia-Wen Lo; Chih-Ching Yen; Chun-You Chen; Haw-Wen Chen; Chong-Kuei Lii (Toxicology and Applied Pharmacology, 2023)

Removal and concurrent reduction of Cr(VI) by thermoacidophilic Cyanidiales: a novel extreme biomaterial enlightened for acidic and neutral conditions - Yen-Lin Cho; Yu-Min Tzou; Chun-Chieh Wang; Yao-Chang Lee; Liang-Ching Hsu; Shao-Lun Liu; Afifah Assakinah; Yu-Hsien Chen; Nhu Anh Thi Than; Yu-Ting Liu; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Analytical multispecies chemical mixture transport model comprising degradable byproducts subject to scale-dependent dispersion - Jui-Sheng Chen; Ssu-Yen Jiang; Heejun Suk; Ching-Ping Liang; Chen-Wuing Liu (Hydrogeology Journal, 2023)

Health Risk of Infants Exposed to Lead and Mercury Through Breastfeeding - Yung-Chieh Lin; Wei-Hsiang Chang; Tsun-Ching Li; Osuke Iwata; Hsiu-Ling Chen (Exposure and Health, 2023)
Donor milk from the human milk bank is important for vulnerable infants without their mothers’ own milk. Longitudinal changes in toxic metals in donor milk has not been reported. This study aimed to assess the effect of donors’ demographic characteristics, life habits and dietary habits on the concentration of metals in breastmilk donated to a human milk bank and to assess the health risk of lead (Pb) and mercury (Hg) exposure of donor mothers’ offspring through breastfeeding and the vulnerable recipients. A total of 228 samples, which were longitudinally donated to the human milk bank by 39 donors, were selected specifically to assess the levels of Pb, Hg, and MeHg. Donors’ offspring were also enrolled as mother-infant-dyads to monthly obtain the milk consumption and body weight. The results showed significant differences in the infant risk in exclusive breastfeeding months. The average Pb level of breast milk was 6.49 ± 5.23 µg/L (mean ± standard deviation), and the Hg level was 0.76 ± 0.98 µg/L. The sources of these toxins—residential districts, cleaning products, cosmetics, drinking water, viscera, eggs, seafood, and canned food—have a significant influence on the concentration of toxic metals in human milk. This study showed an unacceptable non-cancerous health risk (95th percentile hazard index, HI = 1.37 > 1) for Pb and Hg. In the future, the breast milk offered by the bank should be strictly monitored, especial for Pb, to ensure high-quality donor milk for vulnerable recipients but also donor mothers’ offspring who depend on it. Graphical Abstract

Bouguer gravity anomalies and the three-dimensional density structure of a thick mudstone area: A case study of southwestern Taiwan - Yu-Tsung Lo; Kuo-En Ching; Horng-Yuan Yen; Song-Chuen Chen (Tectonophysics, 2023)

Toxicity prediction: An application of alternative testing and computational toxicology in contaminated groundwater sites in Taiwan - Rachelle D. Arcega; Rong-Jane Chen; Pei-Shan Chih; Yi-Hsuan Huang; Wei-Hsiang Chang; Ting-Khai Kong; Ching-Chang Lee; Trias Mahmudiono; Chun-Chih Tsui; Wen-Che Hou; Hsin-Ta Hsueh; Hsiu-Ling Chen (Journal of Environmental Management, 2023)

Nitrogen-phosphorous co-doped palladium electrocatalyst for glycerol electro-oxidation reaction (GEOR): An efficient system for mesoxalic acid and dihydroxyacetone production - Muhammad Sheraz Ahmad; Kim Hoong Ng; Ching-Lung Chen; Faryal Kabir; Thongthai Witoon; Ta Yeong Wu; Chin Kui Cheng (Fuel, 2023)

In situ derived sulfated/sulfonated carbon nanogels with multi-protective effects against influenza a virus - Hung-Yun Lin; Ka-Long Luo; Ju-Yi Mao; Chin-Jung Lin; Chen-Yow Wang; Lauren Panny; Shiow-Yi Chen; Shih-Chao Lin; Chih-Ching Huang; Scott G. Harroun; Robert Y.L. Wang; Chang-Jer Wu (Chemical Engineering Journal, 2023)

Multi-objective operation optimization of spent coffee ground torrefaction for carbon–neutral biochar production - Wei-Hsin Chen; Kuan-Ting Lee; Kuan-Yu Ho; Alvin B. Culaba; Veeramuthu Ashokkumar; Ching Joon Juan (Bioresource Technology, 2023)

Transcriptomic profile of symbiotic accessory nidamental gland during female maturation in bigfin reef squid - Peng-Wei Tseng; Hau-Wen Li; Chih Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2023)
The bigfin reef squid, Sepioteuthis lessoniana , are a valuable commercial species in East Asian regions such as Taiwan and Japan. A lack of genomic information limits the application of potential aquaculture techniques, especially in breeding when considering the hatching rate of offspring. In some squids and cuttlefishes, symbiotic bacteria are transmitted from the accessory nidamental gland (ANG) to the jelly coat of eggs. In Hawaiian bobtail squid, these parent-delivered mutualistic bacteria play an important role in preventing lethal biofouling of the eggs and accelerating the hatch rate of offspring. The bacterial consortium, which is housed in the female squids ANG, are governed by host selection during female maturation. Immune functions are typically used to explain the regulatory mechanism of symbioses by host selection. In this study, we evaluated the transcripts featured in bacterial selection and maintenance during ANG development using RNA-seq. Different developmental stages of ANGs (stages 1–4) were sequenced. The de novo transcriptome assembly resulted in 524,918 unigenes. Two groups, non-pigmentation group (stage 1 and stage 3) and pigmentation group (stage 4), were clustered by transcriptome-wide expression profile analysis. The gene expression analyses indicated that 9,475 differential expression genes (DEGs) in three different phases and 1,363 (14.3%) DEGs were matched in the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Furthermore, KEGG-enriched analysis results suggested that immune responses are a dominant pathway in the non-pigmentation group (stage 1 and stage 3) whereas lipid metabolism and metabolism of flora fermentation are dominant in the pigmentation group (stage 4). Although the host immunity plays an important role during bacterial colonization of the ANG in bigfin reef squid, our results showed that most immune-related genes had a reduced transcriptomic level in the pigmentation group compared with the non-pigmentation group. Therefore, our results provide new insight to understand the regulatory mechanisms of initial bacterial colonization and later bacterial pigmentation in the bigfin reef squid.

Two new chromones and a new coumarin from the fruit of Cnidium monnieri (L.) Cusson - Hui-Chi Huang; Chun-Hsiang Lin; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Che-Yi Chao; Guan-Jhong Huang; Yueh-Hsiung Kuo (Natural Product Research, 2023)

Bioremediation potential of cadmium by recombinant Escherichia coli surface expressing metallothionein MTT5 from Tetrahymena thermophila - Che-Wei Lu; Hsin-Cheng Ho; Chao-Ling Yao; Tsung-Yu Tseng; Chih-Ming Kao; Ssu-Ching Chen (Chemosphere, 2023)

The modulation of Pacific Decadal Oscillation on ENSO-East Asian summer monsoon relationship over the past half-millennium - Nguyen-Xuan Hau; Masaki Sano; Takeshi Nakatsuka; Shin-Hao Chen; I-Ching Chen (Science of The Total Environment, 2023)

CO2 dynamics in a small and old subtropical reservoir in East Asia: Environmental controls driving seasonal and spatial variability - Chun Ngai Chan; Matthew J. Bogard; Fong Ching Ma; Yu Ching Ip; Boyi Liu; Shuai Chen; Lishan Ran (Science of The Total Environment, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

An analytical and meshless model for 3D transient flow in a confined aquifer with nonuniform thickness: Application to stream depletion due to groundwater extraction - Chenchen Tong; Chen Wang; Manling Xiong; Ching-Sheng Huang; Hund-Der Yeh (Environmental Modelling & Software, 2023)

The classification and localization of crack using lightweight convolutional neural network with CBAM - Liujie Chen; Haodong Yao; Jiyang Fu; Ching Tai Ng (Engineering Structures, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Removal of tetracycline by a photocatalytic membrane reactor with MIL-53(Fe)/PVDF mixed-matrix membrane - Chien-Jung Wu; Irish Valerie Maggay; Ching-Hsueh Chiang; Wei Chen; Yung Chang; Chechia Hu; Antoine Venault (Chemical Engineering Journal, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

The involvement of AtMKK1 and AtMKK3 in plant-deleterious microbial volatile compounds-induced defense responses - Ching-Han Chang; Wu-Guei Wang; Pei-Yu Su; Yu-Shuo Chen; Tri-Phuong Nguyen; Jian Xu; Masaru Ohme-Takagi; Tetsuro Mimura; Ping-Fu Hou; Hao-Jen Huang (Plant Molecular Biology, 2023)

Durations of virtual exposure to built and natural landscapes impact self-reported stress recovery: evidence from three countries - Pongsakorn Suppakittpaisarn; Chia-Ching Wu; Yu-Hsin Tung; Yu-chen Yeh; Chulalux Wanitchayapaisit; Matthew H. E. M. Browning; Chun-Yen Chang; William C. Sullivan (Landscape and Ecological Engineering, 2023)

Development of the dried blood spot preparation protocol for comprehensive evaluation of the hematocrit effect - Chih-Ning Cheng; Yu-Fong Peng; Ju-Yu Chen; Guan-Yuan Chen; Te-I Weng; Ching-Hua Kuo (Analytica Chimica Acta, 2023)

Coupling phytotoxicity and human health risk assessment to refine the soil quality standard for As in farmlands - Kai-Wei Juang; Li-Jia Chu; Chien-Hui Syu; Bo-Ching Chen (Environmental Science and Pollution Research, 2022)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

QTL analyses of soybean root system architecture revealed genetic relationships with shoot-related traits - Zhili Wang; Cheng Huang; Yongchao Niu; Wai-Shing Yung; Zhixia Xiao; Fuk-Ling Wong; Mingkun Huang; Xin Wang; Chun-Kuen Man; Ching-Ching Sze; Ailin Liu; Qianwen Wang; et al. (Theoretical and Applied Genetics, 2022)

Efficacy of methylphenidate for the treatment of apathy in patients with Alzheimer’s disease: a systematic review and meta-analysis of randomized controlled studies - Chia-Wei Lee; Jui-Yi Chen; Ching-Chung Ko; Min-Hsiang Chuang; Wen-Wen Tsai; Cheuk-Kwan Sun; Kuo-Chuan Hung (Psychopharmacology, 2022)

Long-term dietary restriction ameliorates ageing-related renal fibrosis in male mice by normalizing mitochondrial functions and autophagy - Chun-Hsien Chiang; Sin-Jin Li; Ting-Rui Zhang; Ching-Yi Chen (Biogerontology, 2022)

ZAKβ Alleviates Oxidized Low-density Lipoprotein (ox-LDL)-Induced Apoptosis and B-type Natriuretic Peptide (BNP) Upregulation in Cardiomyoblast - Yueh-Min Lin; Jiro Hasegawa Situmorang; Jia-Zun Guan; Dennis Jine-Yuan Hsieh; Jaw-Ji Yang; Michael Yu-Chih Chen; Ching-Hui Loh; Chia-Hua Kuo; Shang-Yeh Lu; Ying-Ming Liou; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2022)

Attention deficit hyperactivity disorder among children related to maternal job stress during pregnancy in Taiwan: a prospective cohort study - Ping Shih; Ching-chun Huang; Tung-liang Chiang; Pau-Chung Chen; Yue Leon Guo (International Archives of Occupational and Environmental Health, 2022)

Mechanical behavior of sands reinforced with shredded face masks - Soheil Ghadr; Chieh-Sheng Chen; Chih-hsuan Liu; Ching Hung (Bulletin of Engineering Geology and the Environment, 2022)

The Spatial Variation in Chlorophyte Community Composition From Coastal to Offshore Waters in a Subtropical Continental Shelf System - Yun-Chi Lin; Chien-Pang Chin; Wei-Ting Chen; Ching-Ting Huang; Gwo-Ching Gong; Kuo-Ping Chiang; Xin-Bei Chen (Frontiers in Marine Science, 2022)
Globally, the continental shelf occupies less than 10% of the total sea surface, but supports substantial primary production and fisheries. Photosynthetic picoeukaryotes (PPE) are important primary producers in marine ecosystems, and chlorophytes make a significant contribution to PPE abundance. Although the distribution of chlorophytes has been widely studied, little is known about how their community composition varies along the coastal-offshore gradient in subtropical continental shelf waters. To better understand their spatial variations, we employed metabarcoding data of 18S rRNA V4 gene to examine chlorophyte composition within the surface and deep chlorophyll maximum (DCM) layers over the continental shelf in the East China Sea (ECS) with high-resolution sampling. Our results indicate a higher chlorophyte diversity in the surface layer than in the DCM. In addition, we found that chlorophytes in oligotrophic Kuroshio surface water were the most diverse, with a higher percentage of Chloropicophyceae, prasinophyte clade V, prasinophyte clade IX, Palmophyllophyceae and Chlorodendrophyceae. In more eutrophic waters along the coast and within the DCM layer, chlorophytes were dominated by Mamiellophyceae. A significant spatial variation in community composition occurred along the nutrient gradient in the subtropical continental shelf ecosystem, varying from Mamiellophyceae-dominant in coastal water to Chloropicophyceae-dominant in offshore water. Furthermore, at a low saline coastal station, which had the lowest chlorophyte diversity, Picochlorum (Trebouxiophyceae) was dominant. Overall, chlorophyte diversity was positively correlated with temperature, and negatively correlated with silicate concentration. This study revealed that terrestrial input into continental systems influences chlorophyte diversity in the subtropical northwestern Pacific Ocean.

Pre-existing Reactivity to an IgG4 Fc-Epitope: Characterization and Mitigation of Interference in a Bridging Anti-drug Antibody Assay - Michael A. Partridge; Jihua Chen; Elif Kabuloglu Karayusuf; Thanoja Sirimanne; Colin Stefan; Ching Ha Lai; Meghna Gathani; Lisa DeStefano; Michal Rozanski; Sean McAfee; Manoj Rajadhyaksha; Matthew D. Andisik; et al. (The AAPS Journal, 2022)
Twenty percent of baseline patient samples exhibited a pre-existing response in a bridging anti-drug antibody (ADA) assay for a human IgG4 monoclonal antibody (mAb) therapeutic. In some cases, assay signals were more than 100-fold higher than background, potentially confounding detection of true treatment-emergent ADA responses. The pre-existing reactivity was mapped by competitive inhibition experiments using recombinant proteins or chimeric human mAbs with IgG4 heavy chain regions swapped for IgG1 sequences. These experiments demonstrated that the majority of the samples had reactivity to an epitope containing leucine 445 in the CH3 domain of human IgG4. The pre-existing reactivity in baseline patient samples was mitigated by replacing the ADA assay capture reagent with a version of the drug containing a wild type IgG1 proline substitution at residue 445 without impacting detection of drug-specific, treatment-emergent ADA. Finally, purification on Protein G or anti-human IgG (H + L) columns indicated the pre-existing response was likely due to immunoglobulins in patient samples. Graphical abstract

Preliminary establishment of a mass movement warning system for Taiwan using the soil water index - Chi-Wen Chen; Ching Hung; Guan-Wei Lin; Jun-Jih Liou; Shih-Yao Lin; Hsin-Chi Li; Yung-Ming Chen; Hongey Chen (Landslides, 2022)

Sex-specific differences in early renal impairment associated with arsenic, lead, and cadmium exposure among young adults in Taiwan - Kai-Wei Liao; Ling-Chu Chien; Yang-Ching Chen; Ho-Ching Kao (Environmental Science and Pollution Research, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Useful rapid light-response curve of electron transport rate for estimations of photosynthetic capacity in C4 species - Meng-Yuan Huang; Chung-Wei Chen; Ching-Wen Wang; Shau-Lian Wong; Jen-Hsien Weng (Theoretical and Experimental Plant Physiology, 2022)

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

Using DeepLab v3 + -based semantic segmentation to evaluate platelet activation - Tsung-Chen Kuo; Ting-Wei Cheng; Ching-Kai Lin; Ming-Che Chang; Kuang-Yao Cheng; Yun-Chien Cheng (Medical & Biological Engineering & Computing, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Geographic distance, sedimentation, and substrate shape cryptic crustose coralline algal assemblages in the world’s largest subtropical intertidal algal reef - Shing Hei Zhan; Ling Chen; Chen‐Pan Liao; Wun‐Ruei Chang; Cheng‐Chin Li; Guang‐You Tang; Ching‐Yu Liou; Wei‐Lung Wang; Shih‐Wei Wang; Shao‐Lun Liu (Molecular Ecology, 2022)
Algal reefs, concreted by crustose coralline algae (CCA), are the main biotic reefs in temperate waters but rare in the subtropics and tropics. The world's largest known intertidal algal reef in the subtropics is the Taoyuan Algal Reef (TAR) located in the northwestern coast of Taiwan. The biodiversity and ecology of the TAR are scarcely explored, and now the reef is imperiled by industrialization. Here, we document cryptic species of CCA in Taiwan, particularly the TAR, by sequencing the psb A genes of over 1800 specimens collected across Taiwan. We also examine the ecological background of the TAR by surveying its benthic composition and measuring its environmental parameters. Our data reveal that the TAR harbours a high diversity of cryptic CCA species (27 molecular operational taxonomic units, or mOTUs), many of which are potentially new to science (18 mOTUs) and/or endemic to the TAR (9 mOTUs). Comparing the CCA species inventory of the TAR with the rest of Taiwan shows that the TAR represents a unique hotspot of CCA taxa in the waters of Taiwan. Our analyses show that variation in the CCA assemblages in the TAR is associated with geographic distance, sedimentation, and substrate type (for example, reef vs. hermit crab shell), suggesting that dispersal limitation and contemporary environmental selection shape the CCA assemblages in the TAR. The data from this study can inform the monitoring of human impacts on the health of the TAR and contribute to our understanding of the ecological processes underlying algal reef development.

The regulation of shrimp metabolism by the white spot syndrome virus (WSSV) - Ramya Kumar; Jiun‐Yan Huang; Yen‐Siong Ng; Cong‐Yan Chen; Han‐Ching Wang (Reviews in Aquaculture, 2022)
For more than three decades, infectious diseases have been one of the major causes of economic losses in the global shrimp industry. One of the deadliest of the shrimp pathogens is white spot syndrome virus (WSSV), which causes mass mortality in farmed shrimp. Various aspects of WSSV pathogenicity have been studied, but in this review, we will focus only on one of them, namely metabolic reprogramming. WSSV’s modulation of host metabolism affects glycolysis, the tricarboxylic acid (TCA) cycle, glutaminolysis and lipid metabolism. Several signaling pathways are involved in this regulation, including JAK‐STAT, PI3K‐AKT‐mTOR, MAPK and Ras‐Raf‐MEK, with the PI3K‐Akt‐mTOR pathway in particular playing a critical role in activating the WSSV‐induced Warburg effect. Taken together, these changes benefit the virus by facilitating WSSV replication. In this review, we summarize current knowledge regarding the metabolism‐related aspects of WSSV pathogenesis, and discuss the mechanisms by which this virus reprograms its host's metabolic pathways. A deeper understanding of these pathways, key metabolic enzymes and signaling mechanisms is potentially important for the development of effective anti‐WSSV strategies.

The Characteristics and Expression Profile of Peptidoglycan Recognition Protein 2 in the Accessory Nidamental Gland of the Bigfin Reef Squid During Bacterial Colonization - Hau-Wen Li; Wei-Lun Kuo; Chi Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2022)
Some cephalopods carry microorganisms in two specialized organs, the light organ and the accessory nidamental gland (ANG). For the light organ, comprehensive mechanisms have been described for winnowing (bacterial selection) and maintenance of the symbiotic luminescent bacterium Vibrio fischeri ( V. fischeri ). However, the mechanisms controlling bacterial selection and maintenance during bacterial colonization of the ANG are open biological issues with physiological significance. Our recent study on bigfin reef squid ( Sepioteuthis lessoniana ) already showed that the ANG bacterial community shifts gradually and exhibits decreased diversity throughout maturation. This study further describes a potential role of an innate immunity-involved molecule, peptidoglycan recognition proteins (PGRPs), in the ANG of bigfin reef squid during bacterial transmission and colonization. First, we found that four homologs of the PGRP family are expressed in the ANG of bigfin reef squid ( sl PGRP2-5), but only slPgrp2 transcript levels are highly correlated with ANG development and bacterial colonization. Besides, slPgrp2 transcripts are mainly expressed in the epithelial cells of certain secondary tubules of ANG, and the expression levels are varied in the epithelial cells of other secondary tubules. This data reveals that slPgrp2 transcripts may associate with the composition of bacterial consortium and its secretary factors. Moreover, recombinant sl PGRP2 had a negative effect of Escherichia coli ( E.coli ) which inhibited bacterial growth in culture. Therefore, our data suggest slPgrp2 expression in the epithelial cells of secondary tubules in the ANG may have an essential role in the winnowing and maintenance of holobiont homeostasis in bigfin reef squid.

Interleukin-6 transiently promotes proliferation of osteoclast precursors and stimulates the production of inflammatory mediators - Peng-Yuan Chang; Hung-Kang Wu; Yu-Hsu Chen; Yu-Pao Hsu; Ming-Te Cheng; Ching-Hsiao Yu; Shau-Kwaun Chen (Molecular Biology Reports, 2022)

The assessment of rill irrigation and perforated pipes for Lowland paddy rice under the system of rice intensification (SRI) - Hsin-Piao Chiu; Yi-Lung Yeh; Samkele S. Tfwala; Gcina Mavuso; Ching-Nuo Chen (Paddy and Water Environment, 2022)

Effects of the Coastal Uplift on the Kuroshio Ecosystem, Eastern Taiwan, the Western Boundary Current of the North Pacific Ocean - Chung-Chi Chen; Chun-Yi Lu; Sen Jan; Chih-hao Hsieh; Chih-Ching Chung (Frontiers in Marine Science, 2022)
The Kuroshio is the western boundary current of the North Pacific Ocean. In the subtropical region of eastern Taiwan, a coastal uplift of the isotherms has occurred. To explore its impact on this oligotrophic ecosystem, hydrographic data along the transect line at 23.75°N were measured between September 2012 and September 2014. Results show that the intensity of coastal uplift was positively correlated to the flow volume transport of the Kuroshio. Significant dissolved inorganic nutrients were uplifted to the sunlit zone, especially in the onshore. For example, compared to the offshore, nitrate concentration increased 0.49 μM (or ∼178%) in the upper 100 m of the onshore. The increased nutrients thereafter enhanced the growth of phytoplankton; for instance, the Chl a concentration increased 88.3%, compared to offshore, in the upper 100 m of the onshore. Phytoplankton community was mostly composed of picophytoplankton (<2 μm in size), which were dominated, in terms of relative abundance, by Prochlorococcus (83.6%), followed by Synechococcus (13.8%) and picoeukaryotes (2.7%). The relative abundance of Prochlorococcus increased from onshore toward offshore, but the trend was reversed for Synechococcus and picoeukaryotes, which may be affected by the coastal uplift. The results also suggest that the coastal uplift may support more energy transferred to higher tropical levels in this oligotrophic Kuroshio ecosystem.

Reoxygenation of the Hypoxia in the East China Sea: A Ventilation Opening for Marine Life - Chung-Chi Chen; Dong S. Ko; Gwo-Ching Gong; Chun-Chi Lien; Wen-Chen Chou; Hung-Jen Lee; Fuh-Kwo Shiah; Yu-Sin Wita Huang (Frontiers in Marine Science, 2022)
Hypoxia and upwelling co-occur in the summer, and well-mixed water typically reaches the subsurface in the East China Sea (ECS), especially off the Changjiang River estuary. The impact of upwelling on hypoxia and, therefore, on the ecosystem in the ECS is not known. This study demonstrates both positive and negative effects of upwelling on hypoxia and its impact on the ecosystem. With upwelling, the spatial extent of hypoxic water increases with a lower pH but waters with high regenerated nutrients and fugacity of CO 2 ( f CO 2 ), which are normally confined to the near-bottom, are found just up to 5–10 m below the surface. This upwelled high nutrient water can enhance phytoplankton growth in this region. On one occasion in August 2014, upwelling reached to the surface and lasted for 3 weeks, with the area of coverage ranging from 326.8 to 24,368.0 km 2 . During this event, the water was mixed thoroughly throughout the water column, with high concentrations of nutrients, chlorophyll a , and slightly undersaturated dissolved oxygen but saturated f CO 2 , alongside a normal pH. This event may have served as an important pathway from the ocean to the atmosphere for the regenerated CO 2 . It also provided a productive and suitable environment for marine life and ventilation to alleviate low-oxygen stress in this hypoxic but upwelling region in the ECS.

Characterization of two chromate reducing bacteria isolated from heavy metal contaminated soil - Chih-Ming Kao; Ssu-Ching Chen; Zi-Yi Liao; Shu-Shiuan Wen; Chih-Ching Chien (Biologia, 2021)

A Unique Diel Pattern in Carbonate Chemistry in the Seagrass Meadows of Dongsha Island: The Enhancement of Metabolic Carbonate Dissolution in a Semienclosed Lagoon - Wen-Chen Chou; Lan-Feng Fan; Chang-Chang Yang; Ying-Hsuan Chen; Chin-Chang Hung; Wei-Jen Huang; Yung-Yen Shih; Keryea Soong; Hsiao-Chun Tseng; Gwo-Ching Gong; Hung-Yu Chen; Cheng-Kuan Su (Frontiers in Marine Science, 2021)
In contrast to other seagrass meadows where seawater carbonate chemistry generally shows strong diel variations with higher pH but lower partial pressure of CO 2 ( p CO 2 ) during the daytime and lower pH but higher p CO 2 during nighttime due to the alternation in photosynthesis and respiration, the seagrass meadows of the inner lagoon (IL) on Dongsha Island had a unique diel pattern with extremely high pH and low p CO 2 across a diel cycle. We suggest that this distinct diel pattern in pH and p CO 2 could be associated with the enhancement of total alkalinity (TA) production coupled to carbonate sediment dissolution in a semienclosed lagoon. The confinement of the IL may hamper water exchange and seagrass detritus export to the adjacent open ocean, which may result in higher organic matter loading to the sediments, and longer residence time of the water in the IL, accompanied by microbial respiration (both aerobic and anaerobic) that may reduce carbonate saturation level to drive carbonate dissolution and thus TA elevation, thereby forming such a unique diel pattern in carbonate chemistry. This finding further highlights the importance of considering TA production through metabolic carbonate dissolution when evaluating the potential of coastal blue carbon ecosystems to buffer ocean acidification and to absorb atmospheric CO 2 , in particular in a semienclosed setting.

A Comparative Analysis of Slack-Based Green Total Factor Productivity in China: a Directional Distance Function - Xuping Zhang; Xiang Chen; Ching-Cheng Lu; Fu-Yueh Cheng (Water, Air, & Soil Pollution, 2021)

New interpretation of the rupture process of the 2016 Taiwan Meinong Mw 6.4 earthquake based on the InSAR, 1-Hz GPS and strong motion data - Ying-Hui Yang; Qiang Chen; Xin Diao; Jingjing Zhao; Lang Xu; Jyr-Ching Hu (Journal of Geodesy, 2021)

Effectiveness of palonosetron versus granisetron in preventing chemotherapy-induced nausea and vomiting: a systematic review and meta-analysis - Yu-Chen Hsu; Ching-Yao Chen; Ka-Wai Tam; Chin-Yu Hsu (European Journal of Clinical Pharmacology, 2021)

Streptococcus vaginalis sp. nov., a novel bacterial species isolated from vaginal swabs of a pregnant woman with diabetes - An-Shine Chao; Chiao-Yun Lin; Angel Chao; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Yi-Sheng Chen (Archives of Microbiology, 2021)

Identification of Neuronal Polarity by Node-Based Machine Learning - Chen-Zhi Su; Kuan-Ting Chou; Hsuan-Pei Huang; Chiau-Jou Li; Ching-Che Charng; Chung-Chuan Lo; Daw-Wei Wang (Neuroinformatics, 2021)
Identifying the direction of signal flows in neural networks is important for understanding the intricate information dynamics of a living brain. Using a dataset of 213 projection neurons distributed in more than 15 neuropils of a Drosophila brain, we develop a powerful machine learning algorithm: node-based polarity identifier of neurons (NPIN). The proposed model is trained only by information specific to nodes, the branch points on the skeleton, and includes both Soma Features (which contain spatial information from a given node to a soma) and Local Features (which contain morphological information of a given node). After including the spatial correlations between nodal polarities, our NPIN provided extremely high accuracy (>96.0%) for the classification of neuronal polarity, even for complex neurons with more than two dendrite/axon clusters. Finally, we further apply NPIN to classify the neuronal polarity of neurons in other species (Blowfly and Moth), which have much less neuronal data available. Our results demonstrate the potential of NPIN as a powerful tool to identify the neuronal polarity of insects and to map out the signal flows in the brain’s neural networks if more training data become available in the future.

The use of multi-pronged screening strategy to understand the epidemiology of carbapenemase-producing Enterobacteriaceae in Hong Kong: transition from epidemic to endemic setting - Shuk- Ching Wong; Veronica Wing- Man Chan; Germaine Kit-Ming Lam; Christine Ho-Yan AuYeung; Elaine Yin-Ling Leung; Simon Yung-Chun So; Jonathan Hon-Kwan Chen; Siddharth Sridhar; Anthony Raymond Tam; Ivan Fan-Ngai Hung; Pak- Leung Ho; Kwok- Yung Yuen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Biomechanical Evaluation of a Fin-type Implant Compared to Traditional Buttress Plate for the Stabilization of the Posteromedial Fragment in Tibial Plateau Split Fractures - Jian-Chih Chen; Kang-Ping Lin; Tien-Ching Lee; Yin-Chih Fu; Kun-Jhih Lin (Journal of Medical and Biological Engineering, 2021)

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

Intermittent Hypoxia Activates N-Methyl-D-Aspartate Receptors to Induce Anxiety Behaviors in a Mouse Model of Sleep-Associated Apnea - Yun Fan; Mei-Chuan Chou; Yen-Chin Liu; Ching-Kuan Liu; Chu-Huang Chen; Shiou-Lan Chen (Molecular Neurobiology, 2021)

A Case Study of Whistle Detection and Localization for Humpback Dolphins in Taiwan - Ching-Tang Hung; Wei-Yen Chu; Wei-Lun Li; Yen-Hsiang Huang; Wei-Chun Hu; Chi-Fang Chen (Journal of Marine Science and Engineering, 2021)
In recent years, Taiwan’s government has focused on policies regarding offshore wind farming near the Indo-Pacific humpback dolphin habitat, where marine mammal observation is a critical consideration. The present research developed an algorithm called National Taiwan University Passive Acoustic Monitoring (NTU_PAM) to assist marine mammal observers (MMOs). The algorithm performs whistle detection processing and whistle localization. Whistle detection processing is based on image processing and whistle feature extraction; whistle localization is based on the time difference of arrival (TDOA) method. To test the whistle detection performance, we used the same data to compare NTU_PAM and the widely used software PAMGuard. To test whistle localization, we designed a real field experiment where a sound source projected simulated whistles, which were then recorded by several hydrophone stations. The data were analyzed to locate the moving path of the source. The results show that localization accuracy was higher when the sound source position was in the detection region composed of hydrophone stations. This paper provides a method for MMOs to conveniently observe the migration path and population dynamics of cetaceans without ecological disturbance.

Phenylpropanoids and lignoids from the whole plant of Vaccinium emarginatum and their cytotoxicity against prostate cancer cells - Ping-Chen Tu; Yu-Chia Liang; Ming-Ching Kao; Louis Kuoping Chao; Mei-Hwei Tseng; Te-Ling Lu; Ping-Jyun Sung; Yueh-Hsiung Kuo (Natural Product Research, 2021)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

Inhibition of p38 Mitogen–Activated Protein Kinase Ameliorates HAP40 Depletion–Induced Toxicity and Proteasomal Defect in Huntington’s Disease Model - Zih-Ning Huang; Jie-Mao Chen; Liang-Ching Huang; Yi-Hsuan Fang; Lu-Shiun Her (Molecular Neurobiology, 2021)

Germination dynamics of allergenic fungal spores in respiratory mucus - Wan-Rou Lin; Szu-Yu Chen; Shih-Ching Hsiao; Pi-Han Wang (Aerobiologia, 2021)

Effect of selected sampling media, flow rate, and time on the sampling efficiency of a liquid impinger packed with glass beads for the collection of airborne viruses - Yen-Chi Chen; I-Jen Wang; Chih-Ching Cheng; Yu-Chiao Wu; Chun-Hsuan Bai; Kuo-Pin Yu (Aerobiologia, 2021)

Fibroblast Growth Factor 9 Stimulates Neuronal Length Through NF-kB Signaling in Striatal Cell Huntington’s Disease Models - Issa Olakunle Yusuf; Hsiu-Mei Chen; Pei-Hsun Cheng; Chih-Yi Chang; Shaw-Jenq Tsai; Jih-Ing Chuang; Chia-Ching Wu; Bu-Miin Huang; H. Sunny Sun; Chuan-Mu Chen; Shang-Hsun Yang (Molecular Neurobiology, 2021)

Scaling effects of a eutrophic river plume on organic carbon consumption - Chung‐Chi Chen; Gwo‐Ching Gong; Kuo‐Ping Chiang; Fuh‐Kwo Shiah; Chih‐Ching Chung; Chin‐Chang Hung (Limnology and Oceanography, 2021)
The amount of fluvial input has important impacts on shelf regions. To understand how the magnitude of fluvial discharge affects plume ecosystems, particularly organic carbon consumption, data over 10 consecutive summers (2003–2012) were examined in the Changjiang River plume of the East China Sea. The area of the Changjiang River plume ranged from approximately 4.90 × 10 3 km 2 to 94.83 × 10 3 km 2 and varied in proportion to the freshwater discharge rate. Plankton community respiration was at the medium to high end of the values reported for coastal regions. Total organic carbon consumption over the Changjiang River plume was positively correlated with the Changjiang freshwater discharge. This scaling relationship might be associated with river flows delivering allochthonous organic carbon and dissolved inorganic nutrients into the East China Sea. However, plankton community respiration (per m 3 basis) decreased as the area of the Changjiang River plume increased; this rate appeared to have been influenced by particulate organic carbon (POC) levels and/or total plankton biomass. Even though POC was dominated by phytoplankton biomass allometrically, bacteria contributed more to plankton community respiration, possibly signifying that these bacteria were more reliant on plankton‐derived organic matter. Even with high phytoplankton biomass and primary productivity, this plume ecosystem was heterotrophic, albeit close to a state of carbon balance. To support high organic carbon consumption, in addition to allochthonous sources from fluvial runoff, a large amount of organic matter might have been autochthonous and derived from plankton in the Changjiang River plume.

Carbon monoxide-triggered health effects: the important role of the inflammasome and its possible crosstalk with autophagy and exosomes - Rong-Jane Chen; Yu-Hsuan Lee; Tzu-Hao Chen; Yu-Ying Chen; Ya-Ling Yeh; Ching-Ping Chang; Chien-Cheng Huang; How-Ran Guo; Ying-Jan Wang (Archives of Toxicology, 2021)

The Effect of Wave-Induced Current and Coastal Structure on Sediment Transport at the Zengwen River Mouth - Chun-Hung Pao; Jia-Lin Chen; Shih-Feng Su; Yu-Ching Huang; Wen-Hsin Huang; Chien-Hung Kuo (Journal of Marine Science and Engineering, 2021)
The mechanisms that control estuarine sediment transport are complicated due to the interaction between riverine flows, tidal currents, waves, and wave-driven currents. In the past decade, severe seabed erosion and shoreline retreat along the sandy coast of western Taiwan have raised concerns regarding the sustainability of coastal structures. In this study, ADCPs (Acoustic Doppler Current Profiler) and turbidity meters were deployed at the mouth of the Zengwen river to obtain the time series and the spatial distribution of flow velocities and turbidity during the base flow and flood conditions. A nearshore circulation model, SHORECIRC, has been adapted into a hybrid finite-difference/finite-volume, TVD (Total Variation Diminishing)-type scheme and coupled with the wave-spectrum model Simulating Waves Nearshore (SWAN). Conventional finite-difference schemes often produce unphysical oscillations when modeling coastal processes with abrupt bathymetric changes at river mouths. In contrast, the TVD-type finite volume scheme allows for robust treatment of discontinuities through the shock-capturing mechanism. The model reproduces water levels, waves, currents observed at the mouth of the Zengwen River reasonably well. The simulated residual sediment transport patterns demonstrate that the transport process at the river mouth is dominated by the interaction of the bathymetry and wave-induced currents when the riverine discharge was kept in reservoirs. The offshore residual transport causes erosion at the northern part of the river mouth, and the onshore residual transport causes accretion in the ebb tidal shoals around the center of the river mouth. The simulated morphological evolution displays significant changes on shallower deltas. The location with significant sea bed changes is consistent with the spot in which severe erosion occurred in recent years. Further analysis of morphological evolution is also discussed to identify the role of coastal structures, for example, the extension of the newly constructed groins near the river mouth.

Variations in life-history traits and statolith shape for Sepioteuthis spp. in the waters off southwestern Japan - Tzu-Yun Ching; Chih-Shin Chen; Naoki Yagishita; Atsuko Yamaguchi; Chia-Hui Wang; Kang-Ning Shen (Fisheries Science, 2021)

Continental shelf morphology controlled by bottom currents, mud diapirism, and submarine slumping to the east of the Gaoping Canyon, off SW Taiwan - Yi-Ching Yeh; Chung-Lin Tsai; Shu-Kun Hsu; Hsiao-Shan Lin; Kuan-Ting Chen; Yen-Yu Cho; Chin-Wei Liang (Geo-Marine Letters, 2021)

Disinfection efficiency of hospital infectious disease wards with chlorine dioxide and hypochlorous acid - Ming-Chun Lu; Po-Lin Chen; Da-Ji Huang; Chih-Kuo Liang; Ching-Shan Hsu; Wei-Ting Liu (Aerobiologia, 2021)

A landslide ternary diagram for geometric form and topographic site in Taiwan - Samkele Tfwala; Chia-Ling Huang; Ching-Ying Tsou; Su-Chin Chen (Landslides, 2021)

Timing of coseismic displacement grid model construction for updating the semi-kinematic reference frame: case study in Taiwan - Shih-Han Hsiao; Kuo-En Ching; Kwo-Hwa Chen; Chien-Kuan Li (Journal of Geodesy, 2021)

Molecular survey of selected viral pathogens in wild leopard cats (Prionailurus bengalensis) in Taiwan with an emphasis on the spatial and temporal dynamics of carnivore protoparvovirus 1 - Chen-Chih Chen; Ai-Mei Chang; Wan-Jhen Chen; Po-Jen Chang; Yu-Ching Lai; Hsu-Hsun Lee (Archives of Virology, 2021)

Risk of incident gastroesophageal reflux disease (GERD) in patients with sleep disorders: a population-based cohort study - Yu-Hsien Cheng; Tao-Hsin Tung; Pei-En Chen; Ching-Yao Tsai (Sleep and Biological Rhythms, 2021)

Polycyclic aromatic hydrocarbon metabolites and mortality risk in an adult population - Yuan-Yuei Chen; Tung-Wei Kao; Chung-Ching Wang; Ying-Jen Chen; Chen-Jung Wu; Ching-Huang Lai; Wei-Liang Chen (Environmental Geochemistry and Health, 2021)

A study of climate model responses of the western Pacific subtropical high to El Niño diversity - Mengyan Chen; Ting-Huai Chang; Ching-Teng Lee; Shih-Wei Fang; Jin-Yi Yu (Climate Dynamics, 2021)

Doxorubicin metabolism moderately attributes to putative toxicity in prodigiosin/doxorubicin synergism in vitro cells - Shian-Ren Lin; Chun-Shu Lin; Ching-Cheng Chen; Feng-Jen Tseng; Tsung-Jui Wu; Lebin Weng; Ching-Feng Weng (Molecular and Cellular Biochemistry, 2020)
Doxorubicin (Dox) is a widely neoplasm chemotherapeutic drug with high incidences of cardiotoxicity. Prodigiosin (PG), a red bacterial pigment from Serratia marcescens , has been demonstrated to potentiate Dox’s cytotoxicity against oral squamous cell carcinoma cells through elevating Dox influx and identified as a Dox enhancer via PG-induced autophagy; however, toxicity of normal cell remains unclear. This study is conducted to evaluate putative cytotoxicity features of PG/Dox synergism in the liver, kidney, and heart cells and further elucidate whether PG augmented Dox’s effect via modulating Dox metabolism in normal cells. Murine hepatocytes FL83B, cardio-myoblast h9c2, and human kidney epithelial cells HK-2 were sequentially treated with PG and Dox by measuring cell viability, cell death characteristics, oxidative stress, Dox flux, and Dox metabolism. PG could slightly significant increase Dox cytotoxicity in all tested normal cells whose toxic alteration was less than that of oral squamous carcinoma cells. The augmentation of Dox cytotoxicity might be attributed to the increase of Dox-mediated ROS accumulation that might cause slight reduction of Dox influx and reduction of Dox metabolism. It was noteworthy to notice that sustained cytotoxicity appeared in normal cells after PG and Dox were removed. Taken together, moderately metabolic reduction of Dox might be ascribed to the mechanism of increase Dox cytotoxicity in PG-induced normal cells; nevertheless, the determination of PG/Dox dose with sustained cytotoxicity in normal cells needs to be comprehensively considered.

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Overexpression of a multifunctional β-glucosidase gene from thermophilic archaeon Sulfolobus solfataricus in transgenic tobacco could facilitate glucose release and its use as a reporter - Chih-Hao Huang; Tzu-Ling Huang; Yu-Chang Liu; Ting-Chieh Chen; Shih-Ming Lin; Shyh-Yu Shaw; Ching-Chun Chang (Transgenic Research, 2020)

A memory optimization method combined with adaptive time-step method for cardiac cell simulation based on multi-GPU - Ching-Hsing Luo; Haiyi Ye; Xingji Chen (Medical & Biological Engineering & Computing, 2020)

Low-pass genome sequencing: a validated method in clinical cytogenetics - Matthew Hoi Kin Chau; Huilin Wang; Yunli Lai; Yanyan Zhang; Fuben Xu; Yanqing Tang; Yanfang Wang; Zihan Chen; Tak Yeung Leung; Jacqueline Pui Wah Chung; Yvonne K. Kwok; Shuk Ching Chong; et al. (Human Genetics, 2020)

A new macrocyclic diterpenoid from Anisomeles indica - Chen-Liang Chao; Hui-Chi Huang; Hsiou-Yu Ding; Jenn-Haung Lai; Hang-Ching Lin; Wen-Liang Chang (Natural Product Research, 2020)

A field pilot-scale study on heavy metal-contaminated soil washing by using an environmentally friendly agent—poly-γ-glutamic acid (γ-PGA) - Yen-Ping Peng; Yu-Chen Chang; Ku-Fan Chen; Ching-Hsiang Wang (Environmental Science and Pollution Research, 2020)

Optimization of bund wall height and trigger depth for re‐irrigation in paddy field by deepwater ponding irrigation treatment - Chien‐Lin Huang; Hau‐Lieh Huang; Nien‐Sheng Hsu; Ching‐Wen Chen (Irrigation and Drainage, 2020)
This study develops two models and an algorithm to determine the optimal bund wall height of the paddy field and the trigger depth for re‐irrigation, considering the benefits and costs of the transformation from shallow intermittent irrigation treatment to deepwater ponding irrigation. The models and algorithms are composed of: (i) a hydrologic model for ponding depth simulation in a paddy field; (ii) an optimization model for height design and depth determination in deepwater ponding irrigation; (iii) a real‐coded genetic algorithm for solving the optimization model. The results show that the optimal bund wall height of the paddy field is 27.7 cm and the optimal discount ratio of re‐irrigation depth (i.e. trigger depth divided by the upper limit of ponding depth) is 0.008 in Taiwan, with a unit net benefit of US$18 500 ha¯¹. During the first crop‐growing season (January to May) and the second (June to October), the benefit of groundwater recharge, flood mitigation, saved irrigation quantity and income of paddy rice of deepwater ponding irrigation is increased by 73, 13, 53 and 25% than those of shallow intermittent irrigation treatment, respectively. Furthermore, the total benefit of the second season is 16% better than that of the first. © 2020 John Wiley & Sons, Ltd.

Dissolved and Particulate Primary Production and Subsequent Bacterial C Consumption in the Southern East China Sea - Tzong-Yueh Chen; Chao-Chen Lai; Fuh-Kwo Shiah; Gwo-Ching Gong (Frontiers in Marine Science, 2020)

Combination of “generalized Trotter operator splitting” and “quadratic adaptive algorithm” method for tradeoff among speedup, stability, and accuracy in the Markov chain model of sodium ion channels in the ventricular cell model - Xing-Ji Chen; Ching-Hsing Luo; Min-Hung Chen (Medical & Biological Engineering & Computing, 2020)

New gravimetric-only and hybrid geoid models of Taiwan for height modernisation, cross-island datum connection and airborne LiDAR mapping - Cheinway Hwang; Hung-Jui Hsu; W. E. Featherstone; Ching-Chung Cheng; Ming Yang; Wenhsuan Huang; Chong-You Wang; Jiu-Fu Huang; Kwo-Hwa Chen; Chi-Hsun Huang; Hechin Chen; Wen-Yi Su (Journal of Geodesy, 2020)

Two new diprenylated flavanones from Derris laxiflora Benth - Hui-Chi Huang; Shih-Chang Chien; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Hsi-Lin Chiu; Yueh-Hsiung Kuo (Natural Product Research, 2020)

New land use regression model to estimate atmospheric temperature and heat island intensity in Taiwan - Chin-Yu Hsu; Uen-Ching Ng; Chiao-Ying Chen; Yu-Cheng Chen; Mu-Jean Chen; Nai-Tzu Chen; Shih-Chun Candice Lung; Huey-Jen Su; Chih-Da Wu (Theoretical and Applied Climatology, 2020)

Fungi from the black cutworm Agrotis ipsilon oral secretions mediate plant–insect interactions - Xuewei Chen; Michelle Peiffer; Ching-Wen Tan; Gary W. Felton (Arthropod-Plant Interactions, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Distribution and genetic variability of young-of-the-year greater amberjack (Seriola dumerili) in the East China Sea - Takamasa Hasegawa; Ching-Ping Lu; Sheng-Tai Hsiao; Tsubasa Uchino; Hsin-Ming Yeh; Wei-Chuan Chiang; June-Ru Chen; Chiyuki Sassa; Kazuyoshi Komeyama; Ryo Kawabe; Takashi Sakamoto; Satoshi Masumi; et al. (Environmental Biology of Fishes, 2020)
We examined the distribution and genetic variability of the greater amberjack Seriola dumerili in the East China Sea (ECS) from the mitochondrial DNA (mtDNA) control region of young-of-the-year (YOY) individuals, which may reflect the genetic characteristics of the spawning population. In the years 2016 and 2017, a total of 165 YOY S. dumerili were collected from two different locations in the ECS: the southern part of the ECS, and western Japanese coast. The spawning period was estimated using otolith daily increments from a total of 67 larvae and juveniles collected in the ECS. Results from size and age distribution indicated that S. dumerili spawned near the shelf break region in the southern ECS from January to April. Phylogenetic analysis based on mtDNA sequence data showed no significant genetic differentiation among samples collected from different locations, implying S. dumerili in the ECS is mainly composed of one population. S. dumerili around the Japanese coast may be originated from the southern ECS.

Short-Term Variability of Biological Production and CO2 System Around Dongsha Atoll of the Northern South China Sea: Impact of Topography-Flow Interaction - Jen-Hua Tai; Wen-Chen Chou; Chin-Chang Hung; Kuan-Chieh Wu; Ying-Hsuan Chen; Tzong-Yueh Chen; Gwo-Ching Gong; Fuh-Kwo Shiah; Chun Hoe Chow (Frontiers in Marine Science, 2020)

Expression and characterization of a thermostable l-aminoacylase in transgenic rice - Parawee Kanjanaphachoat; I-Wen Wang; Kun-Ting Hsieh; Ching-Shan Tseng; Liang-Jwu Chen (Journal of Plant Biochemistry and Biotechnology, 2020)

Statistical Analysis on Heart Rate Variability for Graded Cardiopulmonary Groups with Different Exercise Intensities - Ching-Kun Chen; Shyan-Lung Lin; Cheng-Yi Huang; Tasi-Chu Wang; Ting-Yen Yao; Chieh-Liang Wu (Journal of Medical and Biological Engineering, 2020)

Correction to: Pro-arrhythmogenic Effects of the V141M KCNQ1 Mutation in Short QT Syndrome and Its Potential Therapeutic Targets: Insights from Modeling - Hsiang-Chun Lee; Yoram Rudy; Hongwu Liang; Chih-Chieh Chen; Ching-Hsing Luo; Sheng-Hsiung Sheu; Jianmin Cui (Journal of Medical and Biological Engineering, 2020)

Acute physiological responses to combined blood flow restriction and low-level laser - Yi-Ching Chen; Yu-Han Su; Yen-Ting Lin; Chien-Chun Huang; Ing-Shiou Hwang (European Journal of Applied Physiology, 2020)

Fatigue-related modulation of low-frequency common drive to motor units - Ing-Shiou Hwang; Yen-Ting Lin; Chien-Chun Huang; Yi-Ching Chen (European Journal of Applied Physiology, 2020)

Prior Antiplatelet Therapy, Excluding Phosphodiesterase Inhibitor Is Associated with Poor Outcome in Patients with Spontaneous Intracerebral Haemorrhage - Zhuo-Hao Liu; Chi-Hung Liu; Po-Hsun Tu; Ping K. Yip; Ching-Chang Chen; Yu-Chi Wang; Nan-Yu Chen; Yu-Sheng Lin (Translational Stroke Research, 2020)

Integrating Patient-Specific Electrocardiogram Signals and Image-Based Computational Fluid Dynamics Method to Analyze Coronary Blood Flow in Patients during Cardiac Arrhythmias - Szu-Hsien Chou; Kuan-Yu Lin; Zhen-Ye Chen; Chun-Jung Juan; Chien-Yi Ho; Tzu-Ching Shih (Journal of Medical and Biological Engineering, 2020)
Purpose The aim of this study was to use the computational fluid dynamics (CFD) method, patient-specific electrocardiogram (ECG) signals, and computed tomography three-dimensional image reconstruction technique to investigate the blood flow in coronary arteries during cardiac arrhythmia. Methods Two patients with premature ventricular contraction-type cardiac arrhythmia and one with atrial fibrillation-type cardiac arrhythmia were investigated. The inlet velocity of the coronary artery in simulation was applied with the measured velocity profile of the left ventricular outflow tract (LVOT) from the Doppler echocardiography. The measured patient central aortic blood pressure waveform was employed for the coronary artery outlet in simulation. The no-slip boundary condition was applied to the arterial wall. Results For the patient with irregular cardiac rhythms (Case I), the coronary blood flow rate under the shortened and lengthened cardiac rhythms were 0.66 and 0.96 mL/s, respectively. In Case II, the maximum velocity at the LVOT under a normal heartbeat was found to be 101 cm/s, whereas the average value was 73 cm/s. In Case III, the patient was also diagnosed with a congenital stenosis problem at the myocardial bridge (MCB) at the LAD. The measured blood flow rate at the MCB of the LAD for the three heartbeats in Case III was found to be 0.68, 1.08, and 1.14 mL/s. Conclusion The integration of patient-specific ECG signals and image-based CFD methods can clearly analyze hemodynamic information for patients during cardiac arrhythmia. The cardiac arrhythmia can reduce the blood flow in the coronary arteries.

Biomechanical Comparison of Lumbar Motion Unit Stability Following Posterior Instrumentation with Facet Spacers and Facet Screws - Mu-Yi Liu; Tsung-Ting Tsai; Lih-Huei Chen; Wen-Huang Liang; Po-Liang Lai; Ching-Lung Tai (Journal of Medical and Biological Engineering, 2020)
Purpose Lumbar posterior instrumentation for facet stabilization has become popular for the treatment of lumbar instability. The present study investigated and compared facet stabilization following lumbar posterior instrumentation with facet spacers and facet screws using porcine lumbar spines. Methods Eighteen L5–L6 lumbar motion units (LMUs) of the porcine spines were randomly divided into three groups (un-instrumented, facet-spacer and facet-screw). In the un-instrumented group (control), all ligamentous structures were preserved. In the facet-spacer group, two facet spacers were inserted into the joint spaces of the bilateral upper and lower facets. In the facet-screw group, two cannulated screws were used to transfix the bilateral upper and lower facets. With the use of a material testing machine, a gradually increasing moment of up to 6000 N-mm was generated in flexion, extension, lateral bending and torsion motions to compare facet stabilization among the groups. Results The facet-spacer group was significantly stiffer than the facet-screw group in extension ( p = 0.013), whereas the facet-screw group was significantly stiffer than the facet-spacer group in axial rotation ( p = 0.004). No statistically significant differences were observed between the two fixation techniques in flexion ( p = 0.284) and lateral bending ( p = 0.085). Conclusion Both facet-spacer and facet-screw fixation techniques significantly improve stability in a single LMU. Facet-spacer fixation provided better stabilization in extension, while facet-screw fixation provided better stabilization in axial rotation.

Population Structure of the World Vegetable Center Mungbean Mini Core Collection and Genome-Wide Association Mapping of Loci Associated with Variation of Seed Coat Luster - Caleb Manamik Breria; Ching Hsiang Hsieh; Jo-Yi Yen; Ramakrishnan Nair; Chen-Yu Lin; Shu-Mei Huang; Thomas J. Noble; Roland Schafleitner (Tropical Plant Biology, 2020)

Twist1 Plays an Anti-apoptotic Role in Mutant Huntingtin Expression Striatal Progenitor Cells - Wei-Ping Jen; Hui-Mei Chen; Yow-Sien Lin; Yijuang Chern; Yi-Ching Lee (Molecular Neurobiology, 2020)

Construction of a single nucleotide polymorphism marker based QTL map and validation of resistance loci to bacterial wilt caused by Ralstonia solanacearum species complex in tomato - Il Sheob Shin; Jung-Ching Hsu; Shu-Mei Huang; Jaw-Rong Chen; Jaw-Fen Wang; Peter Hanson; Roland Schafleitner (Euphytica, 2020)
Bacterial wilt (BW), caused by Ralstonia solanacearum species complex is one of the major biotic factors limiting tomato production in the humid tropics. Pyramiding of resistance genes through marker-assisted selection is an efficient way to develop durable BW resistant cultivars. Tomato line ‘Hawaii 7996’ (H7996) is a stable and robust resistance source against various strains of the species complex. Major BW resistance quantitative trait loci (QTLs) Bwr - 12 and Bwr - 6 , and several minor or strain specific QTLs have been coarse-mapped in this line, but none has been fine-mapped and validated. The objective of the current study was to construct a high density genetic map using single-nucleotide polymorphism (SNP) markers derived from genotyping-by-sequencing, fine-map Bwr - 12 and Bwr - 6 and determine the effects of these QTLs using a near isogenic line (NIL) population. A high density genetic map using 1604 SNP markers with an average distance of 0.82 cM was developed for 188 F 9 recombinant inbred lines derived from the cross H7996 × WVa700. A total of seven QTLs associated with BW resistance to race 1-phylotype I ( R. pseudosolanacearum ) or/and race 3-phylotype II ( R. solanacearum ) strains were located on chromosomes 6 ( Bwr - 6.1 , 6.2 , 6.3 and 6.4 ) and 12 ( Bwr - 12.1 , Bwr - 12.2 and Bwr - 12.3 ) with logarithm of odds (LOD) scores of 6.2–15.6 and 6.2–31.1, explaining 14.2–33.4% and 15.9–53.9% of the total phenotypic variation contributed from H7996, respectively. To validate the genetic effects of the two QTL regions, a set of 80 BC 3 F 3 NILs containing different sections of Bwr -6 with or without Bwr -12 was phenotyped for disease severity after challenge with either race 1-phylotype I Pss4 or race 3-phylotype II Pss1632 BW strains over two seasons. Bwr -6.1 specific to Pss4 and Bwr -6.3 specific to Pss1632 were mapped to an interval of 5.0 cM ( P < 0.05) between 6_33,444,000_SLM6-47 and 6_33,868,000_SLM6-124 SNP marker, and to 2.7 cM ( P < 0.01) between positions 6_35,949,000 _SLM6-107 to 6_36,750,000_SLM6-82 marker, respectively. In addition, the specific effect of Bwr -12 for resistance to Pss4 (LOD score of 5.8-16.1, P < 0.01) was confirmed.

Seasonal Variations of Marine Environment and Primary Production in the Taiwan Strait - Hsiao-Chun Tseng; Wan-Lynn You; Wei Huang; Chih-Ching Chung; An-Yi Tsai; Tzong-Yueh Chen; Kuo-Wei Lan; Gwo-Ching Gong (Frontiers in Marine Science, 2020)

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

Comparative Study of Regulations of Devices for Aesthetic Purposes: US, European Union, China, and Taiwan - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2020)

Pulse Oximetry Monitor Feasible for Early Screening of Obstructive Sleep Apnea (OSA) - Huei-Chen Lin; Chien-Ling Su; Jun-Hui Ong; kun-ling Tsai; Yu-Wen Chen; Cheng-Yu Lin; Ling-Ling Chiang; Ching-Hsia Hung (Journal of Medical and Biological Engineering, 2020)

The relationship between lead and cadmium levels and functional dependence among elderly participants - Yuan-Yuei Chen; Chung-Ching Wang; Tung-Wei Kao; Chen-Jung Wu; Ying-Jen Chen; Ching-Huang Lai; Yi-Chao Zhou; Wei-Liang Chen (Environmental Science and Pollution Research, 2020)

Cold treatment for guava fruits infested with oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae) - Kao W. Lin; Huey L. Lin; Ching C. Shiesh; Yu. L. Hsu; Chih. H. Lin; Su. C. Chen; Wen B. Yeh (Applied Entomology and Zoology, 2020)

Resource availability affects temporal variation of phytoplankton size structure in the Kuroshio east of Taiwan - Fan‐Sian Lin; Pei‐Chi Ho; Akash R. Sastri; Chung‐Chi Chen; Gwo‐Ching Gong; Sen Jan; Chih‐hao Hsieh (Limnology and Oceanography, 2020)
The on‐going discussion concerning how environmental factors determine phytoplankton size structure has centered around two hypotheses: (H1) The resource‐size relationship predicts that normalized biovolume size spectrum (NBSS) slopes for phytoplankton are progressively shallower with increasing resource availability and (H2) The temperature‐size relationship predicts that phytoplankton NBSS slopes steepen with increasing water temperature. To test these hypotheses, we examined 72 phytoplankton assemblage collections in the Kuroshio east of Taiwan. Total phytoplankton biomass was used as a proxy for resource availability instead of nutrients because nutrients are depleted and do not represent resource availability for oligotrophic seas. We found no significant relationship between NBSS slopes with temperature, providing little support for the temperature‐size rule. In contrast, a positive relationship between NBSS slopes and total biomass for most of the year lends general support to the resource‐size relationship, except during the winter and early spring. To explain this exception, we hypothesize that resource pulses occurring during the cold seasons are used more efficiently by small cells and promote faster growth of small relative to large phytoplankton because these pulses take place after a long period of resource depletion in oligotrophic seas; thus, the NBSS slopes become much steeper than would be expected from a positive resource‐size relationship. This deviation can be considered as nonsteady state in terms of phytoplankton size structure relative to resources. Nevertheless, we cannot rule out the possibility that grazing effects also play an important role in controlling phytoplankton size structure.

Urinary biomarkers of polycyclic aromatic hydrocarbons and the association with hearing threshold shifts in the United States adults - Cheng-Wai Chou; Yuan-Yuei Chen; Chung-Ching Wang; Tung-Wei Kao; Chen-Jung Wu; Ying-Jen Chen; Yi-Chao Zhou; Wei-Liang Chen (Environmental Science and Pollution Research, 2020)

A multidecadal change analysis for irrigation ponds in Taoyuan, Taiwan, using multisource data - Yen-Ching Chen; Wei-Chun Lin; Lin-Hsuan Hsiao; Ke-Sheng Cheng (Paddy and Water Environment, 2020)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

In vitro activities of imipenem, vancomycin, and rifampicin against clinical Elizabethkingia species producing BlaB and GOB metallo-beta-lactamases - Tein-Yao Chang; Hsing-Yu Chen; Yu-Ching Chou; Yun-Hsiang Cheng; Jun-Ren Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

An integrative assessment to determine the sediment toxicity of Kaohsiung Harbor in Taiwan: combining chemical analysis and cytotoxicity assay - Yun-Ru Ju; Chih-Feng Chen; Chiu-Wen Chen; Mei-Ling Tsai; Jia-Ching Wu; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Tropical cyclone sensitivities to CO2 doubling: roles of atmospheric resolution, synoptic variability and background climate changes - Gabriel A. Vecchi; Thomas L. Delworth; Hiroyuki Murakami; Seth D. Underwood; Andrew T. Wittenberg; Fanrong Zeng; Wei Zhang; Jane W. Baldwin; Kieran T. Bhatia; William Cooke; Jie He; Sarah B. Kapnick; et al. (Climate Dynamics, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Contrasting forms of competition set elevational range limits of species - Shih‐Fan Chan; Wei‐Kai Shih; An‐Yu Chang; Sheng‐Feng Shen; I‐Ching Chen (Ecology Letters, 2019)
How abiotic and biotic factors constrain distribution limits at the harsh and benign edges of species ranges is hotly debated, partly because macroecological experiments testing the proximate causes of distribution limits are scarce. It has long been recognized – at least since Darwin’s On the Origin of Species – that a harsh climate strengthens competition and thus sets species range limits. Using thorough field manipulations along a large elevation gradient, we show the mechanisms by which temperature determines competition type, resulting in a transition from interference to exploitative competition from the lower to the upper elevation limits in burying beetles ( Nicrophorus nepalensis ). This transition is an example of Darwin’s classic hypothesis that benign climates favor direct competition for highly accessible resources while harsh climates result in competition through resources of high rivalry. We propose that identifying the properties of these key resources will provide a more predictive framework to understand the interplay between biotic and abiotic factors in determining geographic range limits.

The Combined Use of Groundwater Quality, Drawdown Index and Land Use to Establish a Multi-Purpose Groundwater Utilization Plan - Ching-Ping Liang; Wen-Shuo Hsu; Yi-Chi Chien; Sheng-Wei Wang; Jui-Sheng Chen (Water Resources Management, 2019)

The ongoing modernization of the Taiwan semi-dynamic datum based on the surface horizontal deformation model using GNSS data from 2000 to 2016 - Chien-Kuan Li; Kuo-En Ching; Kwo-Hwa Chen (Journal of Geodesy, 2019)

Spatial Assessment of Climate Risk for Investigating Climate Adaptation Strategies by Evaluating Spatial-Temporal Variability of Extreme Precipitation - Bing-Chen Jhong; Jung Huang; Ching-Pin Tung (Water Resources Management, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

Progressive multifocal leukoencephalopathy in a renal transplant patient - Tsu-Chen Lin; Mei-Yi Wu; Hui-Tzung Luh; Shiou-Fu Lin; Chien-Min Lin; Ying-Chi Tseng; Yung-Ching Liu; Mai-Szu Wu (Journal of NeuroVirology, 2019)

Therapeutic potential of AAV9-S15D-RLC gene delivery in humanized MYL2 mouse model of HCM - Sunil Yadav; Chen-Ching Yuan; Katarzyna Kazmierczak; Jingsheng Liang; Wenrui Huang; Lauro M. Takeuchi; Rosemeire M. Kanashiro-Takeuchi; Danuta Szczesna-Cordary (Journal of Molecular Medicine, 2019)

Blood and seminal plasma mercury levels and predatory fish intake in relation to low semen quality - Chin-En Ai; Ching-Jen Li; Ming-Chien Tsou; Jun-Lin Chen; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Science and Pollution Research, 2019)

The influence of tourism-based provisioning on fish behavior and benthic composition - Colin K. C. Wen; Kao-Sung Chen; Wei-Chen Tung; Anyo Chao; Ching-Wei Wang; Shao-Lun Liu; Ming-Jay Ho (Ambio, 2019)

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Combination of “quadratic adaptive algorithm” and “hybrid operator splitting” or uniformization algorithms for stability against acceleration in the Markov model of sodium ion channels in the ventricular cell model - Xing-Ji Chen; Ching-Hsing Luo; Min-Hung Chen; Xiang Zhou (Medical & Biological Engineering & Computing, 2019)

Effects of Copper on Root Morphology, Cations Accumulation, and Oxidative Stress of Grapevine Seedlings - Kai-Wei Juang; Yu-Ching Lo; Tzu-Hsuan Chen; Bo-Ching Chen (Bulletin of Environmental Contamination and Toxicology, 2019)

Stable isotope analysis reveals ontogenetic feeding shifts in Pacific blue marlin ( Makaira nigricans ) off eastern Taiwan - Ching‐Tsun Chang; Wei‐Chuan Chiang; Yun‐Chen Chang; Michael K. Musyl; Chi‐Lu Sun; Daniel J. Madigan; Aaron B. Carlisle; Hung‐Hung Hsu; Qi‐Xuan Chang; Nan‐Jay Su; Yuan‐Shing Ho; Chen‐Te Tseng (Journal of Fish Biology, 2019)
To gain a better understanding of the trophic ecology of Pacific blue marlin Makaira nigricans off eastern Taiwan, nitrogen and carbon stable isotopes (δ 15 N and δ 13 C) and Bayesian mixing models were used to explore trophic dynamics and potential ontogenetic feeding shifts across M. nigricans of different size classes. Makaira nigricans samples from east of Taiwan ( n = 213) and Palau ( n = 37), as well as their prey ( n = 70), were collected during 2012 and 2013. Results indicated increases in δ 15 N with size, with values of larger size classes (> 200 cm eye‐to‐fork length; L EF ) significantly higher than those L EF . Values of δ 13 C were negatively correlated with size. Makaira nigricans > 200 cm L EF had the highest estimated trophic position (4.44) and also exhibited ontogenetic changes in trophic position. Large M. nigricans fed more on dolphinfish Coryphaena hippurus and hairtail Trichiurus lepturus , while smaller M. nigricans consumed smaller forage fish ( e.g ., moonfish Mene maculata ) and cephalopods. These changes may relate to greater swimming speeds and vertical habitat use in larger M. nigricans , allowing capture and consumption of larger prey items at higher trophic positions. The high trophic level of M. nigricans east of Taiwan confirms its important role as an apex predator in marine food webs and how ecological role changes with size.

Spatial and temporal variations in species diversity of fish assemblages near a sewage treatment plant in northern Taiwan - Hungyen Chen; Ching-Yi Chen; Kwang-Tsao Shao; Gwo-Ching Gong (Fisheries Science, 2019)

Magnesium sulfate inhibits binding of lipopolysaccharide to THP-1 cells by reducing expression of cluster of differentiation 14 - Ya-Ying Chang; Tzu-Yu Lin; Ming-Chang Kao; Tsung-Ying Chen; Ching-Feng Cheng; Chih-Shung Wong; Chun-Jen Huang (Inflammopharmacology, 2019)

Exposure to polycyclic aromatic hydrocarbons and risk of disability among an elderly population - Yuan-Yuei Chen; Tung-Wei Kao; Chung-Ching Wang; Ying-Jen Chen; Chen-Jung Wu; Ching-Huang Lai; Wei-Liang Chen (Environmental Science and Pollution Research, 2019)

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

Source model and Coulomb stress change of the 2015 Mw 7.8 Gorkha earthquake determined from improved inversion of geodetic surface deformation observations - Yinghui Yang; Qiang Chen; Qian Xu; Guoxiang Liu; Jyr-Ching Hu (Journal of Geodesy, 2019)

Whole-genome sequencing data-based modeling for the investigation of an outbreak of community-associated methicillin-resistant Staphylococcus aureus in a neonatal intensive care unit in Hong Kong - Vincent C. C. Cheng; Shuk-Ching Wong; Huiluo Cao; Jonathan H. K. Chen; Simon Y. C. So; Sally C. Y. Wong; Siddharth Sridhar; Kwok-Yung Yuen; Pak-Leung Ho (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Fundamentals of Pharmacokinetics to Assess the Correlation Between Plasma Drug Concentrations and Different Blood Sampling Methods - Wei-Ching Chen; Pei-Wei Huang; Wan-Ling Yang; Yen-Lun Chen; Ying-Ning Shih; Hong-Jaan Wang (Pharmaceutical Research, 2019)

Effects of a Web-based Health Education Program on Quality of Life and Symptom Distress of Initially Diagnosed Advanced Non-Small Cell Lung Cancer Patients: A Randomized Controlled Trial - Chi-Chin Huang; Han-Pin Kuo; Yueh-E Lin; Shu-Ching Chen (Journal of Cancer Education, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Id1 and Sonic Hedgehog Mediate Cell Cycle Reentry and Apoptosis Induced by Amyloid Beta-Peptide in Post-mitotic Cortical Neurons - A-Ching Chao; Chien-Hui Chen; Shih-Hsin Chang; Chao-Tzu Huang; Wei-Chao Hwang; Ding-I Yang (Molecular Neurobiology, 2019)

Spatial dynamic assessment of health risks for urban river cruises - Cheng-Shin Jang; Ching-Ping Liang; Shih-Kai Chen (Environmental Monitoring and Assessment, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Pre-treatment with angiotensin-(1–7) inhibits tumor growth via autophagy by downregulating PI3K/Akt/mTOR signaling in human nasopharyngeal carcinoma xenografts - Yu-Tsai Lin; Hung-Chen Wang; Hui-Ching Chuang; Yi-Chiang Hsu; Ming-Yu Yang; Chih-Yen Chien (Journal of Molecular Medicine, 2018)

Asian dust storms and diabetes hospitalization: a nationwide population-based study - Yun-Shan Chan; Joshua Chen-Yuan Teng; Tsai-Ching Liu; Yu-I Peng (Air Quality, Atmosphere & Health, 2018)

Response to Qian et al. (2017): Daily and seasonal climate variations are both critical in the evolution of species’ elevational range size - Wei‐Ping Chan; I‐Ching Chen; Robert K. Colwell; Wei‐Chung Liu; Cho‐ying Huang; Sheng‐Feng Shen (Journal of Biogeography, 2018)
In their recent critique, Qian et al. stated that the results of structural equation modeling analysis ( SEM ) in Chan et al. were flawed. Here, we show that the source of the difference, in their reanalysis, is that Qian et al. did not follow the standard, iterative strategy of SEM , which allows researchers to evaluate which model offers the best account of the data in both absolute and relative terms. Here, we provide step‐by‐step instructions to reproduce our published results. We address—and aim to resolve—Qian et al.'s concerns regarding SEM . Moreover, in our original paper, we used three distinct statistical methods—hierarchical partitioning, SEM and stationary bootstrap—to show that different temporal scales of environmental variability differentially impact the elevational range size ( ERS ) of species. We believe it is time to move on to probing the pressing issue of how and why climatic variability impacts ERS .

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Analysis of the Aso-Bridge landslide during the 2016 Kumamoto earthquakes in Japan - Ching Hung; Guan-Wei Lin; Huei-Sian Syu; Chi-Wen Chen; Hsin-Yi Yen (Bulletin of Engineering Geology and the Environment, 2018)

Evaluating Future Joint Probability of Precipitation Extremes with a Copula-Based Assessing Approach in Climate Change - Bing-Chen Jhong; Ching-Pin Tung (Water Resources Management, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Unexpected dose response of HaCaT to UVB irradiation - Rong-Shing Chang; Chi-Shuo Chen; Ching-Lung Huang; Chiu-Ting Chang; Yujia Cui; Wei-Ju Chung; Wun-Yi Shu; Chi-Shiun Chiang; Chun-Yu Chuang; Ian C. Hsu (In Vitro Cellular & Developmental Biology - Animal, 2018)

Molecular cloning and characterization of proliferating cell nuclear antigen; its potential involvement in germ cell development of stony corals - Shinya Shikina; Yi-Ling Chiu; Man-ru Ye; Jack-I-Chen Yao; Yi-Jou Chung; Chieh-Jhen Chen; Ching-Fong Chang (Fisheries Science, 2018)

Effects of normoxic and hypoxic exercise training on the bactericidal capacity and subsequent apoptosis of neutrophils in sedentary men - Yi-Ching Chen; Wan-Yu Chou; Tieh-Cheng Fu; Jong-Shyan Wang (European Journal of Applied Physiology, 2018)

M/g-C3N4 (M=Ag, Au, and Pd) composite: synthesis via sunlight photodeposition and application towards the degradation of bisphenol A - Chen Hong Hak; Lan Ching Sim; Kah Hon Leong; Ping Feng Lim; Yik Heng Chin; Pichiah Saravanan (Environmental Science and Pollution Research, 2018)

Occurrence of Emerging Contaminants in Aquaculture Waters: Cross-Contamination between Aquaculture Systems and Surrounding Waters - Webber Wei-Po Lai; Yen-Ching Lin; Yu-Hsiang Wang; Yue Leon Guo; Angela Yu-Chen Lin (Water, Air, & Soil Pollution, 2018)

Application of physiographic soil erosion–deposition model in estimating sediment flushing efficiency of empty storage - Ching-Nuo Chen (Journal of Earth System Science, 2018)

Improvement of indoor air quality in pet shop using gaseous chlorine dioxide - Ming-Chun Lu; Da-Ji Huang; Ching-Shan Hsu; Chih-Kuo Liang; Geng-Min Chen (Environmental Monitoring and Assessment, 2018)

Lamelloplasts and minichloroplasts in Begoniaceae: iridescence and photosynthetic functioning - Shang-Hung Pao; Ping-Yun Tsai; Ching-I Peng; Pei-Ju Chen; Chi-Chu Tsai; En-Cheng Yang; Ming-Chih Shih; Jiannyeu Chen; Jun-Yi Yang; Peter Chesson; Chiou-Rong Sheue (Journal of Plant Research, 2018)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

Catechol-O-Methyltransferase Val158Met Polymorphism on Striatum Structural Covariance Networks in Alzheimer’s Disease - Chiung-Chih Chang; Shih-Jen Tsai; Nai-Ching Chen; Chi-Wei Huang; Shih-Wei Hsu; Ya-Ting Chang; Mu-En Liu; Wen-Neng Chang; Wan-Chen Tsai; Chen-Chang Lee (Molecular Neurobiology, 2018)

Prototype Deep Brain Stimulation System with Closed-Loop Control Feedback for Modulating Bladder Functions in Traumatic Brain Injured Animals - En Jen; Chii-Wann Lin; Tsung-Hsun Hsieh; Yi-Chun Chiu; Tsung-Che Lu; Shih-Ching Chen; Meng-Chao Chen; Chih-Wei Peng (Journal of Medical and Biological Engineering, 2018)

Protein-bounded uremic toxin p-cresylsulfate induces vascular permeability alternations - Wei-Hua Tang; Chao-Ping Wang; Teng-Hung Yu; Pei-Yang Tai; Shih-Shin Liang; Wei-Chin Hung; Cheng-Ching Wu; Sung-Hao Huang; Yau-Jiunn Lee; Shih-Chieh Chen (Histochemistry and Cell Biology, 2018)

Improving the management of Taiwanese fishery resource conservation zones based on public perceptions and willingness to pay for ecosystem services - Jyun-Long Chen; Yu-Sheng Lin; Ching-Ta Chuang (Journal of Coastal Conservation, 2018)

Epirubicin induces apoptosis in osteoblasts through death-receptor and mitochondrial pathways - Tzu-Ching Huang; Pu-Rong Chiu; Wen-Tsan Chang; Bau-Shan Hsieh; Yu-Ci Huang; Hsiao-Ling Cheng; Li-Wen Huang; Yu-Chen Hu; Kee-Lung Chang (Apoptosis, 2018)

Finite Element Analysis of Tongue Type Calcaneal Fracture with Open Reduction and Internal Fixation with Locking Plate - Ching-Hsuan Chen; Yu-Hsuan Huang; Chinghua Hung; Chen-Sheng Chen; Chao-Ching Chiang (Journal of Medical and Biological Engineering, 2018)

The persistence and photostabilizing characteristics of benzotriazole and 5-methyl-1H-benzotriazole reduce the photochemical behavior of common photosensitizers and organic compounds in aqueous environments - Kenneth Hsien-Yung Chung; Yen-Ching Lin; Angela Yu-Chen Lin (Environmental Science and Pollution Research, 2018)

Broad-specificity amino acid racemase, a novel non-antibiotic selectable marker for transgenic plants - Yi-Chia Kuan; Venkatesan Thiruvengadam; Jia-Shin Lin; Jia-Hsin Liu; Tsan-Jan Chen; Hsin-Mao Wu; Wen-Ching Wang; Liang-Jwu Chen (Plant Biotechnology Reports, 2018)

Photolytic degradation of ciprofloxacin in solid and aqueous environments: kinetics, phototransformation pathways, and byproducts - Yen-Ching Lin; Kuan-Wen Hsiao; Angela Yu-Chen Lin (Environmental Science and Pollution Research, 2018)

Assessing climate change adaptations for community-scale water resources using a low-frequency weather generator - Yuan-Hua Li; Ching-Pin Tung; Yuan-Hung Li; Pei-Yuan Chen (Paddy and Water Environment, 2018)

Prevalence, mechanisms and genetic relatedness of the human pathogenic fungus Aspergillus fumigatus exhibiting resistance to medical azoles in the environment of Taiwan - Hsuan‐Chen Wang; Jui‐Chang Huang; Yong‐Hong Lin; Yu‐Hsin Chen; Ming‐I Hsieh; Pui‐Ching Choi; Hsiu‐Jung Lo; Wei‐Lun Liu; Ching‐Shan Hsu; Hsin‐I Shih; Chi‐Jung Wu; Yee‐Chun Chen (Environmental Microbiology, 2018)
Summary Emerging azole resistance in Aspergillus fumigatus poses a serious threat to human health. This nationwide surveillance study investigated the prevalence and molecular characteristics of azole‐resistant A. fumigatus environmental isolates in Taiwan, an island country with increasing use of azole fungicides. Of the 2760 air and soil samples screened from 2014 to 2016, 451 A. fumigatus isolates were recovered from 266 samples and 34 isolates from 29 samples displayed resistance to medical azoles (itraconazole, voriconazole or posaconazole). The resistance prevalence was 10.9% and 7.5% in A. fumigatus ‐positive samples and isolates respectively. Most (29, 85.3%) azole‐resistant isolates harboured TR 34 /L98H mutations, which were widely distributed, clustered genetically with clinical isolates, and had growth rates that were similar to those of the wild‐type isolates. Microsatellite genotyping revealed both the global spread of the TR 34 /L98H isolates and the occurrence of TR 34 /L98H/S297T/F495I isolates belonging to local microsatellite genotypes. AfuMDR3 and atrF , two efflux transporter genes, were constitutively upregulated in two individual resistant isolates without cyp51A mutations, highlighting their potential roles in azole resistance. These results emphasize the need for periodic environmental surveillance at the molecular level in regions in which azole fungicides are applied, and agricultural fungicide management strategies that generate less selective pressure should be investigated.

Effects of normoxic and hypoxic exercise regimens on lymphocyte apoptosis induced by oxidative stress in sedentary males - Jong-Shyan Wang; Yi-Ching Chen; Wan-Ling Chen; Chin-Pu Lin (European Journal of Applied Physiology, 2017)

Unprecedented calcareous algal reefs in northern Taiwan merit high conservation priority - Ching-Yu Liou; Sung-Yin Yang; Chaolun Allen Chen (Coral Reefs, 2017)

Myristoylated alanine-rich C kinase substrate (MARCKS): a multirole signaling protein in cancers - Lon Wolf R. Fong; David C. Yang; Ching-Hsien Chen (Cancer and Metastasis Reviews, 2017)

Biomechanical evaluation of reconstruction plates with locking, nonlocking, and hybrid screws configurations in calcaneal fracture: a finite element model study - Ching-Hsuan Chen; Chinghua Hung; Yu-Chun Hsu; Chen-Sheng Chen; Chao-Ching Chiang (Medical & Biological Engineering & Computing, 2017)

Pro-arrhythmogenic Effects of the V141M KCNQ1 Mutation in Short QT Syndrome and Its Potential Therapeutic Targets: Insights from Modeling - Hsiang-Chun Lee; Yoram Rudy; Hongwu Liang; Chih-Chieh Chen; Ching-Hsing Luo; Sheng-Hsiung Sheu; Jianmin Cui (Journal of Medical and Biological Engineering, 2017)
Gain-of-function mutations in the pore-forming subunit of I Ks channels, KCNQ1, lead to short QT syndrome (SQTS) and lethal arrhythmias. However, how mutant I Ks channels cause SQTS and the possibility of I Ks -specific pharmacological treatment remain unclear. V141M KCNQ1 is a SQTS associated mutation. We studied its effect on I Ks gating properties and changes in the action potentials (AP) of human ventricular myocytes. Xenopus oocytes were used to study the gating mechanisms of expressed V141M KCNQ1/KCNE1 channels. Computational models were used to simulate human APs in endocardial, mid-myocardial, and epicardial ventricular myocytes with and without β-adrenergic stimulation. V141M KCNQ1 caused a gain-of-function in I Ks characterized by increased current density, faster activation, and slower deactivation leading to I Ks accumulation. V141M KCNQ1 also caused a leftward shift of the conductance-voltage curve compared to wild type (WT) I Ks (V 1/2 = 33.6 ± 4.0 mV for WT, and 24.0 ± 1.3 mV for heterozygous V141M). A Markov model of heterozygous V141M mutant I Ks was developed and incorporated into the O’Hara–Rudy model. Compared to the WT, AP simulations demonstrated marked rate-dependent shortening of AP duration (APD) for V141M, predicting a SQTS phenotype. Transmural electrical heterogeneity was enhanced in heterozygous V141M AP simulations, especially under β-adrenergic stimulation. Computational simulations identified specific I K1 blockade as a beneficial pharmacologic target for reducing the transmural APD heterogeneity associated with V141M KCNQ1 mutation. V141M KCNQ1 mutation shortens ventricular APs and enhances transmural APD heterogeneity under β-adrenergic stimulation. Computational simulations identified I K1 blockers as a potential antiarrhythmic drug of choice for SQTS.

A Peutz–Jeghers syndrome family associated with sinonasal adenocarcinoma: 28 years follow up report - Jy-Ming Chiang; Tse-Ching Chen (Familial Cancer, 2017)

Alleviation of N-Methyl-d-Aspartate Receptor-Dependent Long-Term Depression via Regulation of the Glycogen Synthase Kinase-3β Pathway in the Amygdala of a Valproic Acid-Induced Animal Model of Autism - Han-Fang Wu; Po See Chen; Yi-Ju Chen; Chi-Wei Lee; I-Tuan Chen; Hui-Ching Lin (Molecular Neurobiology, 2017)

Nonlinear biotic ligand model for assessing alleviation effects of Ca, Mg, and K on Cd toxicity to soybean roots - Bo-Ching Chen; Pin-Jie Wang; Pei-Chi Ho; Kai-Wei Juang (Ecotoxicology, 2017)

Tributyltin exposure at noncytotoxic doses dysregulates pancreatic β-cell function in vitro and in vivo - Ya-Wen Chen; Kuo-Cheng Lan; Jing-Ren Tsai; Te-I Weng; Ching-Yao Yang; Shing-Hwa Liu (Archives of Toxicology, 2017)

Sampling design by the core-food approach for the Taiwan total diet study on veterinary drugs - Chien-Chih Chen; Ching-Lun Tsai; Chia-Chin Chang; Shih-Pei Ni; Yi-Tzu Chen; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2017)

Anti-oxidative Responses on Hepatic Tissue of Zebrafish (Danio rerio) in a Short Duration of Sub-lethal Concentrations of Cadmium Exposure - Su Mei Wu; Li-Hsin Shu; Jia-Hao Liu; Ching Hsein Chen (Bulletin of Environmental Contamination and Toxicology, 2017)

Molecular characterization of myostatin from the skeletal muscle of the African lungfish, Protopterus annectens, and changes in its mRNA and protein expression levels during three phases of aestivation - Jasmine L. Y. Ong; You R. Chng; Biyun Ching; Xiu L. Chen; Kum C. Hiong; Wai P. Wong; Shit F. Chew; Yuen K. Ip (Journal of Comparative Physiology B, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

A novel study of artificial bee colony with clustering technique on paddy rice image classification - Shiuan Wan; Shih-Hsun Chang; Ching-Tung Peng; Yu-Keng Chen (Arabian Journal of Geosciences, 2017)

Important Roles of Ring Finger Protein 112 in Embryonic Vascular Development and Brain Functions - Jen-Hui Tsou; Ying-Chen Yang; Ping-Chieh Pao; Hui-Ching Lin; Nai-Kuei Huang; Shih-Ting Lin; Kuei-Sen Hsu; Che-Ming Yeh; Kuen-Haur Lee; Chu-Jen Kuo; De-Ming Yang; Jiann-Her Lin; et al. (Molecular Neurobiology, 2017)

p-Hydroxyacetophenone suppresses nuclear factor-κB-related inflammation in nociceptive and inflammatory animal models - Chang Ching-Wen; Chen Yun-Chieh; Lin Yu-Chin; Peng Wen-Huang (Journal of Natural Medicines, 2017)

Inhalation exposure of children to indoor PM10 and associated metals during river-dust episodes - Yi-Chen Chiang; Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Ching-Tsan Tsai; Dian-Jheng Lai; Chung-Yih Kuo (Air Quality, Atmosphere & Health, 2017)

An ENSO prediction approach based on ocean conditions and ocean–atmosphere coupling - Yu-heng Tseng; Zeng-Zhen Hu; Ruiqiang Ding; Han-ching Chen (Climate Dynamics, 2017)

Status quo of management of the human tissue banks in Taiwan - Ching-Pang Chou; Szu-Cheng Chou; Ying-Hua Chen; Yu-Hsuan Chen; Ming-Shin Lee (Cell and Tissue Banking, 2017)

Strain distribution, growth eccentricity, and tension wood distribution in the plagiotropic and orthotropic branches of Koelreuteria henryi Dummer - Li-Fen Hung; Ching-Chu Tsai; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2017)

Two MYB-related transcription factors play opposite roles in sugar signaling in Arabidopsis - Yi-Shih Chen; Yi-Chi Chao; Tzu-Wei Tseng; Chun-Kai Huang; Pei-Ching Lo; Chung-An Lu (Plant Molecular Biology, 2017)

Estimation of students’ exposure to metal concentrations from river-dust episodes during 1994–2012 - Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Yi-Chen Chiang; Ching-Tsan Tsai; Pin-Yu Lin; Dian-Jheng Lai; Chung-Yih Kuo (Environmental Science and Pollution Research, 2017)

Improved survival in patients with severe tuberculosis after exposure to fluoroquinolones - Shyh-Ren Chiang; Jiunn-Min Shieh; Chung-Hua Chen; Shu-Chen Hsing; Shih-Feng Wen; Jhi-Joung Wang; Kuo-Chen Cheng; Yin-Ching Chuang (Infectious Diseases, 2016)

Health risk assessment of groundwater arsenic pollution in southern Taiwan - Ching-Ping Liang; Sheng-Wei Wang; Yu-Hsuan Kao; Jui-Sheng Chen (Environmental Geochemistry and Health, 2016)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

Indoxyl sulfate enhances IL-1β-induced E-selectin expression in endothelial cells in acute kidney injury by the ROS/MAPKs/NFκB/AP-1 pathway - Wen-Ching Shen; Chan-Jung Liang; Tao-Ming Huang; Chen-Wei Liu; Shu-Huei Wang; Guang-Huar Young; Jaw-Shiun Tsai; Ying-Chin Tseng; Yu-Sen Peng; Vin-Cent Wu; Yuh-Lien Chen (Archives of Toxicology, 2016)

Rapid Fabrication of a Cell-Seeded Collagen Gel-Based Tubular Construct that Withstands Arterial Pressure - Ho-Yi Tuan-Mu; Po-Ching Lu; Pei-Yuan Lee; Chien-Chih Lin; Chun-Jung Chen; Lynn L.H. Huang; Jia-Horng Lin; Jin-Jia Hu (Annals of Biomedical Engineering, 2016)

Initial Drug Dissolution from Amorphous Solid Dispersions Controlled by Polymer Dissolution and Drug-Polymer Interaction - Yuejie Chen; Shujing Wang; Shan Wang; Chengyu Liu; Ching Su; Michael Hageman; Munir Hussain; Roy Haskell; Kevin Stefanski; Feng Qian (Pharmaceutical Research, 2016)

Carbon Flux and Carbohydrate Gene Families in Pineapple - Robert E. Paull; Nancy Jung Chen; Ray Ming; Ching Man Wai; Neil Shirley; Julian Schwerdt; Vincent Bulone (Tropical Plant Biology, 2016)

Identification of microRNAs, phasiRNAs and Their Targets in Pineapple - Yun Zheng; Ting Li; Zhenning Xu; Ching Man Wai; Kun Chen; Xiaotuo Zhang; Shengpeng Wang; Bo Ji; Ray Ming; Ramanjulu Sunkar (Tropical Plant Biology, 2016)

CLEC5A is critical for dengue virus-induced osteoclast activation and bone homeostasis - Ya-Lang Huang; Szu-Ting Chen; Ren-Shyan Liu; Yen-Hsu Chen; Chun-Yu Lin; Chung-Hao Huang; Pei-Yun Shu; Ching-Len Liao; Shie-Liang Hsieh (Journal of Molecular Medicine, 2016)

The relationship between plasma and urinary 8-hydroxy-2-deoxyguanosine biomarkers measured by liquid chromatography tandem mass spectrometry - Chung-Ching Wang; Wei-Liang Chen; Chien-Ming Lin; Ching-Huang Lai; Ching-Hui Loh; Hong-I Chen; Saou-Hsing Liou (Environmental Science and Pollution Research, 2016)

Identification of Focal Epileptogenic Networks in Generalized Epilepsy Using Brain Functional Connectivity Analysis of Bilateral Intracranial EEG Signals - Po-Ching Chen; Eduardo M. Castillo; James Baumgartner; Joo Hee Seo; Milena Korostenskaja; Ki Hyeong Lee (Brain Topography, 2016)

Focusing phenomenon and near-trapped modes of SH waves - Jeng-Tzong Chen; Jia-Wei Lee; Ya-Ching Tu (Earthquake Engineering and Engineering Vibration, 2016)

Chidamide alleviates TGF-β-induced epithelial–mesenchymal transition in lung cancer cell lines - Sheng-Hao Lin; Bing-Yen Wang; Ching-Hsiung Lin; Peng-Ju Chien; Yueh-Feng Wu; Jiunn-Liang Ko; Jeremy J. W. Chen (Molecular Biology Reports, 2016)

Zonal management of multi-purposes groundwater utilization based on water quality and impact on the aquifer - Ching-Ping Liang; Cheng-Shin Jang; Ching-Fang Chen; Jui-Sheng Chen (Environmental Monitoring and Assessment, 2016)

Taiwanese Records of Oblong Large-Eye Seabream Gymnocranius oblongus (Teleostei: Lethrinidae) and Other Rare or Undetermined Large-Eye Seabreams - Wei-Jen Chen; Hsuan-Ching Ho; Philippe Borsa (Frontiers in Marine Science, 2016)

Study of tension wood in the artificially inclined seedlings of Koelreuteria henryi Dummer and its biomechanical function of negative gravitropism - Li-Fen Hung; Ching-Chu Tsai; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Preclinical Pharmacokinetics Study of R- and S-Enantiomers of the Histone Deacetylase Inhibitor, AR-42 (NSC 731438), in Rodents - Hao Cheng; Zhiliang Xie; William P. Jones; Xiaohui Tracey Wei; Zhongfa Liu; Dasheng Wang; Samuel K. Kulp; Jiang Wang; Christopher C. Coss; Ching-Shih Chen; Guido Marcucci; Ramiro Garzon; et al. (The AAPS Journal, 2016)

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

Molecular Characterization of Ethylene Response Sensor 1 (BoERS1) in Bambusa oldhamii - Yi-Lin Hsieh; Ching-Fang Lu; Bing-Yu Chiang; Shu-Chien Liao; Rita P.-Y. Chen; Choun-Sea Lin; Ai-Yu Wang; Chien-Chih Yang (Plant Molecular Biology Reporter, 2016)

Sensory determinants of valve rhythm dynamics provide in situ biodetection of copper in aquatic environments - Li-John Jou; Bo-Ching Chen; Wei-Yu Chen; Chung-Min Liao (Environmental Science and Pollution Research, 2016)

Arsenic speciation in rice and risk assessment of inorganic arsenic in Taiwan population - Hsiu-Ling Chen; Ching-Chang Lee; Winn-Jung Huang; Han-Ting Huang; Yi-Chen Wu; Ya-Chen Hsu; Yi-Ting Kao (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Soluble organic C and N and their relationships with soil organic C and N and microbial characteristics in moso bamboo (Phyllostachys edulis) plantations along an elevation gradient in Central Taiwan - Ching-Yu Huang; Shih-Hao Jien; Tsai-Huei Chen; Guanglong Tian; Chih-Yu Chiu (Journal of Soils and Sediments, 2016)

Multiobjective Optimal Design of Sewerage Rehabilitation by Using the Nondominated Sorting Genetic Algorithm-II - Yu-Hao Lin; Yi-Ping Chen; Ming-Der Yang; Tung-Ching Su (Water Resources Management, 2016)

Developing a reliable model for aquifer vulnerability - Cheng-Shin Jang; Chien-Wen Lin; Ching-Ping Liang; Jui-Sheng Chen (Stochastic Environmental Research and Risk Assessment, 2016)

Spatial optimization procedure for land-use arrangement in a community based on a human comfort perspective - Pei-Yuan Chen; Ching-Pin Tung; Wei-Chih Lin; Yuan-Hua Li (Paddy and Water Environment, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Effect of Chromium Supplementation on Element Distribution in a Mouse Model of Polycystic Ovary Syndrome - Tsung-Sheng Chen; Yi-Ting Chen; Chia-Hsin Liu; Chi-Ching Sun; Frank Chiahung Mao (Biological Trace Element Research, 2015)

Proteomic analysis of physiological versus pathological cardiac remodeling in animal models expressing mutations in myosin essential light chains - Aldrin V. Gomes; Katarzyna Kazmierczak; Jenice X. Cheah; Jennifer E. Gilda; Chen-Ching Yuan; Zhiqun Zhou; Danuta Szczesna-Cordary (Journal of Muscle Research and Cell Motility, 2015)

Genotyping of turkey coronavirus field isolates from various geographic locations in the Unites States based on the spike gene - Yi-Ning Chen; Chien Chang Loa; Mustafa Mohammed-Khair Ababneh; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2015)

Inhibition of hyperactivity and impulsivity by carbonic anhydrase inhibitors in spontaneously hypertensive rats, an animal model of ADHD - Ming-Tao Yang; Dai-Hua Lu; Jui-Ching Chen; Wen-Mei Fu (Psychopharmacology, 2015)

Identifications and removal of diurnal and semidiurnal variations in radon time series data of Hsinhua monitoring station in SW Taiwan using singular spectrum analysis - Arvind Kumar; Vivek Walia; Baldev Raj Arora; Tsanyao Frank Yang; Shih-Jung Lin; Ching-Chou Fu; Cheng-Hong Chen; Kuo-Liang Wen (Natural Hazards, 2015)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

2,3,5-Trimethoxy-4-cresol, an anti-metastatic constituent from the solid-state cultured mycelium of Antrodia cinnamomea and its mechanism - Chin-Chung Lin; Ching-Chun Chen; Yueh-Hsiung Kuo; Jong-Tar Kuo; K. J. Senthil Kumar; Sheng-Yang Wang (Journal of Natural Medicines, 2015)

Synergistic Impact of Nicotine and Shear Stress Induces Cytoskeleton Collapse and Apoptosis in Endothelial Cells - Yu-Hsiang Lee; Ruei-Siang Chen; Nen-Chung Chang; Kueir-Rarn Lee; Chien-Tsai Huang; Yu-Ching Huang; Feng-Ming Ho (Annals of Biomedical Engineering, 2015)

Associations between TRPV4 genotypes and body mass index in Taiwanese subjects - De-Min Duan; Semon Wu; Lung-An Hsu; Ming-Sheng Teng; Jeng-Feng Lin; Yu-Chen Sun; Ching-Feng Cheng; Yu-Lin Ko (Molecular Genetics and Genomics, 2015)

Robot-Assisted Passive Exercise for Ankle Hypertonia in Individuals with Chronic Spinal Cord Injury - Chia-Ying Fang; Miao-Ju Hsu; Chih-Chung Chen; Hsin-Yi Kathy Cheng; Ching-Chieh Chou; Ya-Ju Chang (Journal of Medical and Biological Engineering, 2015)

The differential roles of Slit2-exon 15 splicing variants in angiogenesis and HUVEC permeability - Yun-Chiu Yang; Pei-Ni Chen; Siou-Yu Wang; Chen-Yi Liao; Yu-Ying Lin; Shih-Rhong Sun; Chun-Ling Chiu; Yih-Shou Hsieh; Jia-Ching Shieh; Jinghua Tsai Chang (Angiogenesis, 2015)

Effect of the big flood events on the water quality of the Muar River, Malaysia - Yun Chen Ching; Yook Heng Lee; Mohd Ekhwan Toriman; Maimon Abdullah; Baharudin Bin Yatim (Sustainable Water Resources Management, 2015)

Adaptive model-based tracking control for real-time hybrid simulation - Pei-Ching Chen; Chia-Ming Chang; Billie F. Spencer; Keh-Chyuan Tsai (Bulletin of Earthquake Engineering, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Occurrence of pharmaceuticals, hormones, and perfluorinated compounds in groundwater in Taiwan - Yen-Ching Lin; Webber Wei-Po Lai; Hsin-hsin Tung; Angela Yu-Chen Lin (Environmental Monitoring and Assessment, 2015)

Avian reovirus S1133-induced apoptosis is associated with Bip/GRP79-mediated Bim translocation to the endoplasmic reticulum - Ping-Yuan Lin; Hung-Jen Liu; Ching-Dong Chang; Yo-Chia Chen; Chi-I Chang; Wen-Ling Shih (Apoptosis, 2015)

Analysis of space–time patterns of rainfall events during 1996–2008 in Yilan County (Taiwan) - Hwa-Lung Yu; Bo-Lin Chen; Chuan-Hung Chiu; Mong-Ming Lu; Ching-pin Tung (Stochastic Environmental Research and Risk Assessment, 2015)

Methodology of disaster risk assessment for debris flows in a river basin - Ing-Jia Chiou; Ching-Ho Chen; Wei-Lin Liu; Shiao-Mei Huang; Yu-Min Chang (Stochastic Environmental Research and Risk Assessment, 2015)

CD200 in growing rat lungs: developmental expression and control by dexamethasone - Mang-Hung Tsai; Chin-Chen Chu; Tsui-Shan Wei; Mei-Miao Chiu; Chiu-Yun Chang; I-Hua Wei; Hsiung-Fei Chien; Hui-Min Chen; Ching-Hsiang Wu; Ya-Fen Jiang-Shieh (Cell and Tissue Research, 2015)

In planta biocontrol of soilborne Fusarium wilt of banana through a plant endophytic bacterium, Burkholderia cenocepacia 869T2 - Ying-Ning Ho; Hsing-Mei Chiang; Chih-Ping Chao; Ching-Chung Su; Hui-Fang Hsu; Chen-tong Guo; Ju-Liang Hsieh; Chieh-Chen Huang (Plant and Soil, 2015)

Prevention of natural flowering in pineapple (Ananas comosus) by shading and urea application - Meng-Tzu Lin; Alfred Ming Chen; Tzong-Shyan Lin; Ching-San Kuan; Ching-Lung Lee; Wen-Ju Yang (Horticulture, Environment, and Biotechnology, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

TGF-β1 mediates the radiation response of prostate cancer - Chun-Te Wu; Ching-Chuan Hsieh; Tzu-Chen Yen; Wen-Cheng Chen; Miao-Fen Chen (Journal of Molecular Medicine, 2015)

Integrated water resources system dynamics modeling and indicators for sustainable rural community - Yuan-Hua Li; Pei-Yuan Chen; Wei-Hsuan Lo; Ching-Pin Tung (Paddy and Water Environment, 2015)

Ammonia exposure increases the expression of Na+:K+:2Cl− cotransporter 1a in the gills of the giant mudskipper, Periophthalmodon schlosseri - Shit F. Chew; Kum C. Hiong; Sock P. Lam; Xiu L. Chen; Biyun Ching; Yuen K. Ip (Journal of Comparative Physiology B, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Worldwide genetic differentiation in the common fouling barnacle, Amphibalanus amphitrite - Hsi-Nien Chen; Ling Ming Tsang; Ving Ching Chong; Benny K.K. Chan (Biofouling, 2014)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Spatial distribution of soil erosion and suspended sediment transport rate for Chou-Shui river basin - Chin-Ping Lin; Ching-Nuo Chen; Yu-Min Wang; Chih-Heng Tsai; Chang-Tai Tsai (Journal of Earth System Science, 2014)

Aerosolized bovine lactoferrin reduces lung injury and fibrosis in mice exposed to hyperoxia - Hsiao-Ling Chen; Chih-Ching Yen; Shih-Ming Wang; Tung-Chou Tsai; Zi-Lun Lai; Jheng-Yue Sun; Willei Lin; Wu-Huei Hsu; Chuan-Mu Chen (BioMetals, 2014)

Molecular characterization of argininosuccinate synthase and argininosuccinate lyase from the liver of the African lungfish Protopterus annectens, and their mRNA expression levels in the liver, kidney, brain and skeletal muscle during aestivation - You R. Chng; Jasmine L. Y. Ong; Biyun Ching; Xiu L. Chen; Wai P. Wong; Shit F. Chew; Yuen K. Ip (Journal of Comparative Physiology B, 2014)

Application of Neural Networks and Optimization Model in Conjunctive Use of Surface Water and Groundwater - Ching-Wen Chen; Chih-Chiang Wei; Hung-Jen Liu; Nien-Sheng Hsu (Water Resources Management, 2014)

Maintenance of human adipose derived stem cell (hASC) differentiation capabilities using a 3D culture - Ching-Yu Lin; Chi-Hui Huang; Yuan-Kun Wu; Nai-Chen Cheng; Jiashing Yu (Biotechnology Letters, 2014)

Soluble organic C and N and their relationships with soil organic C and N and microbial characteristics in moso bamboo (Phyllostachys edulis) plantations along an elevation gradient in Central Taiwan - Ching-Yu Huang; Shih-Hao Jien; Tsai-Huei Chen; Guanglong Tian; Chih-Yu Chiu (Journal of Soils and Sediments, 2014)

Optimal fallow area and location for multifunctional benefits of a paddy field during drought periods - Ching-Wen Chen; Nien-Sheng Hsu; Chieh-Shu Wu (Paddy and Water Environment, 2014)

Effect of the BDNF Val66Met Polymorphism on Regional Gray Matter Volumes and Cognitive Function in the Chinese Population - Mu-En Liu; Chu-Chung Huang; Mu-Hong Chen; Albert C. Yang; Pei-Chi Tu; Heng-Liang Yeh; Chen-Jee Hong; Jin-Fan Chen; Jen-Ping Hwang; Ching-Po Lin; Shih-Jen Tsai (NeuroMolecular Medicine, 2014)

The dual functions of YAP-1 to promote and inhibit cell growth in human malignancy - Hai Wang; Yu-Chen Du; Xiao-jun Zhou; Hong Liu; Shou-Ching Tang (Cancer and Metastasis Reviews, 2014)

Terfenadine induces anti-proliferative and apoptotic activities in human hormone-refractory prostate cancer through histamine receptor-independent Mcl-1 cleavage and Bak up-regulation - Wei-Ting Wang; Yen-Hui Chen; Jui-Ling Hsu; Wohn-Jenn Leu; Chia-Chun Yu; She-Hung Chan; Yunn-Fang Ho; Lih-Ching Hsu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Impact of FORMOSAT-3/COSMIC radio occultation data on the prediction of super cyclone Gonu (2007): a case study - S. K. A. V. Prasad Rao Anisetty; Ching-Yuang Huang; Shu-Ya Chen (Natural Hazards, 2014)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)

Determination of homogeneous regions for regional reference evapotranspiration estimation using the self-organizing map in western Taiwan - Ching-Tien Chen; Yu-Chuan Chang; Guan-Ting Wu (Paddy and Water Environment, 2014)

Cytotoxic effects of acrylamide in nerve growth factor or fibroblast growth factor 1-induced neurite outgrowth in PC12 cells - Jong-Hang Chen; Don-Ching Lee; Ing-Ming Chiu (Archives of Toxicology, 2013)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Partitioning of the source of leaf calcium of American beech and sugar maple using leaf Ca/Sr ratios: a predominantly surficial but variable depth of Ca uptake - Ching-Chih Chen; Frieda Beauregard; Benoît Côté; Nicolas Bélanger; François Courchesne; William H. Hendershot (Plant and Soil, 2013)

Pemetrexed downregulates ERCC1 expression and enhances cytotoxicity effected by resveratrol in human nonsmall cell lung cancer cells - Ruey-Shyang Chen; Jen-Chung Ko; Hsien-Chun Chiu; Ting-Yu Wo; Yi-Jhen Huang; Sheng-Chieh Tseng; Huang-Jen Chen; Yu-Ching Huang; Yi-Jun Jian; Wei-Ting Lee; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Identifying and characterizing Yarrowia keelungensis sp. nov., an oil-degrading yeast isolated from the sea surface microlayer - Chin-Feng Chang; Chih-Chen Chen; Ching-Fu Lee; Shiu-Mei Liu (Antonie van Leeuwenhoek, 2013)

Design, synthesis, and evaluation of fluorescent cell-penetrating peptidic antagonists of Grb2-SH2 for targeting MCF-7 breast cancer cells - Yu-Cheng Hsiao; Chen-Yu Lee; Yi-Jhen Lin; Shu-Huai Tsai; Kee-Ching G. Jeng; Wei-Ting Chao; Feng-Di T. Lung (Medicinal Chemistry Research, 2013)

Histone deacetylase inhibitor AR-42 enhances E7-specific CD8+ T cell-mediated antitumor immunity induced by therapeutic HPV DNA vaccination - Sung Yong Lee; Zhuomin Huang; Tae Heung Kang; Ruey-Shyang Soong; Jayne Knoff; Ellen Axenfeld; Chenguang Wang; Ronald D. Alvarez; Ching-Shih Chen; Chien-Fu Hung; T.-C. Wu (Journal of Molecular Medicine, 2013)

Paradigm of Monoterpene (β-phellandrene) Hydrocarbons Production via Photosynthesis in Cyanobacteria - Fiona K. Bentley; Jose Gines García-Cerdán; Hsu-Ching Chen; Anastasios Melis (BioEnergy Research, 2013)

Subneutralizing antibodies to enterovirus 71 induce antibody-dependent enhancement of infection in newborn mice - I-Chun Chen; Shih-Min Wang; Chun-Keung Yu; Ching-Chuan Liu (Medical Microbiology and Immunology, 2013)

Probabilistic health risk assessment for ingestion of seafood farmed in arsenic contaminated groundwater in Taiwan - Ching-Ping Liang; Cheng-Shin Jang; Jui-Sheng Chen; Sheng-Wei Wang; Jin-Jing Lee; Chen-Wuing Liu (Environmental Geochemistry and Health, 2013)

Estimating Pumping Rates and Identifying Potential Recharge Zones for Groundwater Management in Multi-Aquifers System - Hsien-Tsung Lin; Kai-Yuan Ke; Yih-Chi Tan; Shih-Ching Wu; Gao Hsu; Po-Chia Chen; Shi-Ting Fang (Water Resources Management, 2013)

The integration of nautical hazard assessment and harbor GIS models to the Taichung Port area in Taiwan - Cheng-Wu Chen; Ching-Chung Lee; Chia-Hung Chen; Chun-Pin Tseng (Natural Hazards, 2013)

Toxicokinetics of tilapia following high exposure to waterborne and dietary copper and implications for coping mechanisms - Jeng-Wei Tsai; Yun-Ru Ju; Ying-Hsuan Huang; Yue-Sun Deng; Wei-Yu Chen; Chin-Ching Wu; Chung-Min Liao (Environmental Science and Pollution Research, 2013)

Erratum to: Significance of IL-6 in the transition of hormone-resistant prostate cancer and the induction of myeloid-derived suppressor cells - Chun-Te Wu; Ching-Chuan Hsieh; Cheng-Chia Lin; Wen-Cheng Chen; Ji-Hong Hong; Miao-Fen Chen (Journal of Molecular Medicine, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

Transcriptional regulation of tristetraprolin by NF-κB signaling in LPS-stimulated macrophages - Yu-Ling Chen; Yu-Wun Jiang; Yu-Lun Su; Sheng-Chung Lee; Mau-Sun Chang; Ching-Jin Chang (Molecular Biology Reports, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

A study of the frequency of methylation of gene promoter regions in colorectal cancer in the Taiwanese population - CHANG-CHIEH WU; JEN-CHUN KUAN; CHIH-HSIUNG HSU; TZU-AN CHEN; CHIEN-AN SUN; TSAN YANG; SHINN-LONG LIN; YU-CHING CHOU (Journal of Genetics, 2013)

An Adaptation Due to Climate Change in Southwest Coast of Taiwan - Yuan-Jyh Lan; Tai-Wen Hsu; Yue-Chen Lin; Ching-Jer Huang (Coastal Management, 2013)

Application of GIS for the determination of hazard hotspots after direct transportation linkages between Taiwan and China - Cheng-Wu Chen; Ching-Chung Lee; Chun-Pin Tseng; Chia-Hung Chen (Natural Hazards, 2013)

MicroRNA-210 targets antiapoptotic Bcl-2 expression and mediates hypoxia-induced apoptosis of neuroblastoma cells - Chung-Ching Chio; Jia-Wei Lin; Heien-An Cheng; Wen-Ta Chiu; Yuan-Hung Wang; Jhi-Joung Wang; Chung-Hsi Hsing; Ruei-Ming Chen (Archives of Toxicology, 2013)

Heme oxygenase is involved in H2O2-induced lateral root formation in apocynin-treated rice - Yi-Hsuan Chen; Yun-Yang Chao; Yun Yen Hsu; Ching Huei Kao (Plant Cell Reports, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

A molecular diagnosis method using real-time PCR for quantification and detection of Fusarium oxysporum f. sp. cubense race 4 - Ying-Hong Lin; Ching-Chung Su; Chih-Ping Chao; Chi-Yu Chen; Chung-Jan Chang; Jenn-Wen Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2013)

Lipopolysaccharide/adenosine triphosphate-mediated signal transduction in the regulation of NLRP3 protein expression and caspase-1-mediated interleukin-1β secretion - Pei-Chun Liao; Louis Kuoping Chao; Ju-Ching Chou; Wei-Chih Dong; Chien-Nan Lin; Chai-Yi Lin; Ann Chen; Shuk-Man Ka; Chen-Lung Ho; Kuo-Feng Hua (Inflammation Research, 2013)

Alleviation effects of magnesium on copper toxicity and accumulation in grapevine roots evaluated with biotic ligand models - Bo-Ching Chen; Pei-Chi Ho; Kai-Wei Juang (Ecotoxicology, 2013)

Prospective study of effect modification by Toll-like receptor 4 variation on the association between Trichomonas vaginalis serostatus and prostate cancer - Yen Ching Chen; Yi Ling Huang; Elizabeth A. Platz; John F. Alderete; Lu Zheng; Jennifer R. Rider; Peter Kraft; Edward Giovannucci; Siobhan Sutcliffe (Cancer Causes & Control, 2013)

A procedure to estimate cover coefficient and parameters of soil moisture stress function using soil moisture monitoring data - Nien-Ming Hong; Ching-Pin Tung; Chu-hui Chen (Paddy and Water Environment, 2013)

Pulse Inversion Chirp Coded Tissue Harmonic Imaging (PI-CTHI) of Zebrafish Heart Using High Frame Rate Ultrasound Biomicroscopy - Jinhyoung Park; Ying Huang; Ruimin Chen; Jungwoo Lee; Thomas M. Cummins; Qifa Zhou; Ching-Ling Lien; K. K. Shung (Annals of Biomedical Engineering, 2013)

Isolation of marine bacteria with antimicrobial activities from cultured and field-collected soft corals - Yu-Hsin Chen; Jimmy Kuo; Ping-Jung Sung; Yu-Chia Chang; Mei-Chin Lu; Tit-Yee Wong; Jong-Kang Liu; Ching-Feng Weng; Wen-Hung Twan; Fu-Wen Kuo (World Journal of Microbiology and Biotechnology, 2012)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Significance of IL-6 in the transition of hormone-resistant prostate cancer and the induction of myeloid-derived suppressor cells - Chun-Te Wu; Ching-Chuan Hsieh; Cheng-Chia Lin; Wen-Cheng Chen; Ji-Hong Hong; Miao-Fen Chen (Journal of Molecular Medicine, 2012)

Albumin prevents reactive oxygen species-induced mitochondrial damage, autophagy, and apoptosis during serum starvation - Shu-Yu Liu; Chia-Ling Chen; Tsan-Tzu Yang; Wei-Ching Huang; Chia-Yuan Hsieh; Wan-Jou Shen; Tsung-Ting Tsai; Chi-Chang Shieh; Chiou-Feng Lin (Apoptosis, 2012)

Biomechanical features of eccentric cambial growth and reaction wood formation in broadleaf tree branches - Ching-Chu Tsai; Li-Fen Hung; Ching-Te Chien; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2012)

In vivo screening of zebrafish microRNA responses to bacterial infection and their possible roles in regulating immune response genes after lipopolysaccharide stimulation - Tsung-Han Wu; Chieh-Yu Pan; Ming-Ching Lin; Jung-Chen Hsieh; Cho-Fat Hui; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2012)

The effects of a sudden salinity change on cortisol, glucose, lactate, and osmolality levels in grouper Epinephelus malabaricus - Wen-Ching Tsui; Jiann-Chu Chen; Sha-Yen Cheng (Fish Physiology and Biochemistry, 2012)

GIS-based evaluation on the fault motion-induced coseismic landslides - Ming-Wey Huang; Chien-Yuan Chen; Tzu-Hsiu Wu; Chi-Ling Chang; Sheu-Yien Liu; Ching-Yun Kao (Journal of Mountain Science, 2012)

Glacially derived material in an Inner Mongolian desert lake during Marine Isotope Stage 2 - Kandasamy Selvaraj; Chen‐Tung Arthur Chen; C. Prakash Babu; Jiann‐Yuh Lou; Ching‐Ling Liu; Kenneth J. Hsu (Journal of Quaternary Science, 2012)
Establishing the precise timing of continental glacial dynamics and abrupt high‐latitude climate events is crucial to understanding the causes of global climate change. Here we present multi‐proxy records in a lake sediment core from arid Inner Mongolia (Wuliangsuhai Lake) that show two distinct glacially derived sedimentation events at ∼26.2–21.8 and ∼17.3–11.5k cal a BP. Fine sediments from the Last Glacial Maximum separate these glacially derived coarse sediments. Within these intervals, the occurrence of granite clasts at ∼24–23.5, 17.3–17 and 15.6–14.1k cal a BP implies either sediment discharge by meltwater as well as strong current flow in the Yellow River and/or sediment influx through hill‐slope mass wasting and landsliding from the nearby Yin Mountains. Surface microfeatures of quartz grains and spot elemental analysis of black specks in these intervals, however, indicate that physical weathering is dominant and that the provenance of the rocks is probably from a glacial source. To the best of our knowledge, this is the first time glacier‐derived materials have been detected in any desert lake in the Yellow River basin. The occurrence of granite clasts roughly correlates with Heinrich events in the North Atlantic, suggesting synchronous ice sheet dynamics in high‐ and mid‐latitude regions during the Last Glacial period. Although our data provide unprecedented evidence for the influence of glacier‐related processes in arid Inner Mongolia, further well‐dated records are clearly needed to re‐evaluate the correlative inference drawn between granite clast layers in Wuliangsuhai Lake and Heinrich events in the North Atlantic. Copyright © 2012 John Wiley & Sons, Ltd.

Interplay of RsbM and RsbK controls the σ B activity of Bacillus cereus - Lei‐Chin Chen; Jung‐Chi Chen; Jwu‐Ching Shu; Chien‐Yen Chen; Ssu‐Ching Chen; Shu‐Hwa Chen; Chun‐Yen Lin; Chi‐Yu Lu; Chien‐Cheng Chen (Environmental Microbiology, 2012)
Summary The alternative transcription factor σ B of Bacillus cereus controls the expression of a number of genes that respond to environmental stress. Four proteins encoded in the sigB gene cluster, including RsbV, RsbW, RsbY (RsbU) and RsbK, are known to be essential in the σ B ‐mediated stress response. In the context of stress, the hybrid sensor kinase RsbK is thought to phosphorylate the response regulator RsbY, a PP2C serine phosphatase, leading to the dephosphorylation of the phosphorylated RsbV. The unphosphorylated RsbV then sequesters the σ B antagonist, RsbW, ultimately liberating σ B . The gene arrangement reveals an open reading frame, bc1007 , flanked immediately downstream by rsbK within the sigB gene cluster. However, little is known about the function of bc1007 . In this study, the deletion of bc1007 resulted in high constitutive σ B expression independent of environmental stimuli, indicating that bc1007 plays a role in σ B regulation. A bacterial two‐hybrid analysis demonstrated that BC1007 interacts directly with RsbK, and autoradiographic studies revealed a specific C 14 ‐methyl transfer from the radiolabelled S‐adenosylmethionine to RsbK when RsbK was incubated with purified BC1007. Our data suggest that BC1007 (RsbM) negatively regulates σ B activity by methylating RsbK. Additionally, mutagenic substitution was employed to modify 12 predicted methylation residues in RsbK. Certain RsbK mutants were able to rescue σ B activation in a rsbK ‐deleted bacterial strain, but RsbK E439A failed to activate σ B , and RsbK E446A only moderately induced σ B . These results suggest that Glu439 is the preferred methylation site and that Glu446 is potentially a minor methylation site. Gene arrays of the rsbK orthologues and the neighbouring rsbM orthologues are found in a wide range of bacteria. The regulation of sigma factors through metylation of RsbK‐like sensor kinases appears to be widespread in the microbial world.

Apoptosis induced by 1,3,6,7-tetrahydroxyxanthone in Hepatocellular carcinoma and proteomic analysis - Wei-ming Fu; Jin-fang Zhang; Hua Wang; Hong-sheng Tan; Wei-mao Wang; Shih-Chi Chen; Xiao Zhu; Tak-ming Chan; Ching-man Tse; Kwong-sak Leung; Gang Lu; Hong-xi Xu; et al. (Apoptosis, 2012)

Exploring the spatial and temporal relationships between mosquito population dynamics and dengue outbreaks based on climatic factors - Ching-Tsan Tsai; Fung-Chang Sung; Patrick S. Chen; Shu-Chiung Lin (Stochastic Environmental Research and Risk Assessment, 2012)

Heme oxygenase is involved in nitric oxide- and auxin-induced lateral root formation in rice - Yi-Hsuan Chen; Yun-Yang Chao; Yun Yen Hsu; Chwan-Yang Hong; Ching Huei Kao (Plant Cell Reports, 2012)

Testosterone improves the transition of primary oocytes in artificial maturation eels (Anguilla japonica) by altering ovarian PTEN expression - Yung-Sen Huang; Ya-Mei Chen; Pei-Chi Liao; Yan-Horn Lee; Jin-Chywan Gwo; Ming-Chyuan Chen; Ching-Fong Chang (Fish Physiology and Biochemistry, 2012)

Five novel species of the anamorphic genus Candida in the Cyberlindnera clade isolated from natural substrates in Taiwan - Chin-Feng Chang; Yi-Ru Liu; Shan-Fu Chen; Gennadi I. Naumov; Elena S. Naumova; Ching-Fu Lee (Antonie van Leeuwenhoek, 2012)

Fern spore and pollen airspora profile of Singapore - Tan Ching Ong; Soo Hwee Lim; Xiaowei Chen; Siti Dahlia Mohd Dali; Hugh Tiang Wah Tan; Bee Wah Lee; Fook Tim Chew (Aerobiologia, 2012)

Simvastatin reduces VCAM-1 expression in human umbilical vein endothelial cells exposed to lipopolysaccharide - Johnson Chia-Shen Yang; Faye Huang; Chia-Jung Wu; Yi-Chun Chen; Tsu-Hsiang Lu; Ching-Hua Hsieh (Inflammation Research, 2012)

Copper accumulation, translocation, and toxic effects in grapevine cuttings - Kai-Wei Juang; Yung-I Lee; Hung-Yu Lai; Chiung-Huei Wang; Bo-Ching Chen (Environmental Science and Pollution Research, 2012)

The inhibition by di(2-ethylhexyl)-phthalate of erg-mediated K+ current in pituitary tumor (GH3) cells - Sheng-Nan Wu; Wei-Hsin Yang; Chia-Chen Yeh; Hsien-Ching Huang (Archives of Toxicology, 2012)

Assessment of the quality of stormwater from an industrial park in central Taiwan - Nyuk-Min Chong; Yi-Ching Chen; Chia-Ning Hsieh (Environmental Monitoring and Assessment, 2012)

Evaluation of p53 genotype on gene expression in the testis, liver, and heart from male C57BL/6 mice - Dayton M. Petibone; Rohan M. Kulkarni; Ching-Wei Chang; James J. Chen; Suzanne M. Morris (Transgenic Research, 2012)

Physiographic Drainage-Inundation Model Based Flooding Vulnerability Assessment - Jenq-Tzong Shiau; Ching-Nuo Chen; Chang-Tai Tsai (Water Resources Management, 2012)

A graphical representation for consequential life cycle assessment of future technologies—Part 2: two case studies on choice of technologies and evaluation of technology improvements - I-Ching Chen; Yasuhiro Fukushima; Yasunori Kikuchi; Masahiko Hirao (The International Journal of Life Cycle Assessment, 2012)

Global effect on multi-segment physiological tremors due to localized fatiguing contraction - Yi-Ching Chen; Jeng-Feng Yang; Ing-Shiou Hwang (European Journal of Applied Physiology, 2012)

Toxicokinetics/toxicodynamics with damage feedback improves risk assessment for tilapia and freshwater clam exposed to arsenic - Wei-Yu Chen; Chung-Min Liao; Yun-Ru Ju; Sher Singh; Li-John Jou; Bo-Ching Chen; Jeng-Wei Tsai (Ecotoxicology, 2012)

A graphical representation for consequential life cycle assessment of future technologies. Part 1: methodological framework - I-Ching Chen; Yasuhiro Fukushima; Yasunori Kikuchi; Masahiko Hirao (The International Journal of Life Cycle Assessment, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

Climate change, sea level rise and rice: global market implications - Chi-Chung Chen; Bruce McCarl; Ching-Cheng Chang (Climatic Change, 2012)

Calcium is involved in nitric oxide- and auxin-induced lateral root formation in rice - Yi Hsuan Chen; Ching Huei Kao (Protoplasma, 2012)

Rilmenidine improves hepatic steatosis through p38-dependent pathway to higher the expression of farnesoid X receptor - Po-Sheng Yang; Hung-Tsung Wu; Hsien-Hui Chung; Chun-Ta Chen; Chin-Wen Chi; Ching-Hua Yeh; Juei-Tang Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Investigations into the Correlation Properties of Membrane Electroporation-Induced Inward Currents: Prediction of Pore Formation - Sheng-Nan Wu; Chia-Chen Yeh; Pei-Yu Wu; Hsien-Ching Huang; Mei-Ling Tsai (Cell Biochemistry and Biophysics, 2012)

Associations Between Water Quality Parameters and Planktonic Communities in Three Constructed Wetlands, Taipei - Pen-Yuan Chen; Pei-Fen Lee; Chie-Jen Ko; Chun-Han Ko; Ta-Ching Chou; Chia-Ji Teng (Wetlands, 2011)

Background K2P Channels KCNK3/9/15 Limit the Budding of Cell Membrane-derived Vesicles - Daniel Tsung-Ning Huang; Naiwen Chi; Shiou-Ching Chen; Ting-Ying Lee; Kate Hsu (Cell Biochemistry and Biophysics, 2011)

Infectious bursal disease DNA vaccination conferring protection by delayed appearance and rapid clearance of invading viruses - Yung-Yi Chen; Ming Kun Hsieh; Chun-Yu Tung; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2011)

Mean Structure and Variability of the Cold Dome Northeast of Taiwan - Sen Jan; Chung-Chi Chen; Ya-Ling Tsai; Yiing Jiang Yang; Joe Wang; Ching-Sheng Chern; Glen Gawarkiewicz; Ren-Chieh Lien; Luca Centurioni; Jia-Yu Kuo (Oceanography, 2011)

Mapping land uplift and subsidence in the industrial parks in northern Taiwan by radar interferometry - Chih-Tien Wang; Kun-Shan Chen; Jyr-Ching Hu; Wen-Yen Chang; Wolfgang M. Boerner (International Journal of Remote Sensing, 2011)

Numerical experiments investigating the orographic effects on a heavy rainfall event over the northwestern coast of Taiwan during TAMEX IOP 13 - Pay-Liam Lin; Yi-Leng Chen; Ching-Sen Chen; Che-Ling Liu; Ching-Ying Chen (Meteorology and Atmospheric Physics, 2011)

An integrated flood risk assessment model for property insurance industry in Taiwan - Wen-Ko Hsu; Pei-Chiung Huang; Ching-Cheng Chang; Cheng-Wu Chen; Dung-Moung Hung; Wei-Ling Chiang (Natural Hazards, 2011)

Perturbations of the stress-induced GLUT4 localization pathway in slow-twitch muscles of obese Zucker rats - Yu-Ching Chen; Shin-Da Lee; Shin-Ying Hsih; Yung-Pei Hsu; Chia-Hua Kuo; Low-Tone Ho (Journal of Physiology and Biochemistry, 2011)

Identification and characterization of a neutralizing-epitope-containing spike protein fragment in turkey coronavirus - Yi-Ning Chen; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2011)

Lactoferrin: an iron-binding antimicrobial protein against Escherichia coli infection - Chih-Ching Yen; Chih-Jie Shen; Wu-Huei Hsu; Yi-Hsin Chang; Hsin-Tang Lin; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2011)

An easy and efficient protocol in the production of pflp transgenic banana against Fusarium wilt - Mei-Kuen Yip; Sin-Wan Lee; Kuei-Ching Su; Yi-Hsien Lin; Tai-Yang Chen; Teng-Yung Feng (Plant Biotechnology Reports, 2011)

Coupling bioaccumulation and phytotoxicity to predict copper removal by switchgrass grown hydroponically - Kai-Wei Juang; Hung-Yu Lai; Bo-Ching Chen (Ecotoxicology, 2011)

Assessing abalone growth inhibition risk to cadmium and silver by linking toxicokinetics/toxicodynamics and subcellular partitioning - Wei-Yu Chen; Yun-Ru Ju; Bo-Ching Chen; Jeng-Wei Tsai; Chia-Jung Lin; Chung-Min Liao (Ecotoxicology, 2011)

Inorganic arsenic causes cell apoptosis in mouse cerebrum through an oxidative stress-regulated signaling pathway - Cheng Chien Yen; Tsung Jung Ho; Chin Ching Wu; Chun Fang Chang; Chin Chuan Su; Ya Wen Chen; Tzyy Rong Jinn; Tien Hui Lu; Po Wen Cheng; Yi Chang Su; Shing Hwa Liu; Chun Fa Huang (Archives of Toxicology, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

Synthesis of Highly Selective Indole-Based Sensors for Mercuric Ion - Huei-Jyun Huang; Jiun-Ly Chir; Hsiu-Jung Cheng; Shau-Jiun Chen; Ching-Han Hu; An-Tai Wu (Journal of Fluorescence, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

Characterization of Expressed Sequence Tags from Flower Buds of Alpine Lilium formosanum using a Subtractive cDNA Library - Wei-Kuang Wang; Chia-Chin Liu; Tzen-Yuh Chiang; Ming-Tse Chen; Chang-Hung Chou; Ching-Hui Yeh (Plant Molecular Biology Reporter, 2011)

Generation of transgenic watermelon resistant to Zucchini yellow mosaic virus and Papaya ringspot virus type W - Tsong-Ann Yu; Chu-Hui Chiang; Hui-Wen Wu; Chin-Mei Li; Ching-Fu Yang; Jun-Han Chen; Yu-Wen Chen; Shyi-Dong Yeh (Plant Cell Reports, 2011)

Enhancement of temozolomide-induced apoptosis by valproic acid in human glioma cell lines through redox regulation - Ching-Hsein Chen; Yu-Jia Chang; Maurice S. B. Ku; King-Thom Chung; Jen-Tsung Yang (Journal of Molecular Medicine, 2011)

Using chemical fractionation to evaluate the phytoextraction of cadmium by switchgrass from Cd-contaminated soils - Bo-Ching Chen; Hung-Yu Lai; Dar-Yuan Lee; Kai-Wei Juang (Ecotoxicology, 2011)

Activity enhancement and stabilization of lipase from Pseudomonas cepacia in polyallylamine-mediated biomimetic silica - Guan-Chun Chen; I-Ching Kuan; Jian-Ren Hong; Bing-Hong Tsai; Shiow-Ling Lee; Chi-Yang Yu (Biotechnology Letters, 2011)

Complete nucleotide sequence of capsicum chlorosis virus isolated from Phalaenopsis orchid and the prediction of the unexplored genetic information of tospoviruses - You-Xiu Zheng; Ching-Chung Chen; Fuh-Jyh Jan (Archives of Virology, 2011)

Identification and characterization of H10 enzymes isolated from Bacillus cereus H10 with keratinolytic and proteolytic activities - Kun-Nan Chen; Ju-Chieh Huang; Ching-I Chung; Wen-Yen Kuo; Ming-Ju Chen (World Journal of Microbiology and Biotechnology, 2011)

Simulation of Runoff and Suspended Sediment Transport Rate in a Basin with Multiple Watersheds - Ching-Nuo Chen; Chih-Heng Tsai; Chang-Tai Tsai (Water Resources Management, 2011)

The integrated WRF/urban modelling system: development, evaluation, and applications to urban environmental problems - Fei Chen; Hiroyuki Kusaka; Robert Bornstein; Jason Ching; C. S. B. Grimmond; Susanne Grossman‐Clarke; Thomas Loridan; Kevin W. Manning; Alberto Martilli; Shiguang Miao; David Sailor; Francisco P. Salamanca; et al. (International Journal of Climatology, 2011)
To bridge the gaps between traditional mesoscale modelling and microscale modelling, the National Center for Atmospheric Research, in collaboration with other agencies and research groups, has developed an integrated urban modelling system coupled to the weather research and forecasting (WRF) model as a community tool to address urban environmental issues. The core of this WRF/urban modelling system consists of the following: (1) three methods with different degrees of freedom to parameterize urban surface processes, ranging from a simple bulk parameterization to a sophisticated multi‐layer urban canopy model with an indoor–outdoor exchange sub‐model that directly interacts with the atmospheric boundary layer, (2) coupling to fine‐scale computational fluid dynamic Reynolds‐averaged Navier–Stokes and Large‐Eddy simulation models for transport and dispersion (T&D) applications, (3) procedures to incorporate high‐resolution urban land use, building morphology, and anthropogenic heating data using the National Urban Database and Access Portal Tool (NUDAPT), and (4) an urbanized high‐resolution land data assimilation system. This paper provides an overview of this modelling system; addresses the daunting challenges of initializing the coupled WRF/urban model and of specifying the potentially vast number of parameters required to execute the WRF/urban model; explores the model sensitivity to these urban parameters; and evaluates the ability of WRF/urban to capture urban heat islands, complex boundary‐layer structures aloft, and urban plume T&D for several major metropolitan regions. Recent applications of this modelling system illustrate its promising utility, as a regional climate‐modelling tool, to investigate impacts of future urbanization on regional meteorological conditions and on air quality under future climate change scenarios. Copyright © 2010 Royal Meteorological Society

Asymmetric boundary shifts of tropical montane Lepidoptera over four decades of climate warming - I‐Ching Chen; Jane K. Hill; Hau‐Jie Shiu; Jeremy D. Holloway; Suzan Benedick; Vun Khen Chey; Henry S. Barlow; Chris D. Thomas (Global Ecology and Biogeography, 2011)
Aim To estimate whether species have shifted at equal rates at their leading edges (cool boundaries) and trailing edges (warm boundaries) in response to climate change. We provide the first such evidence for tropical insects, here examining elevation shifts for the upper and lower boundaries shifts of montane moths. Threats to species on tropical mountains are considered. Location Mount Kinabalu, Sabah, Malaysia. Methods We surveyed Lepidoptera (Geometridae) on Mount Kinabalu in 2007, 42 years after the previous surveys in 1965. Changes in species upper and lower boundaries, elevational extents and range areas were assessed. We randomly subsampled the data to ensure comparable datasets between years. Estimated shifts were compared for endemic versus more widespread species, and for species that reached their range limits at different elevations. Results Species that reached their upper limits at 2500–2700 m ( n = 28 species, 20% of those considered) retreated at both their lower and upper boundaries, and hence showed substantial average range contractions (−300 m in elevational extent and −45 km 2 in estimated range area). These declines may be associated with changes in cloud cover and the presence of ecological barriers (geological and vegetation transitions) which impede uphill movement. Other than this group, most species ( n = 109, 80% of the species considered) expanded their upper boundaries upwards (by an average of 152 m) more than they retreated at their lower boundaries (77 m). Main conclusions Without constraints, leading margins shifted uphill faster than trailing margins retreated, such that many species increased their elevational extents. However, this did not result in increases in range area because the area of land available declines with increasing elevation. Species close to a major ecological/geological transition zone on the mountain flank declined in their range areas. Extinction risk may increase long before species reach the summit, even when undisturbed habitats are available.

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Calculation of bed load based on the measured data of suspended load - Chang-Tai Tsai; Chih-Heng Tsai; Chun-Hung Weng; Jinn-Jong Bair; Ching-Nuo Chen (Paddy and Water Environment, 2010)

Interannual variability of circulation–rainfall relationship in Taiwan during the Mei‐yu season - Jau‐Ming Chen; Jung‐Lien Chu; Ching‐Feng Shih; Yea‐Ching Tung (International Journal of Climatology, 2010)
This study aims to investigate interannual variability of seasonal rainfall in Taiwan during the Mei‐yu season (May–June). Its relationship with the low‐level circulation anomaly and associated large‐scale regulatory processes are also examined. It is found that the circulation–rainfall relationship is largely determined by the spatial distribution between Taiwan and the circulation anomaly off the southeastern coastlines of East Asia. For seasons when Taiwan lies under and near the anomalous circulation centre, strong downward (upward) motion and anomalous easterly (southwesterly) moisture flux assocaited with an anomalous high (low) provide large‐scale environments favourable to decreased (increased) Mei‐yu rainfall in Taiwan, resulting in a negative correlation in the circulation–rainfall relationship (anomalous high vs anomalous dry and anomalous low vs anomalous wet). For seasons when Taiwan is located over the northern boundary of the circulation anomaly, anomalous southwesterly (northeasterly) moisture flux induced by an anomalous high (low) enhances (suppresses) moisture supplies from the South China Sea into Taiwan to set up large‐scale conditions suitable for increased (decreased) Mei‐yu rainfall. A positive correlation in the circulation–rainfall relationship (anomalous high vs anomalous wet and anomalous low vs anomalous dry) thus occurs. The Pacific subtropical high (PSH) and monsoon trough (MT) tend to have a coherent spatial (eastward or westward) displacement in each rainfall variability type. The appearance of a low‐level anomalous high (low) in the Taiwan region corresponds to a PSH expansion (retreat) and a MT retreat (expansion) towards the west (east). A strong (moderate) displacement in the PSH and MT is accompanied by a low‐level circulation anomaly centering near (south of) Taiwan and a negative‐correlation (positive‐correlation) variability type. Analyses also suggest that large‐scale processes at low latitudes play a more important role than midlatitudinal transient activity in regulating interannual variability of Mei‐yu rainfall over subtropical Taiwan. Copyright © 2009 Royal Meteorological Society

Constitutive expression of a fungal glucose oxidase gene in transgenic tobacco confers chilling tolerance through the activation of antioxidative defence system - Subbiyan Maruthasalam; Yi Lun Liu; Ching Mei Sun; Pei Ying Chen; Chih Wen Yu; Pei Fang Lee; Chin Ho Lin (Plant Cell Reports, 2010)

Role of DNA methyltransferase 1 in hormone-resistant prostate cancer - Miao-Fen Chen; Wen-Cheng Chen; Yu-Jia Chang; Ching-Fang Wu; Chun-Te Wu (Journal of Molecular Medicine, 2010)

Odontoglossum ringspot virus causing flower crinkle in Phalaenopsis hybrids - You-Xiu Zheng; Bing-Nan Shen; Ching-Chung Chen; Fuh-Jyh Jan (European Journal of Plant Pathology, 2010)

Trace metal cycling in the surface water of the South China Sea: Vertical fluxes, composition, and sources - Tung-Yuan Ho; Wen-Chen Chou; Ching-Ling Wei; Fei-Jan Lin; George T. F. Wong; Hui-Ling Line (Limnology and Oceanography, 2010)
We deployed floating traps in the surface waters of the South China Sea on four occasions at depths of 30 m, 100 m, and 160 m from 2006 to 2007 to quantify vertical metal fluxes in the surface water and examine trace metal composition in the sinking particles to investigate their sources. The elements determined include 13 trace metals and 8 major elements. The fluxes for most of the bioactive elements at 30 m varied markedly during different seasons and strongly co‐varied with organic matter production, but the fluxes at 160 m were low and consistent under different seasons, showing that most of the elements were internally recycled in the surface water during productive seasons. Most of the bioactive trace metals in sinking particles were correlated with biogenic P, and their P‐normalized quotas were also strongly associated with lithogenic Al. The ratios of metals to Al and P for most of the bioactive trace metals were significantly higher than the ratios in lithogenic particles and than intracellular quotas in plankton, respectively, indicating that the trace metals in the sinking particles were abiogenic, nonlithogenic, and adsorbed on biogenic particles. The comparable fluxes between aeolian deposition and the sinking particles in the mixed layer demonstrate that the highly enriched trace metals in the sinking particles were attributed to input from anthropogenic aerosols. The coupling and transport of anthropogenic trace metals with biogenic particles in oceanic surface waters may be an important mechanism for trace metal cycling in global oceans.

5,5-Diphenyl-2-thiohydantoin-N10 (DPTH-N10) suppresses proliferation of cultured colon cancer cell line COLO-205 by inhibiting DNA synthesis and activating apoptosis - Tong-Sheng Lee; Li-Ching Chen; Yuan Liu; Jender Wu; Yu-Chih Liang; Wen-Sen Lee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Metastasis of gastric carcinoma to the thyroid and lung: a case report and review of literature - Hwa-chan Lee; Fen-fen Chen; Ching-chu Lo; Chung-jing Wang; Wei-chun Lo; Shi-ping Luh (Journal of Zhejiang University-SCIENCE B, 2010)

An Evaluation of Colonoscopy Use: Implications for Health Education - Chia-Ching Chen; Charles E. Basch; Tetsuji Yamada (Journal of Cancer Education, 2010)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

Probiotic Lactobacillus casei Expressing Human Lactoferrin Elevates Antibacterial Activity in the Gastrointestinal Tract - Hsiao-Ling Chen; Yi-Wen Lai; Chua-Shun Chen; Te-Wei Chu; Willie Lin; Chih-Ching Yen; Ming-Fong Lin; Ming-Yu Tu; Chuan-Mu Chen (BioMetals, 2010)

Design and implementation of an adaptive code discriminator in a DSP/FPGA-based Galileo receiver - Jyh-Ching Juang; Yu-Hsuan Chen; Tsai-Ling Kao; Yung-Fu Tsai (GPS Solutions, 2010)

Lycopene binding compromised PDGF-AA/-AB signaling and migration in smooth muscle cells and fibroblasts: prediction of the possible lycopene binding site within PDGF - Ching-Pei Chen; Chi-Feng Hung; Shao-Chen Lee; Huey-Ming Lo; Pi-Hui Wu; Wen-Bin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Threatened fishes of the world: Squalidus banarescui Chen and Chang, 2007 (Cyprinidae) - I-Shiung Chen; Nian-Hong Jang-Liaw; Yun-Ching Chang; Villien Weiyun Zhang; Kwang-Tsao Shao (Environmental Biology of Fishes, 2010)

Early-life or lifetime sun exposure, sun reaction, and the risk of squamous cell carcinoma in an Asian population - Yen-Ching Chen; David C. Christiani; Huey-Jen Jenny Su; Yu-Mei Hsueh; Thomas J. Smith; Louise M. Ryan; Sheau-Chiou Chao; Julia Yu-Yun Lee; Yue-Liang Leon Guo (Cancer Causes & Control, 2010)

Salicylic acid-mediated hydrogen peroxide accumulation and protection against Cd toxicity in rice leaves - Yun-Yang Chao; Chao-Yeh Chen; Wen-Dar Huang; Ching Huei Kao (Plant and Soil, 2010)

A Mediated Glucose Biosensor Incorporated with Reverse Iontophoresis Function for Noninvasive Glucose Monitoring - Congo Tak-Shing Ching; Tai-Ping Sun; Su-Hua Huang; Hsiu-Li Shieh; Chung-Yuan Chen (Annals of Biomedical Engineering, 2010)

Gas seepage, pockmarks and mud volcanoes in the near shore of SW Taiwan - Song-Chuen Chen; Shu-Kun Hsu; Ching-Hui Tsai; Chia-Yen Ku; Yi-Ching Yeh; Yunshuen Wang (Marine Geophysical Research, 2010)

Proteomic Analysis of the Effect of Cyanide on Klebsiella oxytoca - Petrus Tang; You-Cheng Hseu; Hui-Hsuan Chou; Kuo-Yang Huang; Ssu Ching. Chen (Current Microbiology, 2010)

Sea level fluctuations on the east coast of Taiwan that overlie continental shelf break - David Ching-Fang Shih; Yue-Gau Chen; Gwo-Fong Lin; Yih-Min Wu; Yee-Ping Jia; Chih-Ming Ma (Stochastic Environmental Research and Risk Assessment, 2010)

Impact of GPS radio occultation data assimilation on regional weather predictions - Ching-Yuang Huang; Ying-Hwa Kuo; Shu-Ya Chen; Chuen-Tsyr Terng; Fang-Ching Chien; Pay-Liam Lin; Mien-Tze Kueh; Shu-Hua Chen; Ming-Jen Yang; Chieh-Ju Wang; Anisetty S. K. A. V. Prasad Rao (GPS Solutions, 2010)

A Reproductive Toxicology Study of Phenanthrene in Medaka (Oryzias latipes) - Ching-Yi Horng; Hui-Chen Lin; Wenjau Lee (Archives of Environmental Contamination and Toxicology, 2010)

Cloning and Characterization of ApRab4, a Recycling Rab Protein of Aiptasia pulchella, and Its Implication in the Symbiosome Biogenesis - Ming-Cheng Hong; Yung-Sen Huang; Pa-Ching Song; Wen-Wen Lin; Lee-Shing Fang; Ming-Chyuan Chen (Marine Biotechnology, 2009)

Model analyses of visual biofeedback training for EEG-based brain-computer interface - Chih-Wei Chen; Ming-Shaung Ju; Yun-Nien Sun; Chou-Ching K. Lin (Journal of Computational Neuroscience, 2009)

Production of cyclodextrin glucanotransferase from an alkalophilic Bacillus sp. by pH-stat fed-batch fermentation - Chou-Chiang Kuo; Ching-An Lin; Jing-Yi Chen; Ming-Tse Lin; Kow-Jen Duan (Biotechnology Letters, 2009)

Geomorphic characteristics of hillslope and channelized debris flows: A case study in the Shitou area of central Taiwan - Jinn-Chyi Chen; Ching-Weei Lin; Lung-Chang Wang (Journal of Mountain Science, 2009)

Ploidy doubling by in vitro culture of excised protocorms or protocorm-like bodies in Phalaenopsis species - Wen Huei Chen; Ching Yan Tang; Yu Lin Kao (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Uncertainty propagation of hydrodispersive transfer in an aquifer: an illustration of one-dimensional contaminant transport with slug injection - David Ching-Fang Shih; Yue-Gau Chen; Gwo-Fong Lin; Yih-Min Wu (Stochastic Environmental Research and Risk Assessment, 2009)

Function of CSE1L/CAS in the secretion of HT-29 human colorectal cells and its expression in human colon - Tang-Yi Tsao; Chin-Shaw Stella Tsai; Jai-Nien Tung; Shun-Liang Chen; Chia-Herng Yue; Ching-Fong Liao; Chi-Chao Wang; Ming-Chung Jiang (Molecular and Cellular Biochemistry, 2009)

Serial cytokine levels in patients with severe sepsis - Huang-Pin Wu; Chian-Kuang Chen; Kong Chung; Jo-Chi Tseng; Chung-Ching Hua; Yu-Chih Liu; Duen-Yau Chuang; Chung-Han Yang (Inflammation Research, 2009)

Classifying Cinnamomums using rough sets classifier based on interval-discretization - Ching-Hsue Cheng; Yao-Hsien Chen; Jing-Wei Liu (Plant Systematics and Evolution, 2009)

A new flavonol galloylrhamnoside and a new lignan glucoside from the leaves of Koelreuteria henryi Dummer - Tzong-Huei Lee; Yuan-Hsiang Chiang; Chin-Hui Chen; Pi-Yu Chen; Ching-Kuo Lee (Journal of Natural Medicines, 2009)

Differential load impact upon arm tremor dynamics and coordinative strategy between postural holding and position tracking - Ing-Shiou Hwang; Yi-Ching Chen; Pei-Shan Wu (European Journal of Applied Physiology, 2009)

A biotic ligand model-based toxicodynamic approach to predict arsenic toxicity to tilapia gills in cultural ponds - Bo-Ching Chen; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2009)

Effect of metal binding and posttranslational lysine carboxylation on the activity of recombinant hydantoinase - Cheng-Yang Huang; Ching-Chen Hsu; Mei-Chun Chen; Yuh-Shyong Yang (JBIC Journal of Biological Inorganic Chemistry, 2009)

Development of a Methodology for Strategic Environmental Assessment: Application to the Assessment of Golf Course Installation Policy in Taiwan - Ching-Ho Chen; Ray-Shyan Wu; Wei-Lin Liu; Wen-Ray Su; Yu-Min Chang (Environmental Management, 2009)

Estimating the economic impacts of climate change on infectious diseases: a case study on dengue fever in Taiwan - Wei-Chun Tseng; Chi-Chung Chen; Ching-Cheng Chang; Yu-Hsien Chu (Climatic Change, 2009)

Fruit Development, Ripening and Quality Related Genes in the Papaya Genome - Robert E. Paull; Beth Irikura; Pingfang Wu; Helen Turano; Nancy Jung Chen; Andrea Blas; John K. Fellman; Andrea R. Gschwend; Ching Man Wai; Qingyi Yu; Gernot Presting; Maqsudul Alam; et al. (Tropical Plant Biology, 2008)

Mana-Hox displays anticancer activity against prostate cancer cells through tubulin depolymerization and DNA damage stress - Che-Jen Hsiao; Yunn-Fang Ho; John T.-A. Hsu; Wei-Ling Chang; Yi-Cheng Chen; Ya-Ching Shen; Ping-Chiang Lyu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Co-circulating genetically divergent A2 human metapneumovirus strains among children in southern Taiwan - Hsuan-Chen Wang; Sheng-Wen Huang; Shainn-Wei Wang; Huey-Pin Tsai; David Kiang; Shih-Min Wang; Ching-Chuan Liu; Ih-Jen Su; Jen-Ren Wang (Archives of Virology, 2008)

Characteristics analysis for the flash flood-induced debris flows - Chen Chien-Yuan; Chen Lien-Kuang; Yu Fan-Chieh; Lin Sheng-Chi; Lin Yu-Ching; Lee Chou-Lung; Wang Yu-Ting; Cheung Kei-Wai (Natural Hazards, 2008)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

Cool-night temperature induces spike emergence and affects photosynthetic efficiency and metabolizable carbohydrate and organic acid pools in Phalaenopsis aphrodite - Wen-Huei Chen; Ya-Chen Tseng; Yo-Ching Liu; Chuo-Min Chuo; Pai-Ting Chen; Kai-Meng Tseng; Yi-Chun Yeh; Mang-Jye Ger; Heng-Long Wang (Plant Cell Reports, 2008)

A new labdane-type diterpene from the bark of Juniperus chinensis Linn. - Chi-I Chang; Wen-Ching Chen; Yi-Yuan Shao; Guey-Ru Yeh; Ning-Sun Yang; Wenchang Chiang; Yueh-Hsiung Kuo (Natural Product Research, 2008)

Possible involvement of MAP kinase pathways in acquired metal-tolerance induced by heat in plants - Po-Yu Chen; Kuo-Ting Lee; Wen-Chang Chi; Heribert Hirt; Ching-Chun Chang; Hao-Jen Huang (Planta, 2008)

Effects on Tyrosinase Activity by the Extracts of Ganoderma lucidum and Related Mushrooms - Chih-Ching Chien; Mei-Ling Tsai; Chin-Chu Chen; Shing-Jyh Chang; Ching-Hui Tseng (Mycopathologia, 2008)

Relationships between physiological responses and presyncope symptoms during tilting up in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2008)

Interleukin-1 receptor antagonist restores homeostatic function and limits multiorgan damage in heatstroke - Kun-Hung Shen; Chen-Kuei Chang; Mao-Tsun Lin; Ching-Ping Chang (European Journal of Applied Physiology, 2008)

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis - Ching-Feng Cheng; Shu-Hui Juan; Jin-Jer Chen; Ying-Chi Chao; His-Hsien Chen; Wei-Shiung Lian; Chun-Yi Lu; Chung-I Chang; Ted-H Chiu; Heng Lin (Apoptosis, 2008)

Gene expression variation increase in trisomy 21 tissues - Ching Yu Chou; Li Yu Liu; Chien Yu Chen; Cheng Hsien Tsai; Hsiao Lin Hwa; Li Yun Chang; Yi Shing Lin; Fon Jou Hsieh (Mammalian Genome, 2008)

Glutamic acid 219 is critical for the thermostability of a truncated α-amylase from alkaliphilic and thermophilic Bacillus sp. strain TS-23 - Long-Liu Lin; Jai-Shin Liu; Wen-Ching Wang; Szu-Han Chen; Chih-Chen Huang; Huei-Fen Lo (World Journal of Microbiology and Biotechnology, 2008)

Identification and characterization of a potyvirus causing chlorotic spots on Phalaenopsis orchids - You-Xiu Zheng; Ching-Chung Chen; Yuh-Kun Chen; Fuh-Jyh Jan (European Journal of Plant Pathology, 2008)

Sulfotransferase 1A1 and glutathione S-transferase P1 genetic polymorphisms modulate the levels of urinary 8-hydroxy-2′-deoxyguanosine in betel quid chewers - Ruey-Hong Wong; Chiung-Wen Hu; Ching-Ying Yeh; Mu-Rong Chao; Chin-Chun Chen; Jun-Huang Huang; Shih-Hsien Chang; Shin-I Lee; Hong-Shen Lee (Archives of Toxicology, 2008)

Assessment of long-term variation in displacement for a GPS site adjacent to a transition zone between collision and subduction - David Ching-Fang Shih; Yih-Min Wu; Gwo-Fong Lin; Jyr-Ching Hu; Yue-Gau Chen; Chien-Hsin Chang (Stochastic Environmental Research and Risk Assessment, 2008)

Changes in hydrogeological properties of the River Choushui alluvial fan aquifer due to the 1999 Chi-Chi earthquake, Taiwan - Cheng-Shin Jang; Chen-Wuing Liu; Yeeping Chia; Li-Hsin Cheng; You-Ching Chen (Hydrogeology Journal, 2008)

Isolation and characterization of the zebrafish Danio rerio insulin-like growth factor binding protein-3 promoter region - Ming Jun CHOU; Jian Chyi CHEN; Jyh Yih CHEN; Hong Yi GONG; Li Tzu LI; Tzou Chi HUANG; Jen Leih WU; Ching Ming KUO (Fisheries Science, 2008)

Identification and characterization of a tospovirus causing chlorotic ringspots on Phalaenopsis orchids - You-Xiu Zheng; Ching-Chung Chen; Chia-Jin Yang; Shyi-Dong Yeh; Fuh-Jyh Jan (European Journal of Plant Pathology, 2008)

Bioavailability Effect of Methylprednisolone by Polymeric Micelles - Ching-Lin Chen; Shwu-Fen Chang; Daniel Lee; Lang-Yo Yang; Yi-Hsuan Lee; Chung Y. Hsu; Shwu-Jiuan Lin; Jiahorng Liaw (Pharmaceutical Research, 2008)

Sphingosine-1-phosphate and endothelin-1 induce the expression of rgs16 protein in cardiac myocytes by transcriptional activation of the rgs16 gene - Sabine Stuebe; Thomas Wieland; Elisabeth Kraemer; Alexandra v. Stritzky; Diana Schroeder; Sünje Seekamp; Andreas Vogt; Ching-Kang Chen; Monica Patten (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Single Strand DNA Breaks in Human Lymphocytes Exposed to para-Phenylenediamine and its Derivatives - Soi Mei Chye; You Cheng Hseu; Shih-Hsiung Liang; Chin-Hui Chen; Ssu Ching Chen (Bulletin of Environmental Contamination and Toxicology, 2008)

The blood-brain barrier in the cerebrum is the initial site for the Japanese encephalitis virus entering the central nervous system - Tsan-Hsiun Liu; Li-Ching Liang; Chien-Chih Wang; Huei-Chung Liu; Wei-June Chen (Journal of NeuroVirology, 2008)

Glycated type 1 collagen induces endothelial dysfunction in culture - Pei-Ching Kuo; Cheng-Heng Kao; Jan-Kan Chen (In Vitro Cellular & Developmental Biology - Animal, 2007)

Development of a biofeedback tilt-table for investigating orthostatic syncope in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2007)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

Lignans and anthraquinones from the fruits of Morinda citrifolia - Chwan Fwu Lin; Ching Li Ni; Yu Ling Huang; Shuenn Jyi Sheu; Chien Chih Chen (Natural Product Research, 2007)

Two new xeniolides from a Taiwanese Xenia soft coral - Ya-Ching Shen; Yu-Hui Chen; Yuan-Bin Cheng; Yao Haur Kuo; Ashraf Taha Khalil (Natural Product Research, 2007)

Delimitation of arsenic-contaminated groundwater using risk-based indicator approaches around blackfoot disease hyperendemic areas of southern Taiwan - Cheng-shin Jang; Chen-wuing Liu; Kuang-liang Lu; Ching-chieh Lin (Environmental Monitoring and Assessment, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A Bacterial Indole-3-acetyl-L-aspartic Acid Hydrolase Inhibits Mung Bean (Vigna radiata L.) Seed Germination Through Arginine-rich Intracellular Delivery - Kevin Liu; Han-Jung Lee; Sio San Leong; Chen-Lun Liu; Jyh-Ching Chou (Journal of Plant Growth Regulation, 2007)

PaCDPK1, a gene encoding calcium-dependent protein kinase from orchid, Phalaenopsis amabilis, is induced by cold, wounding, and pathogen challenge - Tsung-Mu Tsai; Ying-Ru Chen; Tien-Wen Kao; Wen-Su Tsay; Chiou-Ping Wu; Ding-Ding Huang; Wen-Huei Chen; Ching-Chun Chang; Hao-Jen Huang (Plant Cell Reports, 2007)

The Assimilation of GPS Radio Occultation Data and its Impact on Rainfall Prediction along the West Coast of India during Monsoon 2002 - Ching-Yuang Huang; Ying-Hwa Kuo; Shu-Ya Chen; Anisetty S. K. A. V. Prasad Rao; Chien-Ju Wang (Pure and Applied Geophysics, 2007)

Development of a molecular marker for a bruchid (Callosobruchus chinensis L.) resistance gene in mungbean - Huei-Mei Chen; Chien-An Liu; C. George Kuo; Ching-Mei Chien; Horng-Chi Sun; Chung-Chu Huang; Yu-Chung Lin; Hsin-Mei Ku (Euphytica, 2007)

Genetic analysis of an attenuated Papaya ringspot virus strain applied for cross-protection - Chu-Hui Chiang; Chun-Yee Lee; Ching-Hsien Wang; Fuh-Jyh Jan; Shih-Shun Lin; Tsung-Chi Chen; Joseph A. J. Raja; Shyi-Dong Yeh (European Journal of Plant Pathology, 2007)

Characterization of a novel T4-type Stenotrophomonas maltophilia virulent phage Smp14 - Chiy-Rong Chen; Ching-Hsuan Lin; Juey-Wen Lin; Chi-I Chang; Yi-Hsiung Tseng; Shu-Fen Weng (Archives of Microbiology, 2007)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

Inhibition of Cyanide-Insensitive Respiration in Klebsiella oxytoca SYSU-011 by 8-Hydroxyquinolone - Chih Ming Kao; You Cheng Hseu; Yen Ling Huang; Peturs Tang; Ssu Ching Chen (Current Microbiology, 2007)

A web-based decision support system for slopeland hazard warning - Yu Fan-Chieh; Chen Chien-Yuan; Lin Sheng-Chi; Lin Yu-Ching; Wu Shang-Yu; Cheung Kei-Wai (Environmental Monitoring and Assessment, 2007)

Detection and identification of the phytoplasma associated with pear decline in Taiwan - Hsiu-Lin Liu; Ching-Chung Chen; Chan-Pin Lin (European Journal of Plant Pathology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Enhancement of water storage capacity in wetland rice fields through deepwater management practice - Yu‐Chuan Chang; Chun‐E. Kan; Ching‐Tien Chen; Sheng‐Feng Kuo (Irrigation and Drainage, 2007)
Paddy field storage of rainfall by bunds is like a rainwater cistern system during the rainy season. Deepwater management practice in paddy fields might be good for rice production and water storage capacity at the same time. The study was conducted in an experiment testing two water management treatments with six rice variety treatments using two lysimeter experiments. The results revealed that deepwater management significantly affected rice production. On the other hand, deepwater management increased the effective rainfall (70 mm) and percolation (225 mm). The runoff coefficient under deepwater management decreased from 0.67 to 0.53. It was reasonable to conclude that the deepwater management provided more water storage capacity during the growing season. Finally, water productivity results point out that even though the volume of input water under deepwater management had increased, deepwater management still can generate higher water productivity. It looks as if it is pointless to save water during the rainy season. On the contrary, if excess water is available in rivers, it should be delivered in timely fashion to the wetland rice fields to increase effective rainfall and the excess saved by maintaining adequate percolation to replenish groundwater, without having to follow strict water conservation measures. Copyright © 2007 John Wiley & Sons, Ltd.

Improving debris flow monitoring in Taiwan by using high-resolution rainfall products from QPESUMS - Chien-Yuan Chen; Lee-Yao Lin; Fan-Chieh Yu; Ching-Sheng Lee; Chun-Chieh Tseng; An-Hsiang Wang; Kei-Wai Cheung (Natural Hazards, 2007)

Sustainable Water Quality Management Framework and a Strategy Planning System for a River Basin - Ching-Ho Chen; Wei-Lin Liu; Horng-Guang Leu (Environmental Management, 2006)

Organization and promoter analysis of a tiger shrimp Penaeus monodon single WAP domain-containing protein gene - Jyh Yih CHEN; Jian Chyi CHEN; Sheng Hwa LIN; Chia Yu PAN; Ching Ming KUO (Fisheries Science, 2006)

Location and Characterization of Emission Sources for Airborne Volatile Organic Compounds Inside a Refinery in Taiwan - Ching-Liang Chen; Chi-Min Shu; Hung-Yuan Fang (Environmental Monitoring and Assessment, 2006)

Screening of Compactin-Resistant Microorganisms Capable of Converting Compactin to Pravastatin - Chao-Hsien Chen; Hui-Yu Hu; Yen-Ching Cho; Wen-Hwei Hsu (Current Microbiology, 2006)

Alpha-smooth muscle actin expression and structure integrity in chondrogenesis of human mesenchymal stem cells - Shih-Chieh Hung; Pei-Yin Kuo; Ching-Fang Chang; Tain-Hsiung Chen; Larry Low-Tone Ho (Cell and Tissue Research, 2006)

Using the Selective Ion Exchange Resin Extraction and XANES Methods to Evaluate the Effect of Compost Amendments on Soil Chromium(VI) Phytotoxicity - Dar-Yuan Lee; Yu-Na Shih; Hsiu-Ching Zheng; Chiou-Pin Chen; Kai-Wei Juang; Jyh-Fu Lee; Lo Tsui (Plant and Soil, 2006)

Site-specific phosphorylation of L-form starch phosphorylase by the protein kinase activity from sweet potato roots - Guang-Huar Young; Han-Min Chen; Chi-Tsai Lin; Kuang-Ching Tseng; Jiann-Shing Wu; Rong-Huay Juang (Planta, 2006)

Chloroplast sulfate transport in green algae – genes, proteins and effects - Anastasios Melis; Hsu-Ching Chen (Photosynthesis Research, 2005)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Mitogenomic analysis of Montipora cactus and Anacropora matthai (cnidaria; scleractinia; acroporidae) indicates an unequal rate of mitochondrial evolution among Acroporidae corals - Ching-Chih Tseng; Carden C. Wallace; Chaolun Allen Chen (Coral Reefs, 2005)

Sleep-related vagotonic effect of zolpidem in rats - Hsiao Ying Chen; Terry B. J. Kuo; Fu-Zen Shaw; Ching J. Lai; Cheryl C. H. Yang (Psychopharmacology, 2005)

Mapping dopamine D2/D3 receptor function using pharmacological magnetic resonance imaging - Yin-Ching I. Chen; Ji-Kyung Choi; Susan L. Andersen; Bruce R. Rosen; Bruce G. Jenkins (Psychopharmacology, 2005)

Role of SulP, a nuclear-encoded chloroplast sulfate permease, in sulfate transport and H2evolution in Chlamydomonas reinhardtii - Hsu-Ching Chen; A. Jamila. Newton; Anastasios Melis (Photosynthesis Research, 2005)

Polymorphism for Transforming Growth Factor Beta 1-509 (TGF-B1-509): Association with Endometriosis - Yao-Yuan Hsieh; Chi-Chen Chang; Fuu-Jen Tsai; Ching-Tien Peng; Lian-Shun Yeh; Cheng-Chieh Lin (Biochemical Genetics, 2005)

A Natural Compound (Ginsenoside Re) Isolated from Panax ginseng as a Novel Angiogenic Agent for Tissue Regeneration - Ya-Chun Huang; Chiung-Tong Chen; Sung-Ching Chen; Po-Hong Lai; Huang-Chien Liang; Yen Chang; Lin-Chien Yu; Hsing-Wen Sung (Pharmaceutical Research, 2005)

Interaction between environmental tobacco smoke and arsenic methylation ability on the risk of bladder cancer - Yen-Ching Chen; Huey-Jen Jenny Su; Yu-Liang Leon Guo; E. Andres Houseman; David C. Christiani (Cancer Causes & Control, 2005)

Some isotopic and hydrological changes associated with the 1999 Chi‐Chi earthquake, Taiwan - Chung‐Ho Wang; Chi‐Yuen Wang; Ching‐Huei Kuo; Wen‐Fu Chen (Island Arc, 2005)
The changes in the isotopic composition of, and the groundwater level in, the Choshui River alluvial fan near the ruptured Chelungpu Fault during and following the 1999 ( M w = 7.5) Chi‐Chi earthquake in Taiwan are reported. Three aspects of the hydrological changes are noticed. First, following the Chi‐Chi earthquake, the lower aquifers beneath the Choshui River fan showed a significant shift in isotopic composition towards that of the surface water in the Choshui River, suggesting enhanced exchanges of water between the river and the groundwater. Second, in some wells, water levels and isotopic compositions in different aquifers converged to the same respective values during the Chi‐Chi earthquake, suggesting coseismic exchanges of water between the different aquifers, which implies enhanced permeability due perhaps to the fracturing and breaching of aquitards between the aquifers. Third, the pattern of the coseismic water‐level response is distinctly different from that of the shift in the isotopic composition, suggesting that they were produced by different mechanisms.

Distribution of albacore ( Thunnus alalunga ) in the Indian Ocean and its relation to environmental factors - I‐CHING CHEN; PEI‐FEN LEE; WANN‐NIAN TZENG (Fisheries Oceanography, 2005)
The distribution pattern of albacore, Thunnus alalunga , in the Indian Ocean was analyzed based on catch data from the Taiwanese tuna longline fishery during the period 1979–85. The Taiwanese tuna fishery began operating in the Indian Ocean in 1967. We used a geographic information system to compile a fishery and environmental database and statistically explored the catch per unit effort (CPUE) distribution of albacore. Our results indicated that immature albacore were mainly distributed in areas south of 30°S although some displayed a north–south seasonal migration. Mature albacore, which were mainly concentrated between 10°S and 25°S, also showed a north–south migration. Within 10°S and 30°S, the separation of mature, spawning, and immature albacore life history stages roughly coincided with the boundaries of the three oceanic current systems in the Indian Ocean. The optimal environmental variables for CPUE prediction by stepwise discriminant analysis differed among life history stages. For immature albacore, the sea surface variables sea surface temperature (SST), chlorophyll concentration and surface salinity were significant. For mature albacore, SST was significant, while for spawning albacore, the sub‐surface variables temperature at 100 m and oxygen at 200 m were significant. Spawning albacore evidently prefer deep oceanographic conditions. Our results on the oceanographic conditions preferred by different developmental stages of albacore in the Indian Ocean were compatible with previous studies found in the Pacific Ocean.

Localization and function of SulP, a nuclear-encoded chloroplast sulfate permease in Chlamydomonas reinhardtii - Hsu-Ching Chen; Anastasios Melis (Planta, 2004)

Characterization of the genomic structures and selective expression profiles of nine class I small heat shock protein genes clustered on two chromosomes in rice (Oryza sativa L.) - Jiahn-Chou Guan; Tsung-Luo Jinn; Ching-Hui Yeh; Shi-Pin Feng; Yih-Ming Chen; Chu-Yung Lin (Plant Molecular Biology, 2004)

Polyacetylenes Function as Anti-Angiogenic Agents - Li-Wha Wu; Yi-Ming Chiang; Hsiao-Ching Chuang; Sheng-Yang Wang; Ga-Wen Yang; Ya-Huey Chen; Ling-Ya Lai; Lie-Fen Shyur (Pharmaceutical Research, 2004)

Resonance Induced by Edge Waves in Hua-Lien Harbor - Guan-Yu Chen; Chung-Ching Chien; Ching-Ho Su; Hsiang-Mao Tseng (Journal of Oceanography, 2004)

Characterization and Virulence of Hemolysin III from Vibrio vulnificus - Yu-Chung Chen; Ming-Chung Chang; Yin-Ching Chuang; Chii-Ling Jeang (Current Microbiology, 2004)

Detection of cefotaxime-resistant CTX-M-3 in clinical isolates ofSerratia marcescens - Mei-Fen Tsou; Wen-Liang Yu; Siu Wan Hung; Chizh-Ju Chi; Chieh-Ju; Ssu Ching Chen; Lii-Tzu Wu (Folia Microbiologica, 2004)

Inhibitory effect of resveratrol on angiotensin II-induced cardiomyocyte hypertrophy - Tzu-Hurng Cheng; Ju-Chi Liu; Heng Lin; Neng-Lang Shih; Yen-Ling Chen; Meng-Ting Huang; Paul Chan; Ching-Feng Cheng; Jin-Jer Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Cloning of Two Crustacean Hyperglycemic Hormone Isoforms in Freshwater Giant Prawn ( Macrobrachium rosenbergii ): Evidence of Alternative Splicing - Shu-Hwa Chen; Chung-Yen Lin; Ching Ming Kuo (Marine Biotechnology, 2004)

Isolation and characterization of microsatellite loci in Acrossocheilus paradoxus (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Kui-Ching Hsu; Jiang-Ping Wang; Xiang-Lin Chen; Tzen-Yuh Chiang (Conservation Genetics, 2004)

SulP , a nuclear gene encoding a putative chloroplast-targeted sulfate permease in Chlamydomonas reinhardtii - Hsu-Ching Chen; Kittisak Yokthongwattana; A. Jamila Newton; Anastasios Melis (Planta, 2003)

Alpha-naphthoflavone induces vasorelaxation through the induction of extracellular calcium influx and NO formation in endothelium - Yu-Wen Cheng; Ching-Hao Li; Chen-Chen Lee; Jaw-Jou Kang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Mycogloea nipponica - the first known teleomorph in the heterobasidiomycetous yeast genus Kurtzmanomyces - Roland Kirschner; José Paulo Sampaio; Dominik Begerow; Zuei-Ching Chen; Franz Oberwinkler (Antonie van Leeuwenhoek, 2003)

Allele-specific differential expression of a common adiponectin gene polymorphism related to obesity - Wei-Shiung Yang; Pei-Ling Tsou; Wei-Jei Lee; Da-Lun Tseng; Chi-Ling Chen; Chi-Chung Peng; Kuan-Ching Lee; Mei-Ju Chen; Chang-Jen Huang; Tong-Yuan Tai; Lee-Ming Chuang (Journal of Molecular Medicine, 2003)

Arsenic methylation and bladder cancer risk in Taiwan - Yen-Ching Chen; Huey-Jen Jenny Su; Yu-Liang Leon Guo; Yu-Mei Hsueh; Thomas J. Smith; Louise M. Ryan; Meei-Shyuan Lee; David C. Christiani (Cancer Causes & Control, 2003)

Noninvasive Characterization of Regional Variation in Drug Transport into Human Stratum Corneum in Vivo - Jui-Chen Tsai; Ching-Yu Lin; Hamm-Ming Sheu; Yu-Li Lo; Ying-Hsuan Huang (Pharmaceutical Research, 2003)

Establishment of red fluorescent protein-tagged HeLa tumor metastasis models: Determination of DsRed2 insertion effects and comparison of metastatic patterns after subcutaneous, intraperitoneal, or intravenous injection - Jau-Yeong Lu; Hui-Chun Chen; Ricky Yuan-Yuan Chu; Tsu-Chun Emma Lin; Ping-I Hsu; Ming-Shyan Huang; Ching-Jiunn Tseng; Michael Hsiao (Clinical & Experimental Metastasis, 2003)

AtHVA22 gene family in Arabidopsis: phylogenetic relationship, ABA and stress regulation, and tissue-specific expression - Ching-Nen Chen; Chiung-Chih Chu; Rodolfo Zentella; Shu-Mei Pan; Tuan-Hua David Ho (Plant Molecular Biology, 2002)

Microsatellite polymorphism in promoter of heme oxygenase-1 gene is associated with susceptibility to coronary artery disease in type 2 diabetic patients - Ying-Hwa Chen; Shing-Jong Lin; Ming-Wei Lin; Hui-Ling Tsai; San-San Kuo; Jaw-Wen Chen; Min-Ji Charng; Tao-Cheng Wu; Lung-Ching Chen; Philip Ding; Wen-Harn Pan; Yuh-Shan Jou; et al. (Human Genetics, 2002)

Wogonin and fisetin induction of apoptosis through activation of caspase 3 cascade and alternative expression of p21 protein in hepatocellular carcinoma cells SK-HEP-1 - Yen-Chou Chen; Shing-Chuan Shen; Woan-Rouh Lee; Hui-Yi Lin; Ching-Huai Ko; Chun-Ming Shih; Ling-Ling Yang (Archives of Toxicology, 2002)

Wound-response regulation of the sweet potato sporamin gene promoter region - Shu-Jen Wang; Yi-Ching Lan; Shih-Fung Chen; Yih-Ming Chen; Kai-Wun Yeh (Plant Molecular Biology, 2002)

Neurogenesis of cuneothalamic neurons and NO-containing neurons in the cuneate nucleus of the rat - Tsyr-Jiuan Wang; June-Horng Lue; Ching-Hsiang Wu; Jeng-Yung Shieh; Chen-Yuan Wen (Experimental Brain Research, 2002)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

Cloning and characterization of a DEAD box RNA helicase from the viable seedlings of aged mung bean - Sing-Chung Li; Mei-Chu Chung; Ching-San Chen (Plant Molecular Biology, 2001)

Sequencing and Amplified Restriction Fragment Length Polymorphism Analysis of Ribonucleotide Reductase Large Subunit Gene of the White Spot Syndrome Virus in Blue Crab (Callinectes sapidus) from American Coastal Waters - Yun-Shiang Chang; Shao-En Peng; Han-Ching Wang; Hui-Chen Hsu; Ching-Hui Ho; Chung-Hsiung Wang; Sho-Ya Wang; Chu-Fang Lo; Guang-Hsiung Kou (Marine Biotechnology, 2001)

Improvement of phytase thermostability by using sorghum liquor wastes supplemented with starch - Chang-Chih Chen; Ching-Tsan Hunag; Kou-Joan Cheng (Biotechnology Letters, 2001)

The stress- and abscisic acid-induced barley gene HVA22: developmental regulation and homologues in diverse organisms - Qingxi Shen; Ching-Nen Chen; Alex Brands; Shu-Mei Pan; David Ho Tuan-Hua (Plant Molecular Biology, 2001)

Species of Caligus Müller, 1785 (Copepoda: Caligidae) parasitic on marine fishes of Taiwan - Ju-shey Ho; Ching-Long Lin; Shiu-Nan Chen (Systematic Parasitology, 2000)

Synthetic Glycopeptide-Based Delivery Systems for Systemic Gene Targeting to Hepatocytes - Khursheed Anwer; Mark Logan; Frank Tagliaferri; Manpreet Wadhwa; Oscar Monera; Ching-Hsuan Tung; Wei Chen; Pat Leonard; Martha French; Belinda Proctor; Elizabeth Wilson; Arun Singhal; et al. (Pharmaceutical Research, 2000)

Relationship between ammonium accumulation and senescence of detached rice leaves caused by excess copper - Li-Men Chen; Ching Huei Kao (Plant and Soil, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Purification and Characterization of a Cysteine Protease Produced by Pathogenic Luminous Vibrio harveyi - Ping-Chung Liu; Kuo-Kau Lee; Chi-Ching Tu; Shiu-Nan Chen (Current Microbiology, 1997)

Specific protein phosphorylation induced in Xanthomonas campestris pv. oryzae by bacteriophage Xp12 - Ching-Ming Cheng; Jenn Tu; Chen-Chung Yang; Tsong-Teh Kuo (Archives of Microbiology, 1994)

Specific protein phosphorylation induced in Xanthomonas campestris pv. oryzae by bacteriophage Xp12 - Tsong-Teh Kuo; Ching-Ming Cheng; Jenn Tu; Chen-Chung Yang (Archives of Microbiology, 1994)

Oxygen consumption and ammonia-N excretion of prawns (Penaeus chinensis) exposed to ambient ammonia - Jiann-Chu Chen; Fan-Hua Nan; Ching-Ming Kuo (Archives of Environmental Contamination and Toxicology, 1991)

Effect of the peroxisome proliferator perfluorodecanoic acid on growth and lipid metabolism in Sprague Dawley rats fed three dietary levels of selenium - Tim Borges; Howard P. Glauert; Li -Chuan Chen; Ching K. Chow; Larry W. Robertson (Archives of Toxicology, 1990)

Differential modulating effects of retinoic acid on interferon antiviral activity - Chi-Kuan Ho; Bor-Rung Ou; Ching-Yun Wang; Hour-Young Chen; Tsuguo Kuwata (Archives of Virology, 1989)